Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.

Soils and broad-scale topography predict historical stand structure across Front Range dry conifer forests - Kevin G. Willson; Paula J. Fornwalt; Mike A. Battaglia; Peter M. Brown; Antony S. Cheng; Benjamin Gannon; Wade T. Tinkham (Forest Ecology and Management, 2026)

Characterizing snow roughness: A novel low-cost portable tool based on ChArUco board and digital photography - Riccardo Barella; Francesca Carletti; Katharina T. Scheidt; Antonio Mazza; Mathias Bavay; Benjamin Walter; Carlo Marin (Cold Regions Science and Technology, 2026)

Consistent carbon isotope ordering of cyanobacterial lipids - Fatima Husain; Benjamin T. Uveges; Gareth Izon; Gaozhong Shen; Roger E. Summons (Organic Geochemistry, 2026)

Political ideology as a predictor of conservation attitudes: Mechanisms and implications - Benjamin Ghasemi; Jeremy T. Bruskotter (Ambio, 2026)

Impacts of Ocean Acidification on Reproduction and Early Life Development in Marine Teleost Fish—A Synthesis - Rebecca J. Bridge; Benjamin T. McClelland; Silvana N. R. Birchenough; Martina H. Stiasny (Fish and Fisheries, 2026)
Ocean acidification (OA) remains a major and underexplored threat to marine fishes, particularly regarding reproductive physiology and early life stages (ELS). Although research over the past 15 years has documented diverse OA effects, substantial knowledge gaps persist. Most studies focussed on a limited set of species from North America and Europe, leaving broad uncertainty across phylogenetic groups, geographic regions and multi‐stressor conditions. In adult fish, especially females, elevated p CO 2 can shift energy allocation to prioritise reproductive output at the expense of egg or clutch size. While adult and juvenile fish have well‐developed acid–base balancing systems, embryos and larvae possess only rudimentary mechanisms, making them more vulnerable to OA. This article stresses the importance of understanding these physiological and mechanistic responses to predict the future of fish stocks and ecosystem health as OA intensifies due to ongoing CO 2 emissions. Our results highlight that OA responses in fish are highly variable and often specific to life stage and species, with acute and sometimes stage‐specific effects not fully documented. Lastly, our recommendations on targeted research and funding are necessary to address the remaining knowledge gaps, including broadening taxonomic and geographic sampling, exploring multi‐stressor scenarios and improving understanding of the downstream effects of OA on fish reproduction and development. Maintaining robust fish populations is vital for food security, employment and ecosystem functioning, making continued investigation into OA's impacts a scientific and societal priority.

Temporal and spatial changes in fish assemblages associated with the placement of a rock armoured pipeline complex in northwestern Australia - Brooke T. Marshall; Euan S. Harvey; Travis S. Elsdon; Michael J. Marnane; Paul de Lestang; Christopher Jones; Kurt Wiegele; Benjamin J. Saunders (Marine Environmental Research, 2026)

A molybdenum isotope perspective on oceanic palaeoredox conditions during the Cryogenian non-Snowball interlude - Jin Li; Xiang-kun Zhu; Fred T. Bowyer; Benjamin J.W. Mills; Xi Peng; Bin Yan; Simon W. Poulton (Global and Planetary Change, 2026)

Geochemical data links Late Quaternary-age concretion formation to North Atlantic cold climate episodes - Angel Mojarro; Adam B. Jost; Benjamin T. Uveges; Kristin D. Bergmann; Tyler Mackey; Diana Dumit; Mark L. Roberts; Jakob Vinther; Kristian Svennevig; Lisbeth L. Pedersen; Lis Allaart; Ole Bennike; et al. (Geochimica et Cosmochimica Acta, 2026)

Silymarin Reverses Seizure-Precipitating Effects of Alcohol and Associated Psychiatric Comorbidities, and Neurotoxicity in Pentylenetetrazol Pre-Kindled Mice - Benneth Ben-Azu; Itivere A. Omogbiya; Joseph O.T. Emudainohwo; Aliance R. Fokoua; Olajide S. Annafi; Bienose S. Chijioke; Daniel T. Esuku; Emmanuel O. Chidebe; Benjamin Oritsemuelebi; Maxwell Oboh; Whiliki Oscar Onoriadjeren; Eze K. Nwangwa (Neurotoxicity Research, 2026)

Dietary wheat bran pretreated with xylanase and glucanase mixture modulates growth performance, antioxidant capacity, and immune response in Nile tilapia fingerlings - Benjamin U. Akpoilih; Ibrahim Adeshina; Adibabari T. Poromon; Mohsen Abdel-Tawwab (Aquaculture International, 2026)

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

The potential impact of microplastic contamination in cow manure on maternal dung burying behavior and larval survival in the dung beetle Onthophagus taurus - Nathan J. McConnell; Jaydon Galindo Lovell; Jill Walker; Benjamin J. Mathews; Scott G. Morton; Jonathan B. Shurin; Patrick T. Rohner (Chemosphere, 2026)

Abundance-based distribution modelling reveals climate-driven loss of functionally important kelp forest habitat - Patrick Eskuche-Keith; Heather E. Sugden; Michael T. Burrows; Pippa J. Moore; Clare Fitzsimmons; Dan A. Smale; Benjamin Hall; Fabrice Stephenson (Journal of Environmental Management, 2026)

Spatial Phylogenetic and Functional Diversity in Africa—A Case Study of the Cyperaceae (Poales) - Benjamin D. Williams; Israel T. Borokini; Daniel A. Zhigila; Alfred A. Oteng‐Yeboah; A. Muthama Muasya (Journal of Biogeography, 2026)
Aim Understanding the mechanisms that influence the patterns of diversification and spatiotemporal distribution of biodiversity requires integrating species, functional and phylogenetic data. In this study, we assembled, generated and integrated trait data of native plants in Cyperaceae across Africa with their known occurrences and a pruned phylogeny to map the centres of diversity and diversification in Africa. Location Africa and adjacent Oceanic Islands. Methods We assembled 144,001 occurrence records for 643 species of Cyperaceae in Africa that are represented on a chronogram phylogeny, 10 functional traits for these species, and 10 environmental variables. We calculated taxonomic and phylogenetic alpha and beta diversity measures, mapped centres of neo‐ and paleo‐endemism and seven functional diversity measures using a grid of 1° × 1° cells across Africa. Results Our study found areas of high species and phylogenetic diversity in the Okavango Basin, while endemism was the highest in the Mediterranean southern Africa and Madagascar. We also observed centres of paleo‐endemism in closed habitats of West Tropical Africa, while mixed and super‐endemism hotspots are pronounced in the Cape and Madagascar. Beta diversity identified three clusters spatially distributed along climatic zones, thus indicating shared lineages. Functional richness was the highest in the Congolian region, while evenness, divergence and dispersion were mostly high and broadly distributed across the continent. Main Conclusions Spatial patterns of phylogenetic clustering and overdispersion of sedges in Africa indicate varying biogeographical processes across the continent, leading to species with distinct evolutionary histories. The southern region shows high endemism but low functional richness, indicating in situ diversification and functional redundancy among Cyperaceae adapted to extreme conditions. Conversely, the rainforest region exhibits high functional richness due to variability in leaf traits and photosynthetic pathways in response to diverse habitat conditions. This study underscores the eco‐evolutionary mechanisms influencing plant biogeographical patterns in Africa.

Impacts from sector-specific energy policies on mortality: Co-benefits and socioeconomic disparities across three midwestern states in the year 2050 - Rory K. Stewart; Kiarash Farzad; Yang Zhang; Kenneth T. Gillingham; Benjamin F. Hobbs; Daniel C. Esty; Michelle L. Bell (Environmental Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Use of Unmanned Aerial Vehicles in Precision Agriculture: An Exploration of Remotely Sensed Data and Methods for Monitoring Corn Varieties - Benjamin T. Fraser; Russell G. Congalton; Peter H. Davis; Tom Beaudry; Carl Majewski; Aaron Palmer (Agricultural Research, 2026)

Diet composition of data‐limited marlins ( Istiophoridae ) in the Northwest Atlantic - Joseph J. Dello Russo; John M. Logan; Riley Austin; Zachary T. Whitener; Isabelle Sée; Benjamin M. Hurley; Lisa A. Kerr; Joseph M. Quattro; Walter J. Golet (Journal of Fish Biology, 2026)
Knowledge of the dietary composition of Atlantic marlins, especially for recently acknowledged species such as roundscale spearfish ( Tetrapturus georgii ), is limited, as sample access is constrained by international quotas and intermittent landing rates. A series of annual offshore recreational fishing tournaments target Atlantic blue marlin ( Makaira nigricans ), white marlin ( Kajikia albida ) and roundscale spearfish on their seasonal foraging grounds in the South and Mid‐Atlantic Bight. Through this network of tournaments and recreational anglers, we collected stomachs from Atlantic blue marlin ( n = 32), white marlin ( n = 35) and roundscale spearfish ( n = 44) from 2018 to 2020 to investigate general diet composition. Stomach content analysis and DNA barcoding identified a total of 16 prey families across the three focal species, but the majority of prey weight (%W) was from two families (Scombridae and Ommastrephidae). Blue marlin and roundscale spearfish were predominantly piscivorous (99.0 and 80.6%W fishes, respectively), whereas white marlin mainly consumed cephalopods (80%W). The contribution of Scombridae was highest for blue marlin (94.6%W), intermediate for roundscale spearfish (51.7%W) and lowest for white marlin (11%W), with an inverse pattern of relative contribution for Ommastrephidae (0.9, 16.1 and 73.9%W, respectively). Roundscale spearfish and white marlin, despite having a near identical morphology, had diets composed of different prey types in our sample. These dietary data, from three epipelagic apex predators, provide important information for wider ecosystem‐based studies, including in relation to the Mackerel, Squid and Butterfish Fishery Management Plan overseen by the Mid‐Atlantic Fishery Management Council.

Psychometric framework for coexistence with large carnivores - Benjamin Ghasemi; Gerard Kyle; Tara Teel; Rebeca Niemiec; Kevin Crooks; Jenny Anne Glikman; Neil H. Carter; John A. Vucetich; Michelle L. Lute; Stewart Breck; Beatrice Frank; Dana Hoag; et al. (Conservation Biology, 2026)
Human–carnivore coexistence is essential for biodiversity conservation, yet measuring the attitudes and behaviors that support it remains methodologically challenging. We developed psychometric scales to assess willingness to coexist with carnivores and the underlying beliefs of this coexistence through an iterative expert elicitation process grounded in risk perception theory and moral psychology to ensure strong content validity. The scales measure willingness to coexist and encompass individual and collective behaviors and their cognitive antecedents: perceived positive consequences, perceived negative consequences, and ethical considerations. We validated the scales based on three representative samples of Colorado residents ( n = 434, 442, 433) focused on gray wolves ( Canis lupus ), mountain lions ( Puma concolor ), and black bears ( Ursus americanus ). Validation involved expert review, cognitive interviews, confirmatory factor analyses, and measurement invariance testing across species. The scales demonstrated strong construct validity, with factor structures consistent with theoretical expectations and evidence of convergent and discriminant validity. Concurrent validity was supported through associations with related attitudes and behavioral intentions. These instruments offer researchers a robust, theory‐driven framework for examining human–wildlife interactions that facilitates standardized comparisons across species and contexts. For practitioners, the psychometric scales provide a practical means to assess public readiness for coexistence, monitor attitudinal change over time, and design interventions tailored to specific belief structures.

Understanding mitigation intentions for aquatic invasive species: A protection motivation theory perspective - Benjamin Ghasemi; Gerard T. Kyle; Monica E. McGarrity (Ambio, 2026)

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Isolation, characterization of endophytic mycobionts and their utilization for the acclimatization of in vitro propagated plantlets of Anoectochilus elatus – a near threatened terrestrial jewel orchid - N. Ahamed Sherif; J. H. Franklin Benjamin; M. N. Abubacker; T. Senthil Kumar; M. V. Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Extreme wave events inferred from large subaerial carbonate boulders on a rocky coast in Pasuquin, Ilocos Norte, Philippines - Edrian M. Tubalado; Noelynna T. Ramos; Lyndon P. Nawanao; Ace Matthew F. Cantillep; Alec Benjamin G. Ramirez; Jelian S. Reyes; Kathrine V. Maxwell; Shou-Yeh Gong; Tsai-Luen Yu; Chuan-Chou Shen (Marine Geology, 2026)

The cytochrome P450s CYP6CY3 and CYP6CY4 confer resistance to flupyradifurone in the green peach aphid Myzus persicae - Jun Yuan; Bin Zeng; Benjamin J. Hunt; Bartlomiej J. Troczka; Xingzhi Xiao; James Gardner; Faye Papadimitriou; Jason Charamis; Aris Ilias; Adam Pym; Konstantinos Mavridis; Dieudonné T. Tshitenge; et al. (Insect Biochemistry and Molecular Biology, 2026)

A mid‐Proterozoic coupled Sr and Li isotope excursion and its potential connection to enhanced weathering and ocean oxygenation at 1.57 Ga - Xi Chen; Ying Zhou; Simon W. Poulton; Fred T. Bowyer; Colin Mettam; Shihong Zhang; Maoyan Zhu; Da Li; Philip A.E. Pogge von Strandmann; Benjamin J.W. Mills; Graham A. Shields (Earth and Planetary Science Letters, 2026)

Species sorting and spatial effects in hyporheic invertebrate functional groups - Benjamin T. Hutchins; Zoey B. Chanin; Kathryn E. Perez; Peter H. Diaz; Benjamin F. Schwartz (Hydrobiologia, 2026)
Invertebrate communities in the hyporheic zone are structured by metacommunity processes including environmental filtering and spatial effects (e.g., dispersal). We investigated how these processes differentially influence two functional groups: groundwater-obligate invertebrates (stygobionts) and benthic insects. We predicted that environmental filtering would dominate for insects, while spatial effects would prevail for stygobionts. We collected 76 samples from 28 hyporheic sites along 109 km of the Rio Grande, Texas, USA, enumerating 54,508 individuals across 80 taxa. Concordance analysis and RDA revealed two communities: one dominated by insects, and another by crustaceans and soft-bodied organisms, including all stygobionts. In linear models, insect richness and abundance were influenced by temperature, alkalinity, oxygen, and pH. Stygobionts were associated with higher nitrate, higher temperature, and lower specific conductance (indicating groundwater discharge in the study area). Stygobiont presence, richness, and abundance increased near springs. Stygobiont communities exhibited spatial autocorrelation while insect communities did not. Insect responses to environmental variables suggest species sorting effects, which prevail for taxa with sufficient dispersal ability. Stygobiont responses to spatial variables suggest limited dispersal from source populations in adjacent aquifers. Dispersal ability may limit stygobionts’ ability to recolonize habitats after hydrologic disturbances, especially when connection with adjacent aquifers is lost.

Modeling the Influence of Directional Swimming Ability in American Lobster ( Homarus americanus ) Postlarvae on Settlement - Jang‐Geun Choi; Joshua T. Carloni; Benjamin C. Gutzler; Winsor Watson; Steven Jury; Thomas C. Lippmann; Jason S. Goldstein (Fisheries Oceanography, 2026)
We developed a particle tracking model for the transport and dispersion of American lobster ( Homarus americanus ) larvae for the Gulf of Maine (GoM) that considers both passively drifting larval stages and their swimming ability during the postlarval (pre‐settlement) stage. The model takes into account two characteristics of the postlarval stage: directional swimming toward shallower regions and diel fluctuations of their swimming speed. Diffusivity (lateral mixing), based on surface GPS drifter observations, was also considered and used to validate this model. Numerical experiments, using the hydrodynamics predicted by the Gulf of Maine Operational Forecasting System (GoMOFS) model, were conducted to test the potential impact of postlarval swimming ability on successful settlement on suitable habitat (defined as regions shallower than 20 m). The results of this experiment showed that elevated swimming ability (18 cm/s) in postlarvae significantly improves settlement success compared to trials modeling postlarvae with a diminished swimming ability (7 cm/s), or no swimming ability (control) at all. In contrast, diel swimming behavior in postlarvae slightly decreased successful settlement. In addition, ocean drifter observations and numerical simulations consistently revealed that successful settlement decreases the further the initial release point of larvae is from the coast. Combined, these experiments indicate that both the swimming ability of postlarvae and the distance they are from shore when they hatch are critical factors that influence their potential to reach viable settlement locations in the GoM. These data also suggest that if the GoM continues to warm, and females move further offshore to avoid warmer inshore waters, the settlement success of their larvae may be compromised.

Contamination of commercial 15 N 2 : potential impacts on nitrogen fixation assays and a simple method for quantification - Benjamin T. Uveges; Kimberlee L. Sparks; Warren S. Ang; Hannah Monti; Fay-Wei Li; Jed P. Sparks (Isotopes in Environmental and Health Studies, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Watching makes it worse: dairy calves are averse to watching another calf feed while hungry - Jillian Hendricks; Michael T. Mendl; Benjamin Lecorps (Animal Behaviour, 2026)

Stochastic modelling of burden of livestock diseases on domestic ruminants in Ethiopia - Wudu T. Jemberu; Gemma Chaters; Theodore J.D. Knight-Jones; William Gilbert; Stephen Kwok; Mieghan Bruce; Benjamin Huntington; Jonathan Rushton (Preventive Veterinary Medicine, 2026)

Keep your tree above the water: Competition and flooding drive the recent decline of Carya illinoinensis in the Upper Mississippi River - Macarena Férriz; Justin T. Maxwell; Grant L. Harley; Daniel J. King; Karen E. King; Tsun Fung Au; Benjamin J. Vandermyde; Brian Stoff; Beda Luitel (Forest Ecology and Management, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Automated quantification of ecological interactions from video - Mariana Sadde; Benjamin T. Martin (Frontiers in Marine Science, 2026)
Ecological interactions, such as predation, are fundamental events that underlie the flow and distribution of energy through food webs. Yet, directly measuring interaction rates in nature and how they vary across space and time remains a core challenge in ecology. To address this, we developed a machine learning pipeline that combines object detection, tracking, behavioral classification, and bias correction to quantify feeding rates of the planktivorous reef fish Chromis multilineata in situ . We show that the pipeline generates precise, unbiased estimates of planktivory at fine temporal and spatial scales, and use it to reveal how feeding rate changes in response to predator presence and proximity to refuge. While developed and tested in the context of planktivory, we expect this approach can be adapted to quantify a wider array of ecological interactions in situ .

A Review of American Lobster ( Homarus americanus ) Research Since 2000 - Jason S. Goldstein; Benjamin C. Gutzler; Andrew S. Kough; Joshua T. Carloni; Alexa M. Dayton; Carla M. Guenther; Steven H. Jury; Winsor H. Watson (Reviews in Fisheries Science & Aquaculture, 2026)

Two-year real-world retrospective safety evaluation with onabotulinumtoxinA across multiple therapeutic indications: Findings from the SYNCHRONIZE study - Grace Forde; Kimberly Becker Ifantides; Angeli Mayadev; Atul T. Patel; Christopher Rhyne; Theodore Brown; Ritu Singh; Mariana Nelson; Ahunna Ukah; Simona Battucci; Benjamin M. Brucker (Toxicon, 2026)

Restoring the wild east: Predicting public support for cougar and red wolf reintroduction in the eastern United States - Benjamin Ghasemi; Jeremy T. Bruskotter; John A. Vucetich; L. Mark Elbroch; Robyn S. Wilson; Neil H. Carter; Axel Moehrenschlager; Shelby Perry; Joseph W. Hinton (Biological Conservation, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Quantifying the carbon footprint of canine breed-specific surgical care in a veterinary referral setting - Rachel L Nixon; Emma Milne; Iwona N Cameron; Tim Nuttall; Benjamin T Blacklock; Kiterie ME Faller; Gudrun Schoeffmann; Tiziana Liuti; John M Ryan; Kelly L Bowlt Blacklock (The Veterinary Journal, 2025)

Sound velocities of (Al,Fe)-phase H and the seismic visibility of dense oxyhydroxides in Earth’s lower mantle - Benjamin T. Strozewski; Ojashvi Rautela; Johannes Buchen; Wolfgang Sturhahn; Takayuki Ishii; Itaru Ohira; Olivia Pardo; Jiyong Zhao; Thomas S. Toellner; Jennifer M. Jackson (Physics of the Earth and Planetary Interiors, 2025)

Participatory storyworld building for unlocking climate adaptation - Benjamin T. Pederick; Martin Potter; Hailey Cooperrider; Sidney Icarus; Donna Luckman; Rebecca Dahl; Mark Elliot; Trish Cave; Jason Tampake; Brett A. Bryan (Global Environmental Change, 2025)

Multiscale metapopulations - Daniel A. Malagon; Benjamin T. Camper; Sharon Bewick (Theoretical Ecology, 2025)
New advents in technology have improved our ability to study and track host-associated organisms. Often, these organisms experience vastly different spatial and temporal scales than their hosts. However, host-associated organisms are not independent of their hosts nor are hosts independent of their host-associated organisms. Rather, processes at the host and host-associated organism scales interact to alter outcomes for both the host and its symbionts. Often, host-associated organisms are described in terms of metapopulations, wherein individual hosts act as habitat patches for their symbionts. When hosts themselves also exist in patchy environments, the result is metapopulation structure at two distinct scales. In this paper, we develop a model to explore how the incorporation of multiscale metapopulation dynamics impacts metapopulation predictions at both the host and symbiont scales. While related to several disease models, our system differs in its inclusion of full colonization and extinction dynamics at both scales, and its emphasis on how the interaction between colonization and extinction at these two scales impacts the host and its host-associated organisms, including pathogens as well as symbionts that are beneficial to the host. Overall, our multiscale metapopulation model predicts rich dynamics that often deviate from the dynamics of metapopulation models built for either the host or its host-associated organisms independently.

Grief Among Oncology Providers: Prevalence and Association with Burnout - Shannon R. McGue; Cameron J. Oswalt; Benjamin T. Berger; Sarah S. Morgan; Sara A. Barlow; Carl F. Pieper; Linda M. Sutton; Matthew K. Labriola; Anthony N. Galanos (Journal of Cancer Education, 2025)

Impact of neighbor-level disadvantage on survival outcomes in head and neck squamous cell carcinoma - William J. Benjamin; Siddhi Patil; Elham Mohebbi; Sophia Latif; Chamila Perera; Emily Bellile; Kai Wang; Maureen A. Sartor; Jeremy M. G. Taylor; Gregory T. Wolf; Steven B. Chinn; Laura S. Rozek (Cancer Causes & Control, 2025)

Evaluation of single-cell heterogeneity and invasive potential in cancer cells via secreted protease activity assay - Benjamin T. Schelske; Ethan H. Leung; Joseph T. Banovetz; Jared L. Anderson; Robbyn K. Anand (Analytica Chimica Acta, 2025)

Genomic Analysis of Hair Sheep From West/Central Africa Reveals Unique Genetic Diversity and Ancestral Links to Breed Formation in the Caribbean - Pamela Wiener; Juliane Friedrich; Melissa M. Marr; Gustave Simo; Vincent N. Tanya; Keith T. Ballingall; Pavel Flegontov; Benjamin D. Rosen; Guillaume Sallé; Gordon Spangler; Curtis P. Van Tassell; Mazdak Salavati; et al. (Molecular Ecology, 2025)
Cameroon Blackbelly sheep are a domestic breed of hair sheep from West/Central Africa. They are popular with small‐holder farmers in Cameroon as they are highly resilient to local environmental challenges and are prolific a‐seasonal breeders. The aim of this study was to characterise the genetics of Cameroon Blackbelly sheep in relation to global sheep populations and to investigate their relationship to Caribbean hair sheep. We first examined the genetic diversity of the Cameroon Blackbelly breed relative to global sheep populations using 50K SNP data. We also used whole genome sequence data to further investigate relationships between Cameroon Blackbelly and breeds from Africa and Europe, as well as the Barbados Blackbelly breed from the Caribbean, which is phenotypically similar to Cameroon Blackbelly. ADMIXTURE results based on 50K and WGS data demonstrated both West/Central African and European ancestries for the Barbados Blackbelly sheep. Results from f 4 ‐statistics‐based qpAdm analyses supported these findings. Local ancestry inference identified several genomic regions in Barbados Blackbelly with high proportions of West/Central African ancestry. One of these, on OAR3, includes various keratin genes, suggesting that these genes may play a role in the shared coat phenotypes of the Barbados Blackbelly and Cameroon Blackbelly. This result is consistent with previous reports of adaptive introgression of coat characteristics in both wild and domesticated species. The findings of our study support the view that sheep were transported from West/Central Africa to the Caribbean as part of the transatlantic slave trade and European colonisation, similar to introductions proposed for cattle and goats.

Light attenuation due to preferential orientation of particles in waves and shear flow: Idealized modeling for bacteria, algae, and microplastics - Samuel T. Salemink‐Harry; Benjamin J. Smith; Hilary A. Dugan; Jennifer A. Franck; Till J.W. Wagner; Lucas K. Zoet; Grace M. Wilkinson; Nimish Pujara (Limnology and Oceanography, 2025)
Particles are a key component of aquatic light climate due to their attenuation of light. Near the water surface, waves and sheared currents can induce a preferential orientation of nonspherical particles that alters their inherent optical properties and the associated light attenuation. This modeling study focuses on how particle shape, and the corresponding preferential orientation, impacts the light climate in an aquatic environment. We assume aquatic particles, such as bacteria, algae, and microplastic pollutants, are optically homogeneous spheroids that move with the flow. The model computes their preferential orientations within the upper water column in flow driven by linear water waves and sheared currents. This is combined with the anomalous diffraction optical approximation to examine the effect of particle orientation on the beam attenuation coefficient. We find that the preferential orientation by waves and shear tends to increase the projected area of the spheroid compared to random (isotropic) orientation. This has particle size‐dependent effects on light attenuation: for particles comparable in size and shape to algae or microplastics, the preferential orientation corresponds to an increase of 10–25% in the beam attenuation coefficient, whereas there is a decrease of 10–20% in the beam attenuation coefficient for smaller particles comparable in size to bacteria. Overall, our results reveal how preferential orientation of nonspherical particles by waves and currents can impact light climate in the upper water column.

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Corrigendum to “Advanced aspects of acetogens” [Bioresour. Technol. 427 (2025) 131913] - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

The status, challenges, and potential opportunities of fish seed production in Zambia - Oliver J. Hasimuna; Joseph Mphande; Sahya Maulu; Moses Chibesa; Enock Siankwilimba; Inyambo Mumbula; Henry Bwalya; Joyce Mbewe; Benjamin Lundu; Kundananji Nawanzi; Sillah Siavwapa; Mwaanda Sikanyenyene; et al. (Aquaculture International, 2025)

Spawning Habitat Partitioning of Sympatric Salmonid Populations in the Upper Bois Brule River, Wisconsin - Benjamin T. Schleppenbach; Thomas R. Hrabik; Daniel D. McCann; Karen B. Gran; Greg G. Sass (Fishes, 2025)
Spawning habitat partitioning can be important for maintaining sympatric fish species. Likewise, critical spawning habitat loss may challenge the long-term persistence of sympatric fish species. The Bois Brule River, Wisconsin, USA, is a spring-fed, western Lake Superior tributary that supports five naturally reproducing populations of salmonids (native brook trout Salvelinus fontinalis; introduced brown trout Salmo trutta, rainbow trout Oncorhynchus mykiss, coho salmon O. kisutch, and chinook salmon O. tshawytscha). Given increases in recreational angler use and predicted climate-associated changes to trout stream habitat, a better understanding of species interactions during spawning is important to guide future management and conservation of these anthropogenically derived sympatric native and introduced salmonids. Our aim was to establish whether there was partitioning or overlapping in the redd site location preferences among native and introduced salmonids inhabiting the Bois Brule River. We mapped species-specific redd locations by canoe over a 15.3 river km section known to be important for salmonid spawning and evaluated physical, flow, and thermal conditions of these habitats of the Bois Brule River during 2021–2022. We found that spring spawning rainbow trout and fall spawning pacific salmonids and brown trout used the same spawning locations on mid-channel, larger gravel reefs downstream of riffle sections. Native brook trout spawned on smaller substrates with lower streamflow on the edges of the channel, with the highest spawning activity occurring in littoral areas of lentic portions of the river. Our findings provide valuable knowledge of critical spawning habitats for sympatric salmonids that may inform habitat conservation and enhancement efforts in the Bois Brule River and other Great Lakes tributaries with similar sympatric, naturally reproducing salmonids populations.

A new multituberculate (Mammalia, Allotheria) from the Lulworth Formation (Cretaceous, Berriasian) of Dorset, England - Benjamin T. Weston; Steven C. Sweetman; Jake Kean; Charles Wood; David M. Martill; Roy E. Smith (Proceedings of the Geologists' Association, 2025)

Fatty acid and oxidation biomarker concentrations in meat from lambs grazing perennial wheat in binary mixtures with different legumes (clover, serradella, or lucerne) or with a mineral supplement - Benjamin W.B. Holman; Matthew T. Newell; Gordon Refshauge; Kristy L. Bailes; David L. Hopkins; Richard C. Hayes (Meat Science, 2025)

Fracture dynamics and topographic controls at Mount Thorbjörn during the Svartsengi 2023–2024 volcanic unrest, Iceland - Maria Hurley; Nicolas Oestreicher; Alina V. Shevchenko; Gregory P. De Pascale; Magnús T. Gudmundsson; Egill Á. Gudnason; Gylfi P. Hersir; Benjamin F. De Jarnatt; Alea Joachim; Joël Ruch; Fabio L. Bonali; Thomas R. Walter (Journal of Volcanology and Geothermal Research, 2025)

Development and testing of a continuous maritime monitor for radionuclide aerosols - Michael E. Moore; Martin E. Keillor; Daniel Cain; Thomas W. Hallen; Jared C. Johnson; Dustin M. Kasparek; Sarah A. Mendoza; Cory T. Overman; Benjamin Q. Roberts (Journal of Environmental Radioactivity, 2025)

Modeling emissions from pilot testing of wash configurations with aqueous piperazine for CO2 capture - Benjamin J. Drewry; Gary T. Rochelle (International Journal of Greenhouse Gas Control, 2025)

The use of ecoclimatic indices to investigate climate impact on wine grape yield at local scale - Laura T. Massano; Benjamin Bois; Marielle Adrian; Giorgia Fosser; Marco Gaetani (European Journal of Agronomy, 2025)

Development and characterization of an aerosol-generated multi-method analytical particle test material - Lorianne R. Shultz-Johnson; Benjamin T. Manard; Rachel Bergin; Dominic Piedmont; Jordan S. Stanberry; Hunter B. Andrews; Brian W. Ticknor; Mehmet Topsakal; Andrew Kiss; Gage Green; Matthew Wellons; Spencer Scott; et al. (Journal of Aerosol Science, 2025)

Realistic virtual forests for understanding forest disturbances and recovery from space - Kim Calders; Martin Herold; Jennifer Adams; John Armston; Benjamin Brede; Wout Cherlet; Zane T. Cooper; Karun Dayal; Pieter De Frenne; Shaun R. Levick; Patrick Meir; Niall Origo; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Intrinsic Functional Connectivity Associated with γ‑Aminobutyric Acid and Glutamate/Glutamine in the Lateral Prefrontal Cortex and Internalizing Psychopathology in Adolescents - Kai Wang; Harry R. Smolker; Mark S. Brown; Hannah R. Snyder; Yu Cheng; Benjamin L. Hankin; Marie T. Banich (Neuroscience Bulletin, 2025)

Efficacies of cooking and depuration for reducing current-use pesticide residues in wild-caught giant mud crabs (Scylla serrata) - Benjamin C. T. Gray; Curtis Champion; Matt K. Broadhurst; Melinda A. Coleman; Kirsten Benkendorff (Frontiers in Marine Science, 2025)
Introduction Pesticides can be transported into estuaries via spray drift, ground water contamination and surface runoff. Increasing climatic variability and global pesticide use are likely to increase the exposure of harvested estuarine species, and therefore seafood consumers, to agrichemicals. Post-harvest processing strategies present opportunities to reduce pesticide residues in seafood and so mitigate consumer exposure. Materials and methods We evaluated the efficacies of thermal processing (cooking) and depuration (holding individuals in clean flow-through seawater) for reducing pesticide residues in wild-caught giant mud crab ( Scylla serrata ) edible tissues (flesh and brown meat (i.e. hepatopancreas and gonads)). Pesticide residues were detected in 82% of assessed crabs, with five analytes quantified (cyprodinil, diuron, imidacloprid, propargite and triazophos). Results Correlative analyses revealed cooking at ~82°C for 2 min 100-g –1 body mass reduced all pesticide concentrations (and the total residues) in both tissues by 7–99%—except for cyprodinil (51% increase). Imidacloprid residues in crab flesh were reduced (by 81%) after six days of depuration, with complete elimination after 12 days. While a human health-risk assessment identified that the concentrations of pesticide residues in crab tissues posed no negative health effects to seafood consumers, the data support post-harvest processing methods for mitigating consumer exposure. Discussion These findings do not constitute health advice regarding post-harvest possessing methods for reducing contaminants in seafood, but rather highlight the potential utility of the methods assessed for achieving this objective and the broader need for ongoing pesticide surveillance of Australian seafood. Food safety regulation should consider establishing maximum residue limits for seafood, with consideration of consumption preferences.

Improved boron nitride nanomaterial morphologies for the enhanced photocatalytic remediation of perfluorooctanoic acid - Eleanor Castracane; Brian T. Molnar; Addison Lambert; Benjamin G. Harvey; Joseph E. Estevez; Patrick W. Fedick (Chemosphere, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Soil phosphorus transformations along two long-term chronosequences with contrasting climate in south-western Australia - Hongtao Zhong; Jun Zhou; Benjamin L. Turner; Flynn T. Watson; Hans Lambers (Plant and Soil, 2025)
Background Soil organic phosphorus (P) and its chemical nature change markedly during long-term pedogenesis, but how variation in ecosystem water balance and associated differences in vegetation impact such transformations remain unclear. Methods We used solution 31 P-nuclear magnetic resonance ( 31 P-NMR) spectroscopy to assess the chemical nature of soil organic P along two > 2-million-year coastal sand dune chronosequences in south-western Australia characterised by contrasting ecosystem water balance. We sampled soils from the progressive and retrogressive stages of the ecosystem along the wetter Warren and drier Jurien Bay chronosequences. Results Organic P was a much greater proportion of the total soil P in the wetter Warren than the drier Jurien Bay chronosequence. However, the composition of soil organic and inorganic P detected by 31 P-NMR spectroscopy was similar in the two chronosequences. Orthophosphate and simple phosphomonoesters were the dominant P species, and their proportional importance increased as soils aged, constituting > 80% of soil total P in the late stages of pedogenesis. However, no higher-order inositol phosphates were detected along either chronosequence, presumably due to the sandy texture and limited sorption capacity of the soils. Conclusion Our results provide evidence that ecosystem water balance has little impact on the long-term soil organic P transformations during pedogenesis in south-western Australian dune sequences.

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Societal value of seagrass from historical to contemporary perspectives - Nicole R. Foster; Eugenia T. Apostolaki; Katelyn DiBenedetto; Carlos M. Duarte; David Gregory; Karina Inostroza; Dorte Krause-Jensen; Benjamin L. H. Jones; Eduard Serrano; Rym Zakhama-Sraieb; Oscar Serrano (Ambio, 2025)
Seagrasses have been entwined with human culture for millennia, constituting a natural resource that has supported humanity throughout this history. Understanding the societal value of seagrass fosters appreciation of these ecosystems, encouraging conservation and restoration actions to counteract historic and predicted losses. This study overviews the plethora of seagrass use in human history, ranging from spiritual and ceremonial roles, direct and indirect food resources, medicines and raw materials, dating back more than 180 000 years. While many past uses have been abandoned in modern societies, others have persisted or are being rediscovered, and new applications are emerging. As these uses of seagrasses depend on harvesting, we also underscore the need for sustainable practices to (re)generate positive interactions between seagrasses and society. Our review contributes to revalue seagrass societal ecosystem services, highlighting ancient and more recent human and seagrass relationships to incentivize conservation and restoration actions.

Molecular Mechanisms Underlying Response to Influenza in Grey Seals ( Halichoerus grypus ), a Potential Wild Reservoir - Christina M. McCosker; Ebru Unal; Alayna Gigliotti; Wendy B. Puryear; Jonathan A. Runstadler; Kimberly T. Murray; Benjamin L. King; Kristina M. Cammen (Molecular Ecology, 2025)
RNA viruses are infamous for their ability to cross species barriers, posing threats to global health and security. Influenza A virus (IAV) is naturally found in avian hosts but periodically spills over into marine wildlife. IAV outbreaks occur in the Northwest Atlantic, but grey seals ( Halichoerus grypus ) appear to be less susceptible to IAV compared to other species. The subclinical nature of IAV infection in addition to life history factors suggest grey seals are a potential wild reservoir host for IAV. We investigated differential gene expression among grey seals naturally exposed to IAV to elucidate genetic mechanisms involved in grey seal disease resistance. RNA sequencing was conducted on blood samples ( N = 31) collected from grey seal pups in Massachusetts, US between 2014 and 2019. Samples were grouped for analysis based on presence/absence of viral RNA and antibodies. In the presence of IAV RNA, we observed widespread down‐regulation of genes, including immune genes, potentially as a result of IAV‐induced host shutoff. Immune down‐regulation occurred in acute stage of IAV infection (+ viral RNA, − antibodies), followed by up‐regulation of protein production in peak stage (+ viral RNA, + antibodies), possibly as a result of increased viral replication. Evidence of an activated immune response was observed in late stage of infection (− viral RNA, + antibodies) with up‐regulated adaptive immunity genes. We hypothesize that the combination of down‐ and up‐regulated immune gene expression may prevent overstimulation of the immune response, acting as an adaptation in grey seals to resist IAV‐associated mortality.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

A practical framework to evaluate the feasibility of incentive-based approaches to reduce bycatch of marine mammals and other protected species - Manuel Bellanger; Benjamin Dudouet; Sophie Gourguet; Olivier Thébaud; Lisa T. Ballance; Nicolas Becu; Kathryn D. Bisack; Annie Cudennec; Fabienne Daurès; Sigrid Lehuta; Rebecca Lent; C. Tara Marshall; et al. (Marine Policy, 2025)

Advanced aspects of acetogens - Anja Poehlein; Benjamin Zeldes; Maximilian Flaiz; Tim Böer; Alina Lüschen; Franziska Höfele; Kira S. Baur; Bastian Molitor; Christian Kröly; Meng Wang; Quan Zhang; Yixuan Fan; et al. (Bioresource Technology, 2025)

Quorum quenching of phenolic compounds from Leptolyngbya spp. MACC 32 via downregulation of the periplasmic receptor LuxP in Vibrio harveyi: Hinting a putative mechanism - Madiyan Saranya; Byeol Ryu; Jose Seena; Bhaskaran Silpa; Ameer Ahna; C Benjamin Naman; Evgenia Glukhov; T. P. Sajeevan; I. S. Bright Singh; William H. Gerwick; Joseph Valsamma (World Journal of Microbiology and Biotechnology, 2025)

New loci and candidate genes in spring two-rowed barley detected through meta-analysis of a field trial European network - Francesc Montardit-Tarda; Ana M. Casas; William T. B. Thomas; Florian Schnaithmann; Rajiv Sharma; Salar Shaaf; Chiara Campoli; Joanne Russell; Luke Ramsay; Micha M. Bayer; Stefano Delbono; Marko Jääskeläinen; et al. (Theoretical and Applied Genetics, 2025)
Key message A dense genome-wide meta-analysis provides new QTLs, reveals breeding history trends and identifies new candidate genes for yield, plant height, grain weight, and heading time of spring barley. Abstract This study contributes new knowledge on quantitative trait loci (QTLs) and candidate genes for adaptive traits and yield in two-rowed spring barley. A meta-analysis of a network of field trials, varying in latitude and sowing date, with 151 cultivars across several European countries, increased QTL detection power compared to single-trial analyses. The traits analysed were heading date (HD), plant height (PH), thousand-grain weight (TGW), and grain yield (GY). Breaking down the analysis by the main genotype-by-environment trends revealed QTLs and candidate genes specific to conditions like sowing date and latitude. A historical look on the evolution of QTL frequencies revealed that early selection focused on PH and TGW, likely due to their high heritability. GY selection occurred later, facilitated by reduced variance in other traits. The study observed that favourable alleles for plant height were often fixed before those for grain yield and TGW. Some regions showed linkage in repulsion, suggesting targets for future breeding. Several candidate genes were identified, including known genes and new candidates based on orthology with rice. Remarkably, the deficiens allele of gene Vrs1 appears associated with higher GY. These findings provide valuable insights for barley breeders aiming to improve yield and other agronomic traits.

Drivers of Regional Variability in Producer and Consumer Stable Isotope Values (δ13C and δ15N) Within Turtle Grass-Dominated Meadows Across the Northern Gulf of Mexico - Christian Todd Hayes; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Correia; M. Zachary Darnell; Kevin S. Dillon; Bradley T. Furman; Margaret O. Hall; Charles W. Martin; Ashley M. McDonald; Delbert L. Smee; Samantha M. Smith; et al. (Estuaries and Coasts, 2025)

Out of sight and out of mind? The conservation status of subterranean biodiversity in the United States and Canada - Matthew L. Niemiller; Kirk S. Zigler; Amanda N. Curtis; Carter M. Trapeni; Michael E. Slay; David C. Culver; Benjamin T. Hutchins; K. Denise Kendall Niemiller (Biodiversity and Conservation, 2025)

Spatial Replication Is Important for Developing Landscape Genetic Inferences for a Wetland Salamander - Bryce S. Wade; Todd W. Pierson; Benjamin M. Fitzpatrick; Evin T. Carter (Molecular Ecology, 2025)
Habitat fragmentation is a pressing threat to wildlife populations, and maintenance of gene flow between populations is an essential goal of conservation. Resistance surfaces have emerged as an important tool for modelling connectivity and developing management strategies to mitigate effects of habitat fragmentation. However, recent studies have noted inconsistencies in the factors most strongly associated with connectivity across different landscapes. Thus, replication of genetic‐based resistance surface optimisation across landscapes may be necessary for making robust conclusions about the influence of environmental variables. Accordingly, replication represents a substantive challenge and opportunity in the field of landscape genetics. In this study, we conducted replicated landscape genetic analyses across five landscapes in Tennessee and Kentucky for a threatened wetland amphibian, the four‐toed salamander ( Hemidactylium scutatum ). We tested multiple hypotheses of how different landscape features that could directly affect small, desiccation‐intolerant amphibians (e.g., canopy cover) influenced gene flow and assessed the appropriate scale at which to model different features. We found some concordance in the landscape features that influenced gene flow (e.g., a common importance of forest cover and topography), but also some differences—potentially owing to the difference in variability of predictors across landscapes. We also found discordance in the scale of effect of different features across landscapes. Our work emphasises that flat areas of moist forest not bisected by roads may be important for H. scutatum conservation, and our replicated design allows us to identify relationships that would have been missed if only using one study site.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

Explicit value trade-offs in conservation: integrating animal welfare - Kate E. Lynch; Benjamin L. Allen; Oded Berger-Tal; Fiona Fidler; Georgia E. Garrard; Jordan O. Hampton; Christopher H. Lean; Kirsten M. Parris; Sally L. Sherwen; Thomas E. White; Bob B.M. Wong; Daniel T. Blumstein (Trends in Ecology & Evolution, 2025)

The influence of artificial reef structural complexity on fish assemblage composition - Brooke T. Marshall; Sam R. Russell; James H. Florisson; Benjamin J. Saunders; Stephen J. Newman; Euan S. Harvey (Marine Environmental Research, 2025)

Exploring Neoproterozoic climate and biogeochemical evolution in the SCION model - Benjamin J.W. Mills; Guillaume le Hir; Andrew Merdith; Khushboo Gurung; Fred T. Bowyer; Alexander J. Krause; Patricia Sanchez-Baracaldo; Stephen J. Hunter; Yinggang Zhang (Global and Planetary Change, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

Influence of four hook types across four hook removal tools, including bare hands, on the effectiveness of hook removal and reflex impairment of Bluegill ( Lepomis macrochirus ) captured from a lake in Eastern Ontario - Jeremy Hussey; Luc LaRochelle; Andy J. Danylchuk; Sascha Clark Danylchuk; Benjamin W. C. Cooke; Joshua T. H. Cooke; Cameron J. A. Cooke; Steven J. Cooke (Fisheries Management and Ecology, 2025)
Hook removal devices have been developed to enable rapid release of angled fish, yet little research has evaluated their effectiveness and potential for injury among hook types. We compared the performance of hook removal tools and bare hands with four hook types on freshwater Lepomid sunfish. Dehooking performance was assessed using hook removal time, unhooking difficulty, degree of tissue damage at the hooking location, and immediate reflex impairment. Unhooking difficulty was positively related to hooking depth. Unhooking difficulty was lowest for hemostats and the mechanical dehooking device; however, the mechanical dehooking device caused the largest tearing of mouth tissue. Unhooking difficulty was the main driver for hook removal time, tissue tear length, and overall reflex impairment. Hooks that were harder to remove caused higher reflex impairment. Hook type had little influence on the effectiveness of hook removal tools, although circle hooks were more difficult to remove and caused greater injury when using tools. Although use of hook removal tools can be beneficial for fish that are released, more research is needed on more species targeted by recreational anglers, and more hook removal tools. We suggest that hemostats should be used to remove hooks from fish to reduce unhooking difficulty, tissue tears, long air exposure, and thereby to increase the welfare of the fish.

Assessing fish assemblages on oil jackets off the Angolan coast: Implications for decommissioning decisions - Karl D. Schramm; Brooke T. Marshall; Peter Oliver; Travis S. Elsdon; Michael J. Marnane; Benjamin J. Saunders; Anthony B. Rouphael; Euan S. Harvey (Marine Environmental Research, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Unveiling surface-subsurface flow interactions of a salmon redd - Brandon Hilliard; William J. Reeder; Ralph Budwig; Vibhav Durgesh; Bishal Bhattarai; Benjamin T. Martin; Tao Xing; Daniele Tonina (Advances in Water Resources, 2025)

Monitoring post‐spawning movement, habitat use, and survival of adult anadromous rainbow smelt using acoustic telemetry in a New Hampshire estuary - Chloe F. Pearson; Lars J. Hammer; Alyson L. Eberhardt; Linas W. Kenter; David L. Berlinsky; Wellsley J. Costello; Nathan T. Hermann; Aliya Caldwell; Emily A. Burke; Benjamin D. Walther; Nathan B. Furey (Journal of Fish Biology, 2025)
Anadromous rainbow smelt ( Osmerus mordax , [Mitchill 1814]) are found along the northeast Atlantic coastline of North America, with their range now limited to north of Cape Cod, Massachusetts, USA. Although their anadromous life cycles are described broadly, gaps remain regarding how adult rainbow smelt use estuaries post‐spawning, including movement behaviors, habitats used, and specific timing of emigration to coastal waters. In spring 2021, we used acoustic telemetry to characterize movements during and after the spawning season of rainbow smelt captured in tributaries to Great Bay, New Hampshire, USA, a large estuarine system near the southern edge of their range. Forty‐four adult rainbow smelt ( n = 35 male, n = 9 female) were tagged with Innovasea V5 180‐kHz transmitters and an array of 22,180 kHz VR2W receivers were deployed throughout Great Bay to detect movements of tagged fish from March to October 2021. Rainbow smelt were detected 14,186 times on acoustic telemetry receivers, with 41 (93%) of the tagged individuals being detected at least once post‐tagging. Individuals were detected moving between tributaries, revealing that rainbow smelt can use multiple rivers during the spawning season (March–April). Mark‐recapture Cormack‐Jolly‐Seber models estimated 83% (95% confidence interval 66%–92%) of rainbow smelt survived to the mainstem Piscataqua River, and a minimum of 50% (22 of 44) reached the seaward‐most receivers and were presumed to have survived emigration. Most individuals that survived remained in the estuary for multiple weeks (average = 19.47 ± 1.99 standard error days), displaying extended use of estuarine environments. Downstream movements occurred more frequently during ebb tides and upstream movements with flood tides, possibly a mechanism to reduce energy expenditures. Fish emigrated from the estuary by mid‐May to the coastal Gulf of Maine. Our results underscore that rainbow smelt need access to a variety of habitats, including multiple tributaries and high‐quality estuarine habitat, to complete their life cycle.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Recent Abundance Changes at Species' Range Limits in the North and Central American Avifaunas - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Global Ecology and Biogeography, 2025)
Aim Species are often expected to track climate change via changes in their abundances and distributions. This climate tracking hypothesis generates the prediction that warming temperatures should cause species to show population increases at their poleward range limits and population decreases at their equatorward range limits. We tested these predictions for 516 species of North and Central American birds. Location North and Central America. Time Period 2012–2022. Major Taxa Studied Birds. Methods We used data on bird species' recent abundance changes within their breeding or year‐round distributions from eBird Status and Trends models, and temperature data from a global temperature dataset. We defined species' northern and southern range limits, then used regression models to test whether recent abundance changes at species' range limits were predicted by temperature change and a set of ecological traits. Results Abundance changes at species' range edges are not associated with temperature change. There is a latitudinal gradient in recent abundance changes: lower‐latitude species have increased in abundance at both northern and southern range limits, whereas higher‐latitude species have declined in abundance at both range limits. Conclusions Patterns of abundance change at species' northern and southern range limits are not consistent with the climate tracking hypothesis for North and Central American birds. This result casts doubt on the accuracy of long‐term biological forecasts that assume tight temperature tracking for these avifaunas. Our finding of a latitudinal gradient in recent abundance change suggests lower‐latitude species may generally be benefiting from climate change, with consequences for local and regional communities across latitudinal gradients.

Plant Responses to Anomalous Heat and Drought Events in the Sonoran Desert - Benjamin T. Wilder; Kevin R. Hultine; Wetherbee Bryan Dorshow; Sula E. Vanderplank; Blanca R. López; Alfonso Medel‐Narváez; Monica Marvan; Kristen Kindl; Aryn Musgrave; Shane Macfarlan; Exequiel Ezcurra (Global Change Biology, 2025)
A shift to greater aridification in dry regions of the world is ongoing and rapidly increasing in intensity, including in the biodiverse Sonoran Desert of the Southwest United States and northern Mexico. In addition to experiencing over two decades of drought, the Sonoran Desert is facing anomalous heat events that are increasing in frequency, evidenced in a record hot and dry period from 2020 to 2021. This article evaluates the impacts of the 2020–2021 region‐wide heat and drought event at three scales: (1) a landscape level assessment of ecosystem stress across the entirety of the Sonoran Desert based on precipitation and temperature data from meteorological stations and a satellite‐derived vegetation health index (VHI), (2) assessments of stress on iconic columnar cacti and succulent trees, and (3) mechanistic plant responses to extreme heat and drought, and secondary biotic stressors from insect attacks. 2020 was the hottest and driest year since 1980 across the Sonoran Desert region, and vegetation health, determined from VHI, was also near its lowest point. Field‐based assessments of columnar cacti across the Sonoran Desert revealed high levels of acute plant stress, including cactus scorching, defined by rapid onset of discolored photosynthetic tissue that leads to permanent photosynthetic dysfunction and increased plant mortality. Tissue scorching corresponded with a three‐fold increase in mortality of giant cactus species across the region relative to background levels following 2020–2021. Likewise, repeated plant health surveys show a persistent legacy of the 2020–2021 anomaly, resulting in a marked reduction in the current health and survival of the iconic giant saguaro ( Carnegiea gigantea ) in the northern Sonoran Desert. This multi‐scale assessment of previously anomalous heat and drought events on succulent desert plants shows landscape‐wide impacts that could fundamentally reshape populations of these keystone species and the communities that depend on them.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dynamics of hydrogen–ammonia–natural gas lean-premixed high-pressure flames - Tristan T. Shahin; Alexander J. Hodge; Benjamin K. Murdock; Thomas N. McLean; Keaton C. Koenig; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2025)

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Rampant Dispersal Without Gene‐Flow: Reproductively and Geographically Isolated Lineages of the Supertramp Lizard Lamprolepis smaragdina Permeate the Lesser Sunda Archipelago - Sean B. Reilly; Hinrich Kaiser; Benjamin R. Karin; Umilaela Arifin; Alexander L. Stubbs; Evy Arida; Amir Hamidy; Djoko T. Iskandar; Jimmy A. McGuire (Journal of Biogeography, 2025)
Aim We investigated the biogeographical patterns of a widespread arboreal lizard found throughout Wallacea and the western Pacific islands. Wallacea contains longstanding oceanic currents that flow from the Pacific Ocean into the Indian Ocean, known as the Indonesian Throughflow. Using genetic data, we aim to estimate the timing and sequence of island colonisation in the Lesser Sunda archipelago of southern Wallacea, and to determine the proportion of dispersal events that may have been aided by ocean currents. Levels of gene flow are also explored in the context of island arrangement, past connectivity (ex. Pleistocene land bridges), and ocean currents. Location Southern Wallacea (Indonesia, Timor‐Leste). Taxon Emerald Tree Skink ( Lamprolepis smaragdina ). Methods We estimated a mitochondrial DNA phylogeny from southern Wallacean populations to identify divergent populations and to guide sample selection for genomic‐scale data collection. These genomic data were used to estimate (1) phylogenetic relationships of island populations using both concatenated Maximum Likelihood, summary coalescent and multispecies coalescent methods, (2) levels of genetic connectivity between lineages using genetic clustering and migration analyses, and (3) to reconstruct their dispersal history using ancestral range reconstruction analysis. Results We found that the Emerald Tree Skinks of southern Wallacea diverged from a population on Peleng Island ~1.25 Ma and that Lesser Sunda populations diverged between ~1 and 0.4 Ma. MtDNA data are insufficient to estimate the relationships of each population and find one island to be paraphyletic and two to be polyphyletic. Genomic data find that Timor Island is polyphyletic while all other islands are recovered as monophyletic. Gene flow is minimal or absent across the archipelago, even between islands that become periodically land bridged. More than half of the estimated over‐water dispersal events occurred perpendicular to or against ocean currents. Main Conclusions Despite this species' over‐water dispersal abilities island populations are genetically isolated from one another, even on adjacent islands that become periodically land bridged. This suggests that species formation is complete. The inferred dispersal history involved many paths that would be difficult to complete given the direction of ocean currents, indicating that historical ocean currents are more dynamic than currently understood.

Biomarker signatures in host rocks and their co-occurring fossil plants from northern Scotland - Olumuyiwa T. Akinsanpe; Adebola O. Akinsanpe; Solomon A. Adekola; Oluwaseye P. Oyetade; Waheed G. Akande; Musa B. Usman; Abdulwahab M. Bello; Uzochukwu K. Benjamin; Adeniyi O. Olusanya; Chikezie Emele (Organic Geochemistry, 2025)

Modeling gas, hydrates, and slope stability on the U.S. Atlantic margin during Pleistocene glacial cycles - Olin R. Carty; Warren T. Wood; Benjamin J. Phrampus; Taylor R. Lee; Jennifer M. Frederick; Michael Nole; David Fukuyama; Hugh Daigle (Marine Geology, 2025)

Nutrient limitation and seasonality associated with phytoplankton communities and cyanotoxin production in a large, hypereutrophic lake - Gabriella M. Lawson; Jakob L. Young; Zachary T. Aanderud; Erin F. Jones; Samuel Bratsman; Jonathan Daniels; Madeleine P. Malmfeldt; Michelle A. Baker; Benjamin W. Abbott; Scott Daly; Hans W. Paerl; Greg Carling; et al. (Harmful Algae, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

PROCEED v6.1: Phenotypic rates of change evolutionary and ecological database - Lucas D. Gorné; Andrew P. Hendry; Fanie Pelletier; Sarah Sanderson; Cristian Correa; Carlos Arias; Marc‐Olivier Beausoleil; Maryse Boisjoly; Erika Crispo; Daniel Berner; Luis F. De León; Joseph D. DiBattista; et al. (Ecology, 2025)
Populations must continuously respond to environmental change or risk extinction. These responses can be measured as phenotypic rates of change, which allow researchers to predict their contemporary evolutionary responses. In 1999, a database of phenotypic rates of change in wild populations was compiled. Since then, researchers have used (and expanded) this database to examine the phenotypic responses as a function of the features of the study system (i.e., the population or set of populations, of a given species, that experienced a specific driver or disturbance), the measured traits, and methodological approaches. Therefore, PROCEED (Phenotypic Rates of Change Evolutionary and Ecological Database) is an ongoing compilation of rates of phenotypic change, typically calculated as Haldanes and Darwins, published in peer‐reviewed literature (but also including data from theses and technical reports). Studies in this database measure the intraspecific change in quantitative (continuous or discrete) traits and report either the time elapsed from the onset of environmental novelty, or reference a historical or biological event reported in other sources (e.g., a mine opening or a well‐documented biological invasion). Included studies either follow a single population through time (allochronic design) or compare two or more populations that diverged at a known time (synchronic design). Some included studies account for the total phenotypic variability in the field (i.e., phenotypic studies), while others employed common‐garden or other quantitative genetic approaches to account for the heritable component of the phenotypic change (i.e., genetic studies). PROCEED includes systems in both natural and experimental conditions, provided that reproduction was not manipulated (i.e., artificial selection experiments were excluded). In the included experimental systems, the environment of the focal populations was manipulated (e.g., an herbivory exclusion experiment, where the type and load of herbivory are manipulated) but the studies did not deliberately select for trait values in the study population (e.g., the plant height). PROCEED does not include systems where the phenotypic change is presumably due to interspecific hybridization, polyploidy, or other chromosomal alterations. Here, we present the most recently updated PROCEED (Version 6.1). This new, curated version has 9263 records ( n ) collated from 326 studies, 1801 systems, and 428 species. The database includes records belonging to mammals ( n = 686), birds ( n = 1475), reptiles ( n = 96), amphibians ( n = 23), fishes ( n = 3671), invertebrates ( n = 1141, mostly arthropods), and plants ( n = 2171). The maximum elapsed time between the environmental change and the sampling is 500 years but is typically less than 100 years (third quartile 89.5; median 45 years). The database also includes a set of variables describing biological and methodological aspects of the study system and measured traits, along with features of the sampling design in the primary source of information. This new version of PROCEED also includes a time series dataset comprising a subset of records included in the general dataset. These are allochronic studies with three or more sampling times throughout the entire study period. The time series dataset contains 655 time series ( s )—belonging to 61 studies, from 156 systems, and 77 species—including mammals ( s = 140), birds ( s = 77), reptiles ( s = 4), amphibians ( s = 8), fishes ( s = 404), and plants ( s = 22). The data are released under a Creative Commons CC0 1.0 Universal Public Domain Dedication license.

Baseline matters: Challenges and implications of different marine heatwave baselines - Kathryn E. Smith; Alex Sen Gupta; Dillon Amaya; Jessica A. Benthuysen; Michael T. Burrows; Antonietta Capotondi; Karen Filbee-Dexter; Thomas L. Frölicher; Alistair J. Hobday; Neil J. Holbrook; Neil Malan; Pippa J. Moore; et al. (Progress in Oceanography, 2025)

A Metapopulation Model to Assess Water Management Impacts on the Threatened Australian Lungfish, Neoceratodus forsteri - Charles R. Todd; Andrew J. McDougall; Scott M. C. Raymond; Robin Hale; Timothy R. Brown; John D. Koehn; Henry F. Wootton; Steven G. Brooks; Adrian M. Kitchingman; Tom Espinoza; Benjamin G. Fanson; Peter K. Kind; et al. (Fishes, 2025)
The Australian lungfish, Neoceratodus forsteri, is one of the world’s oldest vertebrate lineages, with a slow life-history and threatened status, requiring immediate conservation efforts. The main threats to lungfish populations are degradation and availability of key macrophyte habitats, water regulation and flow modification. As this long-lived species (at least 77 years) has delayed maturity (mature at 10 years), field monitoring alone will not be enough to inform the challenge of ensuring sustainable populations. A stochastic metapopulation model was developed for the Burnett River (Southeast Queensland, Australia), an important habitat for the lungfish that is a highly regulated system with extensive water infrastructure. The model consists of three interacting populations, where the ecology and biology of the species were translated into an 80-year-class population projection matrix for each population, each with post-development streamflow, habitat and movement rules. The model highlights the longer-term interaction between dams and stream flows on habitat availability and subsequent recruitment. Through a pre-development streamflow, we quantify the impact of high regulation and development on the lungfish population in the Burnett River: a minor decline in the upstream population (e.g., 9.8% decline), a large decline in the middle population (64.2% decline), virtually no change in the downstream population (e.g., 1.2% decline) and a moderate decline in the overall metapopulation (e.g., 22.3% decline). The loss of spawning and feeding habitat remains the main reason for population decline, with implications that the loss will lead to greater pressure on remaining downstream habitat due to combined flow and dam effects and, in turn, to extended periods of recovery of spawning habitat. Our modeling approach substantially advances conservation management of this species, as it can be adapted to suit other populations in other river systems and used to test sensitivity to recovery actions.

Corrigendum to “Limited cougar recolonization of eastern North America predicted by an individual-based model” [Biol. Conserv. volume 298 (2024)/110756] - Thomas W. Glass; Richard A. Beausoleil; L. Mark Elbroch; Brian N. Kertson; Benjamin T. Maletzke; Quinton Martins; Marc R. Matchett; T. Winston Vickers; Christopher C. Wilmers; Heiko U. Wittmer; Hugh Robinson (Biological Conservation, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Enhanced cation release via acid pretreatment for gigaton-scale geologic CO2 sequestration in basalt - Qin Zhang; Adedapo N. Awolayo; Patrick R. Phelps; Shafik Vadsariya; Christiaan T. Laureijs; Matthew D. Eisaman; Benjamin M. Tutolo (International Journal of Greenhouse Gas Control, 2024)

Ohmic pasteurization of probiotic chocolate dairy desserts and its quality attributes - Gabriela R.A. Silva; Wanessa P. da Silva; Elson R. Tavares Filho; Louise de A. Sobral; Carolina P.C. Martins; Benjamin Mahieu; Jonas T. Guimarães; Maria Carmela K.H. Duarte; Mônica M. Pagani; Ramon Silva; Monica Q. Freitas; Eliane T. Mársico; et al. (Food Research International, 2024)

Temporary atmospheres produced by human activities on the Moon - Rosemary M. Killen; Benjamin T. Sprague; William M. Farrell (Advances in Space Research, 2024)

Stable isotopes reveal trophic ontogeny in Cisco ( Coregonus artedi ) - Benjamin E. Martin; Joseph T. Mrnak (Journal of Fish Biology, 2024)
Cisco ( Coregonus artedi ) are a widespread, cold‐water zooplanktivore native to North America. Although Cisco are generally referred to as an “obligate zooplanktivore,” there is some evidence that the species exhibits considerable variability in trophic niche. Here, we assessed how Cisco body size relates to trophic position, that is, trophic ontogeny. We analysed 13 C and 15 N isotopes from Cisco ranging from 127 to 271 mm in body length ( n = 66) from Trout Lake, Vilas County, Wisconsin, USA. 15 N isotopes showed smaller Cisco had a trophic position of ~3, which steadily increased to ~3.5 for larger Cisco. Further, 13 C isotope signatures showed Cisco transitioned to be more pelagically reliant (lower 13 C signatures). Using gillnet catch data, we found that larger Cisco were using deeper habitats than smaller Cisco. Our results support that Cisco have significant variability in trophic niche even though they are traditionally thought of as an obligate planktivore. Overall, we emphasize that researchers should be cautious when generalizing Cisco trophic function, particularly when considering the broader food web.

Leaf architecture and functional traits for 122 species at the University of California Botanical Garden at Berkeley - Ilaine Silveira Matos; Mickey Boakye; Monica Antonio; Sonoma Carlos; Ashley Chu; Miguel A. Duarte; Andrea Echevarria; Adrian Fontao; Lisa Garcia; LeeAnn Huang; Breanna Carrillo Johnson; Shama Joshi; et al. (Ecology, 2024)
The dataset contains leaf venation architecture and functional traits for a phylogenetically diverse set of 122 plant species (including ferns, basal angiosperms, monocots, basal eudicots, asterids, and rosids) collected from the living collections of the University of California Botanical Garden at Berkeley (37.87° N, 122.23° W; CA, USA) from February to September 2021. The sampled species originated from all continents, except Antarctica, and are distributed in different growth forms (aquatic, herb, climbing, tree, shrub). The functional dataset comprises 31 traits (mechanical, hydraulic, anatomical, physiological, economical, and chemical) and describes six main leaf functional axes (hydraulic conductance, resistance and resilience to damages caused by drought and herbivory, mechanical support, and construction cost). It also describes how architecture features vary across venation networks. Our trait dataset is suitable for (1) functional and architectural characterization of plant species; (2) identification of venation architecture‐function trade‐offs; (3) investigation of evolutionary trends in leaf venation networks; and (4) mechanistic modeling of leaf function. Data are made available under the Open Data Commons Attribution License.

Assessing the impact of preventative measures to limit the spread of Toxoplasma gondii in wild carnivores of Madagascar - Fidisoa T. Rasambainarivo; Santatra Randrianarisoa; Olivier A. Rasolofoniaina; Benjamin L. Rice; C. Jessica E. Metcalf (Conservation Biology, 2024)
Novel multihost pathogens can threaten endangered wildlife species, as well as humans and domestic animals. The zoonotic protozoan parasite Toxoplasma gondii is transmitted by members of Felidae and can infect a large number of animal species, including humans. This parasite can have significant health consequences for infected intermediate hosts and could further endanger wild carnivore populations of Madagascar. Building on an empirical characterization of the prevalence of the pathogen in local mammals, we used mathematical models of pathogen transmission in a multihost community to compare preventative measures that aim to limit the spread of this parasite in wild carnivores. Specifically, we examined the effect of hypothetical cat vaccination and population control campaigns on reducing the risk of infection by T. gondii in wild Eupleridae. Our model predicted that the prevalence of exposure to T. gondii in cats would be around 72% and that seroprevalence would reach 2% and 43% in rodents and wild carnivores, respectively. Reducing the rodent population in the landscape by half may only decrease the prevalence of T. gondii in carnivores by 10%. Similarly, cat vaccination and reducing the population of definitive hosts had limited impact on the prevalence of T. gondii in wild carnivorans of Madagascar. A significant reduction in prevalence would require extremely high vaccination, low turnover, or both in the cat population. Other potential control methods of T. gondii in endangered Eupleridae include targeted vaccination of wild animals but would require further investigation. Eliminating the threat entirely will be difficult because of the ubiquity of cats and the persistence of the parasite in the environment.

Fabrication and anti-fouling performance assessment of micro-textured CNT-PDMS nanocomposites through the scalable roll-coating process - Pouria Zaghari; Onur Özcan; Md Didarul Islam; Benjamin Black; Sipan Liu; S. M. Naser Shovon; Henry Oliver T. Ware; Axel Rosenhahn; Jong Eun Ryu (Biofouling, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Long distance swimmers in warming waters: Active transport in postlarval American lobsters (Homarus americanus) in the context of climate change in the Gulf of Maine - Jason S. Goldstein; Benjamin C. Gutzler; Abigail Lemmon; Joshua T. Carloni; Marlies Betka; Steven H. Jury (Fisheries Research, 2024)

Behavioral thermoregulation of ovigerous American lobsters (Homarus americanus) - Steven H. Jury; Benjamin C. Gutzler; Jason S. Goldstein; Joshua T. Carloni; Winsor H. Watson (Fisheries Research, 2024)

The carcass characteristics and quality of meat from lambs grazing perennial wheat with different companion legumes (clover, serradella, lucerne) or a mineral supplement - Benjamin W.B. Holman; Gordon Refshauge; Matthew T. Newell; David L. Hopkins; Richard C. Hayes (Meat Science, 2024)

Limited cougar recolonization of eastern North America predicted by an individual-based model - Thomas W. Glass; Richard A. Beausoleil; L. Mark Elbroch; Brian N. Kertson; Benjamin T. Maletzke; Quinton Martins; Marc R. Matchett; T. Winston Vickers; Christopher C. Wilmers; Heiko U. Wittmer; Hugh Robinson (Biological Conservation, 2024)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Integrating importance- performance analysis into transboundary natural resource management of water trails: Case study at the Chattahoochee river national recreation area water trail in Atlanta, GA (USA) - Benjamin T. Fowler; Gary T. Green; B. Bynum Boley (Journal of Outdoor Recreation and Tourism, 2024)

Polyethylene glycol and caspase inhibitor emricasan alleviate cold injury in primary rat hepatocytes - Huyun Chen; Bradley W. Ellis; Antonia T. Dinicu; Mohammadreza Mojoudi; Benjamin T. Wilks; Shannon N. Tessier; Mehmet Toner; Korkut Uygun; Basak E. Uygun (Cryobiology, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Morphological variation of the kelp Ecklonia radiata in northeastern New Zealand and across its Australasian range - Benjamin Hanns; Caitlin Blain; Nick T. Shears (Marine Biology, 2024)
Understanding the drivers of morphological plasticity, a key mechanism allowing species to flourish under a range of conditions, can provide important information on how a species will adapt to climate-change. The kelp Ecklonia radiata is the dominant canopy-forming macroalgae in temperate Australasia, occurring across a wide environmental range. Previous assessments of morphological variation across Australasia have not included northeastern New Zealand (NENZ) populations, where E. radiata exhibits an anomalous long-stipe morphology. Morphology in NENZ E. radiata over nine locations was quantified to examine variability and its relationship with environmental drivers: depth, wave exposure, turbidity and temperature. Published literature was then reviewed to assess variation across Australasia in relation to similar large-scale environmental drivers. In NENZ, morphology was driven by depth, wave exposure, and turbidity, but not temperature. Thalli had short stipes and relatively long lamina at shallow depths (< 2 m) and across depths at highly wave exposed sites. Stipe length increased with depth and the long stipe morphology dominated deeper depths (4–12 m) at sheltered to moderately exposed sites. However, this relationship varied in relation to turbidity, with more turbid sites having shorter stipes across all depths. Regional variation in morphology across Australasia was most strongly related to wave climate rather than temperature with the long-stipe morphology characterising regions with low energy wave climates such as NENZ. This study highlights the high levels of variability in E. radiata morphology and its complex relationship with environmental stress. If Australasia’s wave climate is to increase in severity, our findings suggest morphological variability expressed across Australasian E. radiata populations will shrink.

Asymmetric effects of hydroclimate extremes on eastern US tree growth: Implications on current demographic shifts and climate variability - Justin T. Maxwell; Tsun Fung Au; Steven A. Kannenberg; Grant L. Harley; Matthew P. Dannenberg; Darren L. Ficklin; Scott M. Robeson; Macarena Férriz; Michael C. Benson; Benjamin R. Lockwood; Kimberly A. Novick; Richard P. Phillips; et al. (Global Change Biology, 2024)
Forests around the world are experiencing changes due to climate variability and human land use. How these changes interact and influence the vulnerability of forests are not well understood. In the eastern United States, well‐documented anthropogenic disturbances and land‐use decisions, such as logging and fire suppression, have influenced forest species assemblages, leading to a demographic shift from forests dominated by xeric species to those dominated by mesic species. Contemporarily, the climate has changed and is expected to continue to warm and produce higher evaporative demand, imposing stronger drought stress on forest communities. Here, we use an extensive network of tree‐ring records from common hardwood species across ~100 sites and ~1300 trees in the eastern United States to examine the magnitude of growth response to both wet and dry climate extremes. We find that growth reductions during drought exceed the positive growth response to pluvials. Mesic species such as Liriodendron tulipifera and Acer saccharum , which are becoming more dominant, are more sensitive to drought than more xeric species, such as oaks ( Quercus ) and hickory ( Carya ), especially at moderate and extreme drought intensities. Although more extreme droughts produce a larger annual growth reduction, mild droughts resulted in the largest cumulative growth decreases due to their higher frequency. When using global climate model projections, all scenarios show drought frequency increasing substantially (3–9 times more likely) by 2100. Thus, the ongoing demographic shift toward more mesic species in the eastern United States combined with drier conditions results in larger drought‐induced growth declines, suggesting that drought will have an even larger impact on aboveground carbon uptake in the future in the eastern United States.

Interspecific competition shapes bird species' distributions along tropical precipitation gradients - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Ecology Letters, 2024)
The hypothesis that species' ranges are limited by interspecific competition has motivated decades of debate, but a general answer remains elusive. Here we test this hypothesis for lowland tropical birds by examining species' precipitation niche breadths. We focus on precipitation because it—not temperature—is the dominant climate variable that shapes the biota of the lowland tropics. We used 3.6 million fine‐scale citizen science records from eBird to measure species' precipitation niche breadths in 19 different regions across the globe. Consistent with the predictions of the interspecific competition hypothesis, multiple lines of evidence show that species have narrower precipitation niches in regions with more species. This means species inhabit more specialized precipitation niches in species‐rich regions. We predict this niche specialization should make tropical species in high diversity regions disproportionately vulnerable to changes in precipitation regimes; preliminary empirical evidence is consistent with this prediction.

Application of the integrated threat theory to conservation law enforcement - Mahmood Soofi; Benjamin Ghasemi; Mohsen Ahmadpour; Mobin Soufi; Iman Islami; Alaina Eckert; Mohammad Hossein Gorjian Arabi; Ali T. Qashqaei; Javad Selyari; Kamran Nasirahmadi; Johannes Kamp; Matthias Waltert; et al. (Conservation Biology, 2024)
Interactions between law enforcement agents in conservation (e.g., rangers) and illegal resource users (e.g., illegal hunters) can be violent and sometimes fatal, which negatively affects conservation efforts and people's well‐being. Models from social psychology, such as integrated threat theory (ITT) (intergroup interactions shape intergroup emotions, prejudices and perceived threats leading to hostile attitudes or behaviors between groups), are useful in addressing such interactions. Conservation approaches relying mainly on law enforcement have never been investigated using this framework. Using a structured questionnaire, we collected data from 282 rangers in protected and unprotected areas ( n = 50) in northern Iran. We applied Bayesian structural equation modeling in an assessment of rangers’ affective attitudes (i.e., emotions or feelings that shape attitudes toward a person or object) toward illegal hunters in an ITT framework. Rangers’ positive perceptions of illegal hunters were negatively associated with intergroup anxiety (emotional response to fear) and negative stereotypes about a hunter's personality, which mediated the relationship between negative contact and affective attitudes. This suggests that negative contact, such as verbal abuse, may lead rangers to perceive illegal hunters as arrogant or cruel, which likely forms a basis for perceived threats. Rangers’ positive contact with illegal hunters, such as playing or working together, likely lowered their perceived realistic threats (i.e., fear of property damage). Perceived realistic threats of rangers were positively associated with negative contacts (e.g., physical harm). The associations we identified suggest that relationships based on positive interactions between rangers and illegal hunters can reduce fear and prejudice. Thus, we suggest that rangers and hunters be provided with safe spaces to have positive interactions, which may help lower tension and develop cooperative conservation mechanisms.

Petrogenesis and geodynamic setting of the Bingo alkaline-carbonatite complex, DRC: Constraints from petrography, geochemistry, C-O isotopes and U-Pb geochronology - Georges M. Kasay; Anouk M. Borst; Johannes R. Giebel; Anthony T. Bolarinwa; Aratz Beranoaguirre; Tobias Kluge; Olawale K. Aromolaran; Mohsin Raza; Elisabeth Eiche; Jochen Kolb; Charles Nzolang; Benjamin F. Walter (Precambrian Research, 2024)

Population density and zooplankton biomass influence anadromous juvenile river herring growth in freshwater lakes - Matthew T. Devine; Steven Bittner; Allison H. Roy; Benjamin I. Gahagan; Michael P. Armstrong; Adrian Jordaan (Environmental Biology of Fishes, 2024)

A framework for physically consistent storylines of UK future mean sea level rise - Matthew D. Palmer; Benjamin J. Harrison; Jonathan M. Gregory; Helene T. Hewitt; Jason A. Lowe; Jennifer H. Weeks (Climatic Change, 2024)
We present a framework for developing storylines of UK sea level rise to aid risk communication and coastal adaptation planning. Our approach builds on the UK national climate projections (UKCP18) and maintains the same physically consistent methods that preserve component correlations and traceability between global mean sea level (GMSL) and local relative sea level (RSL). Five example storylines are presented that represent singular trajectories of future sea level rise drawn from the underlying large Monte Carlo simulations. The first three storylines span the total range of the Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report (AR6) likely range GMSL projections across the SSP1-2.6 and SSP5-8.5 scenarios. The final two storylines are based upon recent high-end storylines of GMSL presented in AR6 and the recent literature. Our results suggest that even the most optimistic sea level rise outcomes for the UK will require adaptation of up to 1 m of sea level rise for large sections of coastline by 2300. For the storyline most consistent with current international greenhouse gas emissions pledges and a moderate sea level rise response, UK capital cities will experience between about 1 and 2 m of sea level rise by 2300, with continued rise beyond 2300. The storyline based on the upper end of the AR6 likely range sea level projections yields much larger values for UK capital cities that range between about 3 and 4 m at 2300. The two high-end scenarios, which are based on a recent study that showed accelerated sea level rise associated with ice sheet instability feedbacks, lead to sea level rise for UK capital cities at 2300 that range between about 8 m and 17 m. These magnitudes of rise would pose enormous challenges for UK coastal communities and are likely to be beyond the limits of adaptation at some locations.

Detection of Coxiella burnetii in the mammary gland of a dairy goat - Benjamin Ulrich Bauer; Martin Peters; T. Louise Herms; Martin Runge; Peter Wohlsein; Tim K. Jensen; Martin Ganter (Veterinary Research Communications, 2024)
The zoonotic bacterium Coxiella (C.) burnetii can be excreted by infected goats through birth products and milk. The detection of C. burnetii DNA in the mammary gland tissue of infected dairy goats and intermittent milk shedders has been reported, but confirmation of C. burnetii bacteria in the udder remained pending. The pathogen caused abortions in a 152-head dairy goat herd, resulting in the vaccination against C. burnetii of the entire herd with annual boosters. To monitor the C. burnetii shedding at herd level, monthly bulk tank milk (BTM) samples were analyzed using PCR (IS 1111 ). Despite vaccination, C. burnetii DNA was detected in BTM samples within the first 16 months of the study. Therefore, individual milk samples were tested on four different occasions several months apart to identify potential intermittent milk shedders. Only one goat (#67455) tested positive three times. This goat was necropsied to investigate the presence of C. burnetii in the udder and other organs. PCR detected C. burnetii DNA solely in both mammary glands and the left teat cistern. Immunohistological examination identified C. burnetii antigen in mammary gland tissue, confirmed by the detection of C. burnetii bacteria in the mammary epithelial cells using fluorescence in situ hybridization. The removal of goat #67455 led to negative BTM samples until the end of the study. The findings demonstrate the occurrence of C. burnetii in the mammary gland of a naturally infected and vaccinated goat. The presence possibly contributed to intermittent milk shedding of goat #67455, and the mammary gland tissue may serve as a replicative niche for C. burnetii .

Protecting Newfoundland’s Palaeontological Geoheritage: Mitigating Anthropic and Environmental Damage to the Ediacaran Fossils of Upper Island Cove - Christopher McKean; Jack J. Matthews; Benjamin W. T. Rideout; Rod S. Taylor; Duncan McIlroy (Geoheritage, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Genetic mapping reveals the complex genetic architecture controlling slow canopy wilting in soybean - Ethan Menke; Clinton J. Steketee; Qijian Song; William T. Schapaugh; Thomas E. Carter; Benjamin Fallen; Zenglu Li (Theoretical and Applied Genetics, 2024)
In soybean [ Glycine max (L.) Merr.], drought stress is the leading cause of yield loss from abiotic stress in rain-fed US growing areas. Only 10% of the US soybean production is irrigated; therefore, plants must possess physiological mechanisms to tolerate drought stress. Slow canopy wilting is a physiological trait that is observed in a few exotic plant introductions (PIs) and may lead to yield improvement under drought stress. Canopy wilting of 130 recombinant inbred lines (RILs) derived from Hutcheson × PI 471938 grown under drought stress was visually evaluated and genotyped with the SoySNP6K BeadChip. Over four years, field evaluations of canopy wilting were conducted under rainfed conditions at three locations across the US (Georgia, Kansas, and North Carolina). Due to the variation in weather among locations and years, the phenotypic data were collected from seven environments. Substantial variation in canopy wilting was observed among the genotypes in the RIL population across environments. Three QTLs were identified for canopy wilting from the RIL population using composite interval mapping on chromosomes (Chrs) 2, 8, and 9 based on combined environmental analyses. These QTLs inherited the favorable alleles from PI 471938 and accounted for 11, 10, and 14% of phenotypic variation, respectively. A list of 106 candidate genes were narrowed down for these three QTLs based on the published information. The QTLs identified through this research can be used as targets for further investigation to understand the mechanisms of slow canopy wilting. These QTLs could be deployed to improve drought tolerance through a targeted selection of the genomic regions from PI 471938.

Neuroprotective Effect of Sterculia setigera Leaves Hydroethanolic Extract - Yendubé T. Kantati; Magloire K. Kodjo; Benjamin Lefranc; Magali Basille-Dugay; Sébastien Hupin; Isabelle Schmitz; Jérôme Leprince; Messanvi Gbeassor; David Vaudry (Journal of Molecular Neuroscience, 2024)

Association of size, climatic factors, and mercury body burdens with movement behavior in American alligators - Laura V. Kojima; Michel T. Kohl; Thomas R. Rainwater; Benjamin B. Parrott; Tracey D. Tuberville (Science of The Total Environment, 2024)

Spatio-temporal patterns of rangeland forage nutritive value and grazer selection with patch-burning in the US northern Great Plains - Jonathan W. Spiess; Devan Allen McGranahan; Marisol T. Berti; Caley K. Gasch; Torre Hovick; Benjamin Geaumont (Journal of Environmental Management, 2024)

Effects of space weathering on the Christiansen feature position of lunar surface materials - Nandita Kumari; Timothy D. Glotch; Katherine A. Shirley; Benjamin T. Greenhagen; Benjamin D. Byron (Icarus, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Microalgae: potential novel protein for sustainable human nutrition - Ellen Williamson; Ian L. Ross; Benjamin T. Wall; Benjamin Hankamer (Trends in Plant Science, 2024)

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Continuous co-treatment of mine drainage with municipal wastewater - Charles D. Spellman; Zachary T. Burton; Kaoru Ikuma; William H.J. Strosnider; Travis L. Tasker; Benjamin Roman; Joseph E. Goodwill (Journal of Environmental Management, 2024)

Heterozygous loss-of-function variants in DOCK4 cause neurodevelopmental delay and microcephaly - Charlotte Herbst; Viktoria Bothe; Meret Wegler; Susanne Axer-Schaefer; Séverine Audebert-Bellanger; Jozef Gecz; Benjamin Cogne; Hagit Baris Feldman; Anselm H. C. Horn; Anna C. E. Hurst; Melissa A. Kelly; Michael C. Kruer; et al. (Human Genetics, 2024)
Neurons form the basic anatomical and functional structure of the nervous system, and defects in neuronal differentiation or formation of neurites are associated with various psychiatric and neurodevelopmental disorders. Dynamic changes in the cytoskeleton are essential for this process, which is, inter alia, controlled by the dedicator of cytokinesis 4 ( DOCK4 ) through the activation of RAC1 . Here, we clinically describe 7 individuals (6 males and one female) with variants in DOCK4 and overlapping phenotype of mild to severe global developmental delay. Additional symptoms include coordination or gait abnormalities, microcephaly, nonspecific brain malformations, hypotonia and seizures. Four individuals carry missense variants (three of them detected de novo) and three individuals carry null variants (two of them maternally inherited). Molecular modeling of the heterozygous missense variants suggests that the majority of them affect the globular structure of DOCK4. In vitro functional expression studies in transfected Neuro-2A cells showed that all missense variants impaired neurite outgrowth. Furthermore, Dock4 knockout Neuro-2A cells also exhibited defects in promoting neurite outgrowth. Our results, including clinical, molecular and functional data, suggest that loss-of-function variants in DOCK4 probable cause a variable spectrum of a novel neurodevelopmental disorder with microcephaly.

One hundred and six years of change in a S onoran D esert plant community: Impact of climate anomalies and trends in species sensitivities - Charlotte Brown; Susana Rodriguez Buritica; Deborah E. Goldberg; Frank Reichenbacher; D. Lawrence Venable; Robert H. Webb; Benjamin T. Wilder (Ecology, 2024)
A major restriction in predicting plant community response to future climate change is a lack of long‐term data needed to properly assess species and community response to climate and identify a baseline to detect climate anomalies. Here, we use a 106‐year dataset on a Sonoran Desert plant community to test the role of extreme temperature and precipitation anomalies on community dynamics at the decadal scale and over time. Additionally, we tested the climate sensitivity of 39 desert plant species and whether sensitivity was associated with growth form, longevity, geographic range, or local dominance. We found that desert plant communities had shifted directionally over the 106 years, but the climate had little influence on this directional change primarily due to nonlinear shifts in precipitation anomalies. Decadal‐scale climate had the largest impact on species richness, species relative density, and total plant cover, explaining up to 26%, 45%, and 55% of the variance in each, respectively. Drought and the interaction between the frequency of freeze events and above‐average summer precipitation were among the most influential climate factors. Increased drought frequency and wetter periods with frequent freeze events led to larger reductions in total plant cover, species richness, and the relative densities of dominant subshrubs Ambrosia deltoidea and Encelia farinosa . More than 80% of the tested species were sensitive to climate, but sensitivity was not associated with a species' local dominance, longevity, geographic range, or growth form. Some species appear to exhibit demographic buffering, where when they have a higher sensitivity to drought, they also tend to have a higher sensitivity to favorable (i.e., wetter and hotter) conditions. Overall, our results suggest that, while decadal‐scale climate variation substantially impacts these desert plant communities, directional change in temperature over the last century has had little impact due to the relative importance of precipitation and drought. With projections of increased drought in this region, we may see reductions in total vegetation cover and species richness due to the loss of species, possibly through a breakdown in their ability to demographically buffer climatic variation, potentially changing community dynamics through a change in facilitative and competitive processes.

Do carcass traits influence consumer perception of pork eating quality? - Dante T. Valente Junior; Ira B. Mandell; Benjamin M. Bohrer; Justice B. Dorleku; Cheryl P. Campbell; Tadeu E. Silva; Edenio Detmann; Alysson Saraiva; Manuel Juárez; Marcio S. Duarte (Meat Science, 2024)

Cost details from front-end engineering design of piperazine with the advanced stripper - Gary T. Rochelle; Fred Closmann; Miguel Abreu; Athreya Suresh Babu; Benjamin Drewry; Tianyu Gao; William A. Steen; Karen Farmer; Scott R. Bryan; Max Bernau; Andrew Sexton; Katherine Dombrowski; et al. (International Journal of Greenhouse Gas Control, 2024)

Analytical solutions to evaluate the geothermal energy generation potential from sedimentary-basin reservoirs - Daniel T. Birdsell; Benjamin M. Adams; Paromita Deb; Jonathan D. Ogland-Hand; Jeffrey M. Bielicki; Mark R. Fleming; Martin O. Saar (Geothermics, 2024)

Holocene warming of alpine rockwalls decreased rockwall erosion rates - Daniel Draebing; Till Mayer; Benjamin Jacobs; Steven A. Binnie; Miriam Dühnforth; Samuel T. McColl (Earth and Planetary Science Letters, 2024)

Hurricane Effects on Seagrass and Associated Nekton Communities in the Northern Gulf of Mexico - Kelly M. Correia; Scott B. Alford; Benjamin A. Belgrad; Kelly M. Darnell; M. Zachary Darnell; Bradley T. Furman; Margaret O. Hall; Christian T. Hayes; Charles W. Martin; Ashley McDonald; Delbert L. Smee (Estuaries and Coasts, 2024)

Status of intertidal populations of Pismo clams (Tivela stultorum) across their range in California - Alexandria R. Marquardt; Sara K. Park; Eliana G. Maietta; Noël M. Clark; Grant T. Waltz; Lisa A. Needles; Benjamin I. Ruttenberg (Regional Studies in Marine Science, 2023)

Movement dynamics, sediment turnover and sheltering behaviours of the nocturnal coral reef sea cucumber, Stichopus cf. monotuberculatus - Benjamin C. T. Gray; Maria Byrne; Matthew Clements; Steven W. Purcell (Coral Reefs, 2023)
Animal movement and feeding studies shed light on ecological roles and can inform management strategies for fished species. However, the feeding and movement of nocturnal sea cucumbers have been rarely studied. We determined the movement dynamics, feeding ecology and sheltering behaviour of the nocturnal Stichopus cf. monotuberculatus (dragonfish) at One Tree Reef and Heron Island Reef on the southern Great Barrier Reef. The short-term movement of individual sea cucumbers were tracked, and sediment defecation rates were measured. Displacement rates averaged 3–33 cm h −1 across the four sites, with the sea cucumbers moving more slowly approaching sunrise and within patches of organically rich sediment. The movement paths were moderately tortuous, with larger sea cucumbers moving along straighter paths. Rates of sediment turnover averaged 7.8 g h −1 and were greatest for larger individuals. The faecal casts were organically richer and composed of finer grains than the ambient surface sediments, implying that S. cf. monotuberculatus avoids consuming coarse sediments and feeds on nutritionally rich particles. The sea cucumbers sheltered under hard reef substrata and moved non-directionally on the seascape, with a few individuals homing back to their original refuges. The affinity to reef substrata and short nightly net displacements of S. cf. monotuberculatus have implications for the spatial management of this and other similar species. Larger individuals occupied deeper refuges, implying that projected declines in substratum rugosity on coral reefs due to climate change could impact the size structure of sea cucumber populations, with implications for fisheries.

A review to frame the utilization of Eastern black walnut (Juglans nigra L.) cultivars in alley cropping systems - Benjamin Bishop; Nicholas A. Meier; Mark V. Coggeshall; Sarah T. Lovell; Ronald S. Revord (Agroforestry Systems, 2023)
Agroforestry adoptition is gaining considerable traction in the temperate US with growing popularity and government incentives (e.g., the Partnerships for Climate-Smart Commodities Project) for systems with greenhouse gas mitigation potential. The identification of complementary species combinations will accelerate the expansion of temperate agroforestry. Since the mid-19th century, European timber plantations have taken advantage of the late-leafing habit of walnut ( Juglans spp.) to grow a spring grain crop between the tree rows. Such alley cropping systems increase land-use efficiency and provide extensive environmental benefits. A parallel but underutilized opportunity in North American involves incorporating eastern black walnut ( Juglans nigra L.) cultivars into alley cropping systems (ACS). Eastern black walnut, henceforth referred to as black walnut, is native to North America and exhibits architectural and phenological characters for reduced competition with winter cereal crops grown in alleys. Black walnut also produces nutritious nuts, and cultivars with improved kernel percentage and mass offer potential to cultivate the species as a domesticated orchard crop, as opposed to just the high-quality timber for which it is well-known. However, field observations suggest significant variation in tree architecture and phenology amongst cultivars, which is likely to influence complementarity with winter grains. Comprehensive characterization of trait genetic diversity is needed to best leverage germplasm into productive systems. Here, we review literature related to implementing ACS with consideration of cultivar-dependent traits that may reduce interspecific competition. While the focus is directed toward black walnut, broad characterization of other underutilized fruit/nut species will allow for robust diversification of ACS.

Keratose Hydrogel Drives Differentiation of Cardiac Vascular Smooth Muscle Progenitor Cells: Implications in Ischemic Treatment - Benjamin T. Ledford; Miao Chen; Mark Van Dyke; Catherine Barron; Xiaonan Zhang; Aurora Cartaya; Youjing Zheng; Ahmet Ceylan; Aaron Goldstein; Jia-Qiang He (Stem Cell Reviews and Reports, 2023)

What do older patients know about their medication? A cross-sectional, interview-based pilot study - Olaf Krause; Corinna T. Ziemann; Martin Schulze Westhoff; Sebastian Schröder; Benjamin Krichevsky; Stephan Greten; Dirk O. Stichtenoth; Johannes Heck (European Journal of Clinical Pharmacology, 2023)
Purpose This study sought to analyze the medication knowledge and awareness of medication adjustment options during intercurrent illness (sick day rules) of patients ≥ 70 years treated at a hospital for geriatric medicine in northern Germany. Methods The study was designed as a cross-sectional, interview-based pilot study, was approved by the Ethics Committee of Hannover Medical School (No. 10274_BO_K_2022; date of approval: 11 March 2022), and enrolled a convenience sample of 100 patients between May and December 2022. Results The median of the average medication knowledge score in the study population (median age 82 years (IQR 75–87); 71% female) was 5 on a scale from 0 to 6 (IQR 3.8–5.6). Women achieved higher average medication knowledge scores than men (median 5.1 (IQR 4–5.6) vs. median 4.3 (IQR 3.6–5.1); p = 0.012), and patients < 80 years achieved higher average medication knowledge scores than patients ≥ 80 years (median 5.4 (IQR 4.9–5.7) vs. median 4.3 (IQR 3.2–5.3); p < 0.001). Sick day rules were known for only 1.1% of drugs for which sick day rules were applicable. Fifty-two percent of the patients reported that their general practitioner contributed most to their medication knowledge, and 66% considered their daily number of drugs to take adequate. Conclusion Our study showed that medication knowledge of older patients was overall satisfying. Awareness of sick day rules, however, was poor. Future studies should evaluate the clinical benefits of sick day rules and ways of better communicating sick day rules to patients. In this regard, general practitioners may play a decisive role.

Ocean acidification influences the gene expression and physiology of two Caribbean bioeroding sponges - John T. Morris; Ian C. Enochs; Michael S. Studivan; Benjamin D. Young; Anderson Mayfield; Nash Soderberg; Nikki Traylor-Knowles; Graham Kolodziej; Derek Manzello (Frontiers in Marine Science, 2023)
Introduction Coral reef ecosystems are experiencing increased rates of carbonate dissolution due to losses in live coral cover coupled with the impacts of ocean acidification (OA) on coral reef calcifiers and bioeroders. While the stimulating effect of OA on bioerosion has been demonstrated experimentally, predominantly in the Pacific, the underlying physiological and molecular mechanisms behind the response are still poorly understood. Methods To address this, we subjected common zooxanthellate ( Cliona varians ) and azooxanthellate ( Pione lampa ) Caribbean sponges to pre-industrial (8.15 pH), present-day (8.05 pH), and two future OA scenarios (moderate OA, 7.85 pH; extreme OA, 7.75 pH) and evaluated their physiological and transcriptomic responses. Results The influence of OA on sponge bioerosion was nonlinear for both species, with the greatest total bioerosion and chemical dissolution rates found in the 7.85 pH treatment, then not increasing further under the more extreme 7.75 pH conditions. A trend towards reduced bioerosion rates in the 7.75 pH treatment occurred regardless of the presence of algal symbionts and suggests that the sponges may become physiologically impaired under prolonged OA exposure, resulting in diminished bioerosion potential. These findings were supported by the RNA-seq analysis, which revealed differentially expressed genes involved in a stress response to OA, in particular, suppressed metabolism. Discussion This may indicate that the sponges had reallocated energy resources towards more critical physiological needs in response to OA as a survival mechanism under stressful conditions. These data reveal that while the bioerosion rates of excavating sponges in Caribbean reef ecosystems may increase under moderate OA scenarios, this OA-stimulation may plateau or be lost at extreme end-of-century pH conditions, with implications for the dissolution and long-term persistence of reef habitat structures.

The ethics of intervening in animal behaviour for conservation - Thom van Dooren; Catherine J. Price; Peter B. Banks; Oded Berger-Tal; Matthew Chrulew; Jane Johnson; Gabrielle Lajeunesse; Kate E. Lynch; Clare McArthur; Finn C.G. Parker; Myles Oakey; Benjamin J. Pitcher; et al. (Trends in Ecology & Evolution, 2023)

Bewildering biogeography: Waves of dispersal and diversification across southern Wallacea by bent-toed geckos (genus: Cyrtodactylus) - Sean B. Reilly; Alexander L. Stubbs; Benjamin R. Karin; Evy Arida; Umilaela Arifin; Amir Hamidy; Hinrich Kaiser; Ke Bi; Awal Riyanto; Djoko T. Iskandar; Jimmy A. McGuire (Molecular Phylogenetics and Evolution, 2023)

AgAnimalGenomes: browsers for viewing and manually annotating farm animal genomes - Deborah A. Triant; Amy T. Walsh; Gabrielle A. Hartley; Bruna Petry; Morgan R. Stegemiller; Benjamin M. Nelson; Makenna M. McKendrick; Emily P. Fuller; Noelle E. Cockett; James E. Koltes; Stephanie D. McKay; Jonathan A. Green; et al. (Mammalian Genome, 2023)
Current genome sequencing technologies have made it possible to generate highly contiguous genome assemblies for non-model animal species. Despite advances in genome assembly methods, there is still room for improvement in the delineation of specific gene features in the genomes. Here we present genome visualization and annotation tools to support seven livestock species (bovine, chicken, goat, horse, pig, sheep, and water buffalo), available in a new resource called AgAnimalGenomes. In addition to supporting the manual refinement of gene models, these browsers provide visualization tracks for hundreds of RNAseq experiments, as well as data generated by the Functional Annotation of Animal Genomes (FAANG) Consortium. For species with predicted gene sets from both Ensembl and RefSeq, the browsers provide special tracks showing the thousands of protein-coding genes that disagree across the two gene sources, serving as a valuable resource to alert researchers to gene model issues that may affect data interpretation. We describe the data and search methods available in the new genome browsers and how to use the provided tools to edit and create new gene models.

Interdisciplinary approaches to advancing anti-racist pedagogies in ecology, evolution, and conservation biology - Benjamin A. Hà; Kiana Foxx; Samantha T. Mensah; Paul H. Barber; Rachel L. Kennison (Trends in Ecology & Evolution, 2023)

Overexpression of the UDP-glycosyltransferase UGT34A23 confers resistance to the diamide insecticide chlorantraniliprole in the tomato leafminer, Tuta absoluta - Charles Grant; Kumar Saurabh Singh; Angela Hayward; Benjamin J. Hunt; Bartlomiej J. Troczka; Adam Pym; Seung-Joon Ahn; Bin Zeng; Cong-Fen Gao; Alicia Leroux; Eve Daum; Philip Süess; et al. (Insect Biochemistry and Molecular Biology, 2023)

Environmental formation of methylmercury is controlled by synergy of inorganic mercury bioavailability and microbial mercury‐methylation capacity - Benjamin D. Peterson; David P. Krabbenhoft; Katherine D. McMahon; Jacob M. Ogorek; Michael T. Tate; William H. Orem; Brett A. Poulin (Environmental Microbiology, 2023)
Methylmercury (MeHg) production is controlled by the bioavailability of inorganic divalent mercury (Hg(II) i ) and Hg‐methylation capacity of the microbial community (conferred by the hgcAB gene cluster). However, the relative importance of these factors and their interaction in the environment remain poorly understood. Here, metagenomic sequencing and a full‐factorial MeHg formation experiment were conducted across a wetland sulfate gradient with different microbial communities and pore water chemistries. From this experiment, the relative importance of each factor on MeHg formation was isolated. Hg(II) i bioavailability correlated with the dissolved organic matter composition, while the microbial Hg‐methylation capacity correlated with the abundance of hgcA genes. MeHg formation responded synergistically to both factors. Notably, hgcA sequences were from diverse taxonomic groups, none of which contained genes for dissimilatory sulfate reduction. This work expands our understanding of the geochemical and microbial constraints on MeHg formation in situ and provides an experimental framework for further mechanistic studies.

A spatially explicit model of tree leaf litter accumulation in fire maintained longleaf pine forests of the southeastern US - Nuria Sánchez-López; Andrew T. Hudak; Luigi Boschetti; Carlos A. Silva; Kevin Robertson; E Louise Loudermilk; Benjamin C. Bright; Mac A. Callaham; Melanie K. Taylor (Ecological Modelling, 2023)

The effect of mobility-related anxiety on walking across the lifespan: a virtual reality simulation study - Tiphanie E. Raffegeau; Mindie Clark; Bradley Fawver; Benjamin T. Engel; William R. Young; A. Mark Williams; Keith R. Lohse; Peter C. Fino (Experimental Brain Research, 2023)

Recent progress on understanding coronal mass ejection/flare onset by a NASA living with a star focused science team - Mark G. Linton; Spiro K. Antiochos; Graham Barnes; Yuhong Fan; Yang Liu; Benjamin J. Lynch; Andrey N. Afanasyev; C. Nick Arge; Joan Burkepile; Mark C.M. Cheung; Joel T. Dahlin; Marc L. DeRosa; et al. (Advances in Space Research, 2023)

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

Marine fishes of Palawan, Philippines: Species diversity, new records, and conservation status - Rodulf Anthony T. Balisco; Victor S. Ticzon; Badi R. Samaniego; Wen-Chien Huang; Benjamin J. Gonzales; Te-Yu Liao (Regional Studies in Marine Science, 2023)

Role of α6-Nicotinic Receptors in Alcohol-Induced GABAergic Synaptic Transmission and Plasticity to Cholinergic Interneurons in the Nucleus Accumbens - Hillary A. Wadsworth; Elizabeth Q. Anderson; Benjamin M. Williams; Joakim W. Ronström; Janna K. Moen; Anna M. Lee; J. Michael McIntosh; Jie Wu; Jordan T. Yorgason; Scott C. Steffensen (Molecular Neurobiology, 2023)

Genomic analysis of Bornean geckos (Gekkonidae: Cyrtodactylus ) reveals need for updated taxonomy - Hayden R. Davis; Izneil Nashriq; Kyra S. Woytek; Shanelle A. Wikramanayake; Aaron M. Bauer; Benjamin R. Karin; Ian G. Brennan; Djoko T. Iskandar; Indraneil Das (Zoologica Scripta, 2023)
Using molecular genetic data, recognised diversity within the gecko genus Cyrtodactylus has more than doubled, with many lineages that were once thought to be wide‐ranging being delimited into multiple independent species. On the Southeast Asian island of Borneo, there has been a recent renewed focus on reptile taxonomy, as genetic data have demonstrated a high amount of unrecognised biodiversity. We herein advance this taxonomic trend by delimiting three distinct species within the Cyrtodactylus consobrinus species complex: C. consobrinus, C. kapitensis sp. n., and C. hutan sp. n. To do so, we use a combination of ddRADseq and single‐locus data, and morphological data. Using genomic data, we test species and population boundaries within the consobrinus species complex and show minimal population structure but high species‐level diversity. Despite not finding uniquely diagnostic morphological characters to delimit the new species, we suggest a combination of characters that can be used to identify each lineage. Lastly, we use our data to comment on the status of C. malayanus , with indications that this lineage is also better considered a species complex. These data highlight the prevalence of unrecognised lineages on Borneo, many of which face threats due to increasing deforestation and other anthropogenic pressures.

CRELD1 variants are associated with bicuspid aortic valve in Turner syndrome - Catherina T. Pinnaro; Chloe B. Beck; Heather J. Major; Benjamin W. Darbro (Human Genetics, 2023)
Turner syndrome (TS) is a chromosomal disorder caused by complete or partial loss of the second sex chromosome and exhibits phenotypic heterogeneity, even after accounting for mosaicism and karyotypic variation. Congenital heart defects (CHD) are found in up to 45 percent of girls with TS and span a phenotypic continuum of obstructive left-sided lesions, with bicuspid aortic valve (BAV) being the most common. Several recent studies have demonstrated a genome-wide impact of X chromosome haploinsufficiency, including global hypomethylation and altered RNA expression. The presence of such broad changes to the TS epigenome and transcriptome led others to hypothesize that X chromosome haploinsufficiency sensitizes the TS genome, and several studies have demonstrated that a second genetic hit can modify disease susceptibility in TS. The objective of this study was to determine whether genetic variants in known heart developmental pathways act synergistically in this setting to increase the risk for CHD, specifically BAV, in TS. We analyzed 208 whole exomes from girls and women with TS and performed gene-based variant enrichment analysis and rare-variant association testing to identify variants associated with BAV in TS. Notably, rare variants in CRELD1 were significantly enriched in individuals with TS who had BAV compared to those with structurally normal hearts. CRELD1 is a protein that functions as a regulator of calcineurin/NFAT signaling, and rare variants in CRELD1 have been associated with both syndromic and non-syndromic CHD. This observation supports the hypothesis that genetic modifiers outside the X chromosome that lie in known heart development pathways may influence CHD risk in TS.

Diverse patterns of larval coral reef fish vertical distribution and consequences for dispersal and connectivity - Christina M. Hernández; Claire B. Paris; Ana C. Vaz; Benjamin T. Jones; Julie B. Kellner; David E. Richardson; Su Sponaugle; Robert K. Cowen; Joel K. Llopiz (Coral Reefs, 2023)

Kinetic proteomics identifies targeted changes in liver metabolism and the ribo-interactome by dietary sulfur amino acid restriction - William O. Jonsson; Agnieszka K. Borowik; Atul Pranay; Michael T. Kinter; Emily T. Mirek; Jordan L. Levy; Elizabeth M. Snyder; Benjamin F. Miller; Tracy G. Anthony (GeroScience, 2023)
Dietary sulfur amino acid restriction (SAAR) protects against diet-induced obesity, extends healthspan, and coincides with an overall reduction in hepatic protein synthesis. To explore the underpinnings of SAAR-induced slowed growth and its impact on liver metabolism and proteostasis, we resolved changes in hepatic mRNA and protein abundances and compared synthesis rates of individual liver proteins. To achieve this, adult male mice were provided deuterium-labeled drinking water while freely consuming either a regular-fat or high-fat diet that was SAA restricted. Livers from these mice and their respective dietary controls were used to conduct transcriptomic, proteomic, and kinetic proteomic analyses. We found that remodeling of the transcriptome by SAAR was largely agnostic to dietary fat content. Shared signatures included activation of the integrated stress response alongside alterations in metabolic processes impacting lipids, fatty acids, and amino acids. Changes to the proteome correlated poorly with the transcriptome, and yet, functional clustering of kinetic proteomic changes in the liver during SAAR revealed that the management of fatty acids and amino acids were altered to support central metabolism and redox balance. Dietary SAAR also strongly influenced the synthesis rates of ribosomal proteins and ribosome-interacting proteins regardless of dietary fat. Taken together, dietary SAAR alters the transcriptome and proteome in the liver to safely manage increased fatty acid flux and energy use and couples this with targeted changes in the ribo-interactome to support proteostasis and slowed growth.

A chromosome-level genome assembly reveals that a bipartite gene cluster formed via an inverted duplication controls monoterpenoid biosynthesis in Schizonepeta tenuifolia - Chanchan Liu; Samuel J. Smit; Jingjie Dang; Peina Zhou; Grant T. Godden; Zheng Jiang; Wukun Liu; Licheng Liu; Wei Lin; Jinao Duan; Qinan Wu; Benjamin R. Lichman (Molecular Plant, 2023)

Free comment as a valuable approach to characterize and identify the drivers of liking of high-protein flavored milk drink submitted to ohmic heating - Ramon S. Rocha; Benjamin Mahieu; Elson R. Tavares Filho; Patrícia B. Zacarchenco; Mônica Q. Freitas; Eliane T. Mársico; Tatiana C. Pimentel; Erick A. Esmerino; Adriano G. Cruz (Food Research International, 2023)

Radon-222 as a groundwater discharge tracer to surface waters - Dini Adyasari; Natasha T. Dimova; Henrietta Dulai; Benjamin S. Gilfedder; Ian Cartwright; Tristan McKenzie; Peter Fuleky (Earth-Science Reviews, 2023)

Hierarchical cue control of cocaine seeking in the face of cost - Val Collins; Kaisa N. Bornhoft; Amy Wolff; Sonal Sinha; Benjamin T. Saunders (Psychopharmacology, 2023)

Automated attribution of forest disturbance types from remote sensing data: A synthesis - Amanda T. Stahl; Robert Andrus; Jeffrey A. Hicke; Andrew T. Hudak; Benjamin C. Bright; Arjan J.H. Meddens (Remote Sensing of Environment, 2023)

Effects of EU illegal logging policy on timber-supplying countries: A systematic review - Fredy D. Polo Villanueva; Yitagesu T. Tegegne; Georg Winkel; Paolo Omar Cerutti; Sabaheta Ramcilovic-Suominen; Constance L. McDermott; Jonathan Zeitlin; Metodi Sotirov; Benjamin Cashore; David Andrew Wardell; Andrew Haywood; Lukas Giessen (Journal of Environmental Management, 2023)

Walk and chew gum: A demand and supply illustration of macro and micro net-zero initiatives for the automobile industry - Lawrence W.C. Lai; Frank T. Lorne; Mostafa Purmehdi; Katarina Grozdanic; Adam Aldad; Taniya Grace Joshua; Hao Benjamin Ling; Haonan Chi; Marcia Monti Sabaini; Shuang Yan; Mingfei Lai (Sustainable Production and Consumption, 2023)

The genome sequence of the Neotropical brown stink bug, Euschistus heros provides insights into population structure, demographic history and signatures of adaptation - Kumar Saurabh Singh; Erick M.G. Cordeiro; Benjamin J. Hunt; Aniruddha A. Pandit; Patricia L. Soares; Alberto S. Correa; Christoph T. Zimmer; Maria I. Zucchi; Carlos Batista; Julian A.T. Dow; Shireen-Anne Davies; Fernando Luís Cônsoli; et al. (Insect Biochemistry and Molecular Biology, 2023)

Comparative spatially explicit approach for testing effects of soil chemicals on terrestrial wildlife bioindicator demographics - Sean M. Murphy; Charles D. Hathcock; Tatiana N. Espinoza; Philip R. Fresquez; Jesse T. Berryhill; Jenna E. Stanek; Benjamin J. Sutter; Shannon M. Gaukler (Environmental Pollution, 2023)

Detecting hydrologic distinctions among Andean lakes using clumped and triple oxygen isotopes - Sarah A. Katz; Naomi E. Levin; Donald T. Rodbell; David P. Gillikin; Phoebe G. Aron; Benjamin H. Passey; Pedro M. Tapia; Analucía R. Serrepe; Mark B. Abbott (Earth and Planetary Science Letters, 2023)

Advances in polymer-based detection of environmental ibuprofen in wastewater - Ntombenhle Masanabo; Benjamin Orimolade; Azeez O. Idris; Thabo T. I. Nkambule; Bhekie B. Mamba; Usisipho Feleni (Environmental Science and Pollution Research, 2022)

ProX from marine Synechococcus spp. show a sole preference for glycine‐betaine with differential affinity between ecotypes - Benjamin A. Ford; Pramita Ranjit; Bridget C. Mabbutt; Ian T. Paulsen; Bhumika S. Shah (Environmental Microbiology, 2022)
Osmotic stress, caused by high or fluctuating salt concentrations, is a crucial abiotic factor affecting microbial growth in aquatic habitats. Many organisms utilize common responses to osmotic stress, generally requiring active extrusion of toxic inorganic ions and accumulation of compatible solutes to protect cellular machinery. We heterologously expressed and purified predicted osmoprotectant, proline/glycine betaine‐binding proteins (ProX) from two phylogenetically distinct Synechococcus spp. MITS9220 and WH8102. Homologues of this protein are conserved only among Prochlorococcus LLIV and Synechococcus clade I, III and CRD1 strains. Our biophysical characterization show Synechococcus ProX exists as a dimer, with specificity solely for glycine betaine but not to other osmoprotectants tested. We discovered that MITS9220_ProX has a 10‐fold higher affinity to glycine betaine than WH8102_ProX, which is further elevated (24‐fold) in high salt conditions. The stronger affinity and effect of ionic strength on MITS9220_ProX glycine betaine binding but not on WH8102_ProX alludes to a novel regulatory mechanism, providing critical functional insights into the phylogenetic divergence of picocyanobacterial ProX proteins that may be necessary for their ecological success.

Bacterioplankton dispersal and biogeochemical function across Alaskan Arctic catchments - Raymond M. Lee; Natasha Griffin; Erin Jones; Benjamin W. Abbott; Rebecca J. Frei; Samuel Bratsman; Mary Proteau; Isabella M. Errigo; Arial Shogren; William B. Bowden; Jay P. Zarnetske; Zachary T. Aanderud (Environmental Microbiology, 2022)
In Arctic catchments, bacterioplankton are dispersed through soils and streams, both of which freeze and thaw/flow in phase, seasonally. To characterize this dispersal and its potential impact on biogeochemistry, we collected bacterioplankton and measured stream physicochemistry during snowmelt and after vegetation senescence across multiple stream orders in alpine, tundra, and tundra‐dominated‐by‐lakes catchments. In all catchments, differences in community composition were associated with seasonal thaw, then attachment status (i.e. free floating or sediment associated), and then stream order. Bacterioplankton taxonomic diversity and richness were elevated in sediment‐associated fractions and in higher‐order reaches during snowmelt. Families Chthonomonadaceae , Pyrinomonadaceae , and Xiphinematobacteraceae were abundantly different across seasons, while Flavobacteriaceae and Microscillaceae were abundantly different between free‐floating and sediment‐associated fractions. Physicochemical data suggested there was high iron (Fe + ) production (alpine catchment); Fe + production and chloride (Cl − ) removal (tundra catchment); and phosphorus (SRP) removal and ammonium (NH 4 + ) production (lake catchment). In tundra landscapes, these ‘hot spots’ of Fe + production and Cl − removal accompanied shifts in species richness, while SRP promoted the antecedent community. Our findings suggest that freshet increases bacterial dispersal from headwater catchments to receiving catchments, where bacterioplankton‐mineral relations stabilized communities in free‐flowing reaches, but bacterioplankton‐nutrient relations stabilized those punctuated by lakes.

L-lactic and 2-ketoglutaric Acids, Odors from Human Skin, Govern Attraction and Landing in Host-Seeking Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Brogan Amos; Jan Bello; Ring T. Cardé (Journal of Insect Behavior, 2022)
Aedes aegypti , presented with a source of L-lactic and 2-ketoglutaric acid in a wind-tunnel bioassay, takeoff, fly upwind, and land on the odorant substrate at rates comparable to those exhibited by mosquitoes presented with a skin-odor stimulus. Addition of carbon dioxide decreased takeoff latency but was not required to elicit upwind flight nor landings. Ketoglutaric acid, a recently identified component of human skin odor, combined with lactic acid elicits the full repertoire of mosquito host-seeking behaviors.

Predicted threats to a native squirrel from two invading species based on citizen science data - Theodore T. Tran; Benjamin E. Carter; Jessica A. Castillo Vardaro (Biological Invasions, 2022)

Sediment depth and accretion shape belowground mangrove carbon stocks across a range of climatic and geologic settings - Matthew T. Costa; Exequiel Ezcurra; Paula Ezcurra; Pelayo Salinas‐de‐León; Benjamin Turner; Joy Kumagai; James Leichter; Octavio Aburto‐Oropeza (Limnology and Oceanography, 2022)
Estimating the long‐term sedimentary carbon sinks of mangroves and other blue carbon ecosystems has rapidly become a focus of coastal research and conservation attention. Sampling coverage, however, remains low, with sediment cores sparsely distributed across a subset of mangrove environmental settings globally. Furthermore, the ecological and geological drivers of variation in these stocks remain incompletely understood. We assessed the limits of mangrove sedimentary carbon storage by sampling sediments in diverse mangrove environments across four geographic areas: the volcanic Galapagos, the arid Baja Peninsula, and the geologically and climatically distinct Caribbean and Pacific coasts of Panama. At 80 sites across these areas, we quantified the organic carbon density, sampled with depth, of entire sediment columns. Depth‐integrated carbon stocks are highly variable, from 1700 MgC org ha −1 . The positive relationship between sediment carbon density and annual rainfall demonstrated in global studies was not observed across these areas, though some carbon density differences were evident. Variation in sediment depth, ranging from 7 to 427 cm across sites, largely explained variation in carbon stock across the areas studied. These results underscore the importance of using measurements of sediment depth to estimate carbon stock. Long‐term geomorphological processes, such as the build‐up of sediment deposits shaped by coastal dynamics, play a major role in shaping mangrove carbon stocks. Investigating and accounting for these processes will enable more accurate estimation of this variable and valuable carbon pool.

Implications of barrier ephemerality in geogenomic research - Raúl Araya‐Donoso; Sarah M. Baty; Pedro Alonso‐Alonso; María José Sanín; Benjamin T. Wilder; Adrian Munguia‐Vega; Greer A. Dolby (Journal of Biogeography, 2022)
Aim Previous population genetic and phylogeographical studies have shown how generation time and dispersal affect population divergence in the presence of a vicariant barrier. More recently, speciation genomic studies have revealed that selection and recombination can be equally impactful. Here, we test how the interaction of these factors shapes the divergence expected in response to an ephemeral barrier and compare these results to empirical literature using the Baja California peninsula as a test case. Location Global. Taxon Diploid eukaryotes. Methods We forward simulated population genomic data with CDMetaPOP and SLiM by varying dispersal rate, mutation rate, generation time, selection pressure and recombination in the presence and then removal of a physical barrier. We tested which factors affect the divergence signal (measured as F ST ). We compared simulation results to empirical literature that included 147 records of generation times and 78 divergence estimates from population genomic studies. Results Population differentiation not only occurred due to the presence of a barrier under lower dispersal abilities but also emerged as a result of low dispersal among structured populations without a barrier. Divergent selection strengthened differentiation, which is supported by empirical data. Barrier removal quickly eroded the divergence signal (~500 generations) for high‐dispersing species, but low dispersal species retained divergence after gene flow resumed. In the empirical data, generation times varied by four orders of magnitude and dispersal by three orders of magnitude. Main Conclusions Divergence can arise without vicariant barriers, it may not produce a tight co‐divergence peak in absolute time, and co‐divergence may not imply a common cause of divergence. Deeper integration of geologic, climatic and genomic data (i.e. geogenomics) may help clarify origins of divergence in physically complex settings.

Perspectives on strengthening local food systems in Small Island Developing States - Cornelia Guell; Catherine R. Brown; Otto W. Navunicagi; Viliamu Iese; Neela Badrie; Morgan Wairiu; Arlette Saint Ville; Nigel Unwin; Sashi Kiran; T. Alafia Samuels; Ian Hambleton; Colin Tukuitonga; et al. (Food Security, 2022)
Small Island Developing States (SIDS) share high burdens of nutrition-related conditions, including non-communicable diseases, associated with an increasing reliance on imported, processed foods. Improving health through increasing the production and consumption of local, nutritious foods is a policy objective of many SIDS governments. This study aimed to understand contemporary challenges and opportunities to strengthening local food systems in two case study settings, Fiji and St. Vincent and the Grenadines. Fifty-two in-depth, semi-structured interviews were conducted with key stakeholders involved in local food production. Interviews were analysed by both country teams using thematic analysis. Local food production networks in both settings included formal governance bodies as well as more informal connections through civil society and communities. Their main function was the sharing of resources and knowledge, but levels of trust and cooperation between the stakeholders varied in a market open to intense competition from imports. Local food production was hindered by few and slow investments by local governments, dated technology, and lack of knowledge. Stakeholders believed this marginalisation was occurring against a background of rising preferences for imported foods in the population, and increasing disinterest in employment in the sector. Despite the challenges, strong narratives of resilience and opportunity were highlighted such as national pride in local produce for commercialisation and local diets. Efforts to support local food production in SIDS should focus on strengthening governance structures to prioritise local produce over corporate and import markets, assist collaboration and co-learning, and support alternative agro-food practices.

Genetic diversity and population structure of some Nigerian accessions of Bambara groundnut (Vigna subterranea (L.) Verdc.,) using DArT SNP markers - Opeyemi T. Osundare; Benjamin O. Akinyele; Alexander C. Odiyi; Rajneesh Paliwal; Olaniyi A. Oyatomi; Michael T. Abberton (Genetic Resources and Crop Evolution, 2022)
Bambara groundnut is one of the crops with inadequate molecular research to show its full potentials. Previous studies showed morphological diversity with inadequate information to confirm genetic variations. In the quest to reveal the genetic potentials, deoxyribonucleic acid (DNA) of the selected accessions was extracted through leaf samples at 3 weeks old, using Dellaporta Miniprep for Plant DNA Isolation procedure. The high quality DNA was sequenced using Diversity Arrays Technology (DArT) markers to unlock diversity among Bambara groundnut of Nigerian origin. Cluster analysis (neighbor-joining clustering) of the single nucleotide polymorphisms (SNP’s) were used to generate sub-population to show relatedness and differences. Seven sub-populations were generated with 5927 (50.13%) high quality DArT markers out of the 11,821 SNPs generated. This revealed high genetic diversity existed among the selected Bambara groundnut accessions in Nigeria. This also revealed that DArT markers were highly efficient in classifying the accessions based on molecular expressions. This study also identified markers responsible for genetic variation that could facilitate the characterization of larger collections for further utilization of genetic resources and most importantly Bambara groundnut for the purpose of crop improvement.

Data Gathering in UWA Sensor Networks: Practical Considerations and Lessons from Sea Trials - Nils Morozs; Benjamin Sherlock; Benjamin T. Henson; Jeffrey A. Neasham; Paul D. Mitchell; Yuriy Zakharov (Journal of Marine Science and Engineering, 2022)
Underwater acoustic (UWA) network protocol design is a challenging task due to several factors, such as slow propagation of acoustic waves, low frequency bandwidth and high bit error and frame error rates often encountered in real UWA environments. In this paper, we consider the design of a robust and scalable data gathering protocol for UWA sensor networks (UASNs), focusing on practical considerations and lessons learnt from multiple lake and sea trials. A cross-layer protocol is presented that integrates a network discovery process, intelligent routing, scheduling via Transmit Delay Allocation MAC (TDA-MAC) and multi-node Automatic Repeat Request (ARQ), to facilitate reliable data gathering in practical UASN deployments. Furthermore, this paper presents the details of a novel experimental testbed and underwater sensor node prototype that were used for the trials reported in this study. Based on the results of the trials, important conclusions are drawn on the protocol features required to achieve reliable networked communication in realistic UWA environments. The insights gained from the trials are valuable both for further development of the proposed data gathering protocol, and for the wider UWA networking research community concerned with developing practical solutions for real-world UASN deployments.

The advantages and limitations of biophysical modelling as a tool for informing limit setting in New Zealand's barrier‐enclosed estuaries - Karin R. Bryan; Benjamin T. Stewart; Alex M. Port; Hannah F. E. Jones; Conrad A. Pilditch (New Zealand Journal of Marine and Freshwater Research, 2022)
Estuaries are the receiving environment for catchment‐derived contaminants, the fate of which depends on the interplay between the estuarine geomorphology and hydrodynamics. In large estuaries, biophysical processes are spatially and temporally‐diverse, which makes understanding and managing the impact of human activities challenging. Here we use two common modelling approaches to explore the advantages and limitations of biophysical modelling as a tool for limit setting in a large barrier‐enclosed estuary in New Zealand. The model shows the large spatial variation in water quality associated with low upper harbour flushing. Variations can also be attributed to spatial variation in processes (such as denitrification). Although the non‐linear interactions between processes within these models can limit the value of using specific detail of outputs for decision making, the general patterns and sensitivities can be used to define areas, explore connectivity, and provide some information when monitoring data is lacking. Even in a deterministic modelling environment, it can very difficult to attribute water quality variations output at one location to the loading that caused these variations. While biophysical modelling will likely remain a core tool for informing management, any future development of limit setting methods for estuaries should recognise the inherent constraints we describe here.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Fish and Zooplankton Community Responses to the Cessation of Long-Term Invasive Eurasian Watermilfoil (Myriophyllum spicatum) Chemical Treatments in a North-Temperate, USA Lake - Benjamin T. Schleppenbach; Gregory Matzke; Stephanie L. Shaw; Greg G. Sass (Fishes, 2022)
2,4-Dichlorophenoxyacetic acid (2,4-D) is commonly used to control invasive aquatic macrophytes, including Eurasian watermilfoil (Myriophyllum spicatum) (EWM). Potential influences of 2,4-D on non-target organisms are poorly understood; however, research has suggested the possibility of lethal effects on certain fish species. Lake Ellwood, Wisconsin was treated with 2,4-D to control EWM annually during 2003–2012. Fish surveys following treatment revealed natural recruitment failures of several regionally thriving species, including largemouth bass (Micropterus salmoides) and bluegill (Lepomis macrochirus). We hypothesized that these species had been negatively influenced by the chemical treatments. We monitored the post-chemical treatment fish community and aquatic ecosystem for responses during 2013–2019. Similar data were collected from Cosgrove (EWM absent) and Seidel lakes (EWM present, no chemical treatment) as reference systems. Limnological and submersed aquatic vegetation conditions did not change on Lake Ellwood post-chemical treatment. Total zooplankton density increased immediately post-chemical treatment on Lake Ellwood and then stabilized, whereas total zooplankton density did not change on the reference lakes over time. Analyses indicated immediate increases in recruitment post-chemical treatment for largemouth bass, smallmouth bass (Micropterus dolomieu), bluegill, and yellow perch (Perca flavescens). Back calculation of year class strength confirmed failures occurred during treatment for northern pike (Esox lucius), largemouth bass, bluegill, and black crappie (Pomoxis nigromaculatus). Our results provide evidence to suggest long-term 2,4-D treatments may negatively influence fish through lethal and sublethal mechanisms. Thus, there remains a critical need for directed research on whole-lake herbicide treatment side-effects.

Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Short‐term movement dynamics of the world’s largest sea cucumbers (genus Thelenota ) - Benjamin C. T. Gray; Luke A. Calvert; Steven W. Purcell (Marine Ecology, 2022)
Movement studies on marine animals can inform conservation and fishery management planning through data that explain likely dispersals and home‐ranging behaviours. Relatively few studies are documented for exploited marine invertebrates, despite many having a high ecological and commercial value. We assessed the diurnal movement patterns of Thelenota ananas and Thelenota anax , the world's largest sea cucumbers, which are highly exploited throughout the Indo‐Pacific. At two coral reef sites at Lizard Island, northern Australia, we tracked the 2‐hourly displacement of individuals from morning to nightfall. Movement of T . ananas was more reef‐associated and tortuous than T . anax . Displacement rates averaged 80 cm h −1 (±8 SE) for T . ananas and 73 cm h −1 (±20) for T . anax . Body size accounted for half of the variation in displacement for T . ananas . Mobility peaked in the late afternoon or early evening for both species, and animals tended to reverse their direction of travel after midday. The data reflect a pattern of animals meandering out from their reef shelters onto sandy lagoon floors to forage, before returning to the reefs. This empirical evidence offers further support that these holothuroids contribute to the formation of “reef halos”. The exceptionally high movement rates and patterns found in this study should inform the design of spatial management measures.

Primacy of Human Odors Over Visual and Heat Cues in Inducing Landing in Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Ring T. Cardé (Journal of Insect Behavior, 2022)
Although human skin odor is thought to be the cue that anthropophilic mosquitoes use to discriminate us from other potential hosts, the precise details of how they use skin odor to find and land on a human is unclear. We found that Aedes aegypti land on a source of skin odor without a co-located visual cue. By collecting human odor on glass beads and using identical glass beads to visually conceal skin odor and heat cues, we were able to study mosquito landing on skin odor, heat, and visual cues separately. Landing is necessary for blood feeding which is a required behavior for the Aedes aegypti life cycle as well as the behavior responsible for the epidemiological impact of mosquitoes. Therefore, we consider it to be the diagnostic measure of the importance of a host cue. In two-choice tests, a skin odor source had the highest valence for landing, followed by a combination of heat and a visual cue, and finally heat and visual cues presented separately. We also measured the durations of the landings, though no significant differences were found.

Long-lasting effects of experimental flow intermittency on alpine stream macroinvertebrates (Val Roseg, Switzerland) - Annemieke M. Drost; Andre R. Siebers; Amael Paillex; Benjamin Misteli; Edwin T. H. M. Peeters; Christopher T. Robinson (Hydrobiologia, 2022)
Changing weather patterns and receding glaciers are predicted to increase flow intermittency in alpine streams. If aquatic macroinvertebrate communities largely comprise taxa adapted to perennial flows, an increase in flow intermittency substantially reduces biodiversity and affects functional processes. We conducted a before-after-control-impact field experiment to examine how macroinvertebrate communities in an alpine headwater stream responded to and recovered from a repeated experimental increase in flow intermittency. Flow in one channel was manipulated to simulate increased summer intermittency (June–September) over two consecutive years, whilst an adjacent channel served as a control. We monitored the density of benthic macroinvertebrates, periphyton and organic matter at approximately monthly intervals over three years during the snow-free period. Before manipulation, both channels had similar ecological properties. The flow manipulation reduced the overall macroinvertebrate density, and especially the proportional rheophile density, across both years. Recovery of the macroinvertebrate community following experimental flow intermittency took more than a year, and longer than our study period. This could be due to long aquatic life stages, dispersal limitation and biotic interactions. We conclude that climate-induced changes in alpine stream flow regimes can lead to a fundamental shift in macroinvertebrate assemblages through local extinctions, mostly of rheophilic species.

Microfossil analysis of dental calculus and isotopic measurements reveal the complexity of human-plant dietary relationships in Late Bronze Age Yunnan - Tingting Wang; Dong Wei; Zhilong Jiang; Xiumin Xia; Yan Wu; Zhen Han; Yating Qu; Yaowu Hu; Benjamin T. Fuller (Archaeological and Anthropological Sciences, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Correction to: Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)

Extreme longevity variants at the FOXO3 locus may moderate FOXO3 isoform levels - Ryan Frankum; Tom S. O. Jameson; Bridget A. Knight; Francis B. Stephens; Benjamin T. Wall; Timothy A. Donlon; Trevor Torigoe; Bradley J. Willcox; D. Craig Willcox; Richard C. Allsopp; Lorna W. Harries (GeroScience, 2022)
The rs2802292, rs2764264 and rs13217795 variants of FOXO3 have been associated with extreme longevity in multiple human populations, but the mechanisms underpinning this remain unclear. We aimed to characterise potential effects of longevity-associated variation on the expression and mRNA processing of the FOXO3 gene. We performed a comprehensive assessment of FOXO3 isoform usage across a wide variety of human tissues and carried out a bioinformatic analysis of the potential for longevity-associated variants to disrupt regulatory regions involved in isoform choice. We then related the expression of full length and 5′ truncated FOXO3 isoforms to rs13217795 genotype in peripheral blood and skeletal muscle from individuals of different rs13217795 genotypes. FOXO3 isoforms displayed considerable tissue specificity. We determined that rs13231195 and its tightly aligned proxy variant rs9400239 may lie in regulatory regions involved in isoform choice. The longevity allele at rs13217795 was associated with increased levels of full length FOXO3 isoforms in peripheral blood and a decrease in truncated FOXO3 isoforms in skeletal muscle RNA. We suggest that the longevity effect of FOXO3 SNPs may in part derive from a shift in isoform usage in skeletal muscle away from the production of 5′ truncated FOXO3 isoforms lacking a complete forkhead DNA binding domain, which may have compromised functionality.

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Turbidity Structures the Controls of Ecosystem Metabolism and Associated Metabolic Process Domains Along a 75-km Segment of a Semiarid Stream - Sarah A. S. Honious; Rebecca L. Hale; James J. Guilinger; Benjamin T. Crosby; Colden V. Baxter (Ecosystems, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Establishing Background Pathologic Changes of Valve Replacement Surgery in Sheep - Jill T. Schappa Faustich; John P. Carney; Matthew T. Lahti; Benjamin L. Zhang; Richard W. Bianco (Cardiovascular Engineering and Technology, 2022)
Purpose Sheep are the standard preclinical model for assessing safety of novel replacement heart valves, yet the anatomic and pathologic effects of invasive surgery, including those involving cardiopulmonary bypass (CPB), are unknown. Thus, we aimed to determine the gross, hematologic and biochemical effects of sham mitral and aortic replacement valve procedures in sheep to establish a useful control for evaluation of novel replacement valves. Methods Six control sheep were examined without any surgical intervention. Six sham mitral valve replacements (MVR) and six sham aortic valve replacements (AVR) were performed on 12 sheep. Complete blood counts and serum biochemistry were performed throughout the study. Sheep were sacrificed with a necropsy performed at 90 days. Results Renal infarcts (RIs) were the most frequently observed lesion, averaging 4.7 in control sheep, 2.5 with MVR and 5.8 with AVR. The number of infarcts strongly correlated with total estimated area of infarcted kidney ( r = .84, p < .01). Additional cardiac interventions were significantly correlated with increased numbers of RIs ( r = .85, p < .01). There was no correlation between number of RIs and time on CPB, or between AVR and MVR procedures. Conclusion The sheep model for AVR and MVR requires invasive surgery and CPB, which are associated with background anatomic and pathologic changes, especially in cases with additional surgical cardiac interventions. These findings serve as a critical control for future evaluation and development of novel replacement valves in order to distinguish device-related safety issues from expected outcomes of the surgical procedure and normal background changes in sheep.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Biophysical Settings that Influenced Plantation Survival During the 2015 Wildfires in Northern Rocky Mountain Moist Mixed-Conifer Forests - Theresa B Jain; Andrew S Nelson; Benjamin C Bright; John C Byrne; Andrew T Hudak (Journal of Forestry, 2022)
Fire suppression and the loss of western white pine (WWP) have made northern Rocky Mountain moist mixed-conifer forests less disturbance resilient. Although managers are installing hundreds of plantations, most of these plantations have not experienced wildfire since establishment. In 2015, wildfires burned through 100 WWP plantations in this region, providing an opportunity to evaluate the effects of wildfires on sapling survival. A Weibull distribution approach was used to characterize the variation of fire severity pixels, as indicated by the differenced normalized burn ratio. The distribution parameters provided a method to identify the biophysical setting and plantation characteristics influencing fire severity and sapling survival. Plantations located on lower slope positions were more resistant to wildfires than plantations located midslope or close to the ridges. Snow water equivalent was positively correlated with wildfire resistance and resilience. Results will help focus reforestation efforts and identify locations where future plantations can potentially survive wildfires.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Prochlorococcus extracellular vesicles: molecular composition and adsorption to diverse microbes - Steven J. Biller; Rachel A. Lundeen; Laura R. Hmelo; Kevin W. Becker; Aldo A. Arellano; Keven Dooley; Katherine R. Heal; Laura T. Carlson; Benjamin A. S. Van Mooy; Anitra E. Ingalls; Sallie W. Chisholm (Environmental Microbiology, 2022)
Summary Extracellular vesicles are small (~50–200 nm diameter) membrane‐bound structures released by cells from all domains of life. While vesicles are abundant in the oceans, their functions, both for cells themselves and the emergent ecosystem, remain a mystery. To better characterize these particles – a prerequisite for determining function – we analysed the lipid, protein, and metabolite content of vesicles produced by the marine cyanobacterium Prochlorococcus . We show that Prochlorococcus exports a diverse array of cellular compounds into the surrounding seawater enclosed within discrete vesicles. Vesicles produced by two different strains contain some materials in common, but also display numerous strain‐specific differences, reflecting functional complexity within vesicle populations. The vesicles contain active enzymes, indicating that they can mediate extracellular biogeochemical reactions in the ocean. We further demonstrate that vesicles from Prochlorococcus and other bacteria associate with diverse microbes including the most abundant marine bacterium, Pelagibacter . Together, our data point toward hypotheses concerning the functional roles of vesicles in marine ecosystems including, but not limited to, possibly mediating energy and nutrient transfers, catalysing extracellular biochemical reactions, and mitigating toxicity of reactive oxygen species.

Cover Image - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; Julia Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)

Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; July A. Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)
Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction.

Environmental Drivers of Seagrass-Associated Nekton Abundance Across the Northern Gulf of Mexico - Benjamin A. Belgrad; Kelly M. Correia; Kelly M. Darnell; M. Zachary Darnell; Christian T. Hayes; Margaret O. Hall; Bradley T. Furman; Charles W. Martin; Delbert L. Smee (Estuaries and Coasts, 2021)

Effects of a physical activity intervention on brain atrophy in older adults at risk of dementia: a randomized controlled trial - Benjamin Sinclair; Chris Steward; Vijay Venkatraman; Rowa Aljondi; Kay L. Cox; Kathryn A. Ellis; David Ames; Colin L. Masters; Pramit M. Phal; Matthew J. Sharman; Elizabeth V. Cyarto; Michelle M. Y. Lai; et al. (Brain Imaging and Behavior, 2021)

Correction to: Microphysics and Optical Attenuation in Fog: Observations from Two Coastal Sites - Qing Wang; Ryan T. Yamaguchi; John A. Kalogiros; Zachary Daniels; Denny P. Alappattu; Haflidi Jonsson; Oswaldo Alvarenga; Alex Olson; Benjamin J. Wauer; David G. Ortiz-Suslow; Harindra Joseph Fernando (Boundary-Layer Meteorology, 2021)

Microphysics and Optical Attenuation in Fog: Observations from Two Coastal Sites - Qing Wang; Ryan T. Yamaguchi; John A. Kalogiros; Zachary Daniels; Denny P. Alappattu; Haflidi Jonsson; Oswaldo Alvarenga; Alex Olson; Benjamin J. Wauer; David G. Ortiz-Suslow; Harindra Joseph Fernando (Boundary-Layer Meteorology, 2021)
A total of 15 fog events from two field campaigns are investigated: the High Energy Laser in Fog (HELFOG) project (central California) and the Toward Improving Coastal Fog Prediction (C-FOG) project (Ferryland Newfoundland). Nearly identical sensors were used in both projects to sample fog droplet-size spectra, wind, turbulence, and thermodynamic properties near the surface. Concurrent measurements of visibility were made by the present weather detector in both experiments, with the addition of a two-ended transmissometer in the HELFOG campaign. The analyses focused first on contrasting the observed fog microphysics and the associated thermodynamics from fog events in the two locations. The optical attenuation by fog was investigated using three methods: (1) derived from Mie theory using the measured droplet-size distribution, (2) parametrized as a function of fog liquid water content, and (3) parametrized in terms of total fog droplet number concentration. The consistency of these methods was investigated. The HELFOG data result in an empirical relationship between the meteorological range and liquid water content. Validation of such relationship is problematic using the C-FOG data due to the presence of rain and other factors. The parametrization with droplet number concentration only does not provide a robust visibility calculation since it cannot represent the effects of droplet size on visibility. Finally, a preliminary analysis of the mixed fog/rain case is presented to illustrate the nature of the problem to promote future research.

The Mean Single Molecule Rate (mSMR) in the Analysis of Fluorescence Fluctuations: Measurements on DNA Mixtures of Defined Composition - Lorenz T. Sparrenberg; Benjamin Greiner; Harald P. Mathis (Journal of Fluorescence, 2021)
We present a method for the evaluation of fluorescence fluctuations on the basis of Mandel’s Q parameter, using sampling time-dependent factorial cumulants. By relating the Q parameter to the sampling time, we obtain the mean single molecule rate (mSMR), an easy to interpret expression that provides both brightness and diffusion information. The model is suitable for the widely used confocal setups with single photon excitation and a single detection channel. We present a way to correct the mSMR for afterpulsing, dead time and background noise. To account for photokinetic effects at short sampling times, we expand the model by a simple on/off isomerization term, which is similar to the well-known triplet model. The functionality of the mSMR is shown using Monte Carlo simulations. The correction mechanisms and the experimental applicability of the model are then demonstrated by DNA measurements of defined composition. By systematically analyzing DNA mixtures, we can show that at large sampling times, the mSMR correctly describes the single molecule brightness rates and the diffusive properties of DNA molecules. At short sampling times, the photokinetic effects of isomerization are accurately described by the mSMR model. Since additionally the mSMR can easily be corrected for measurement artefacts such as detector dead time, afterpulsing and background noise, this is a valuable advantage over the standard method of fluorescence correlation spectroscopy.

Hot and cold flavors of southern California’s Santa Ana winds: their causes, trends, and links with wildfire - Alexander Gershunov; Janin Guzman Morales; Benjamin Hatchett; Kristen Guirguis; Rosana Aguilera; Tamara Shulgina; John T. Abatzoglou; Daniel Cayan; David Pierce; Park Williams; Ivory Small; Rachel Clemesha; et al. (Climate Dynamics, 2021)
Santa Ana winds (SAWs) are associated with anomalous temperatures in coastal Southern California (SoCal). As dry air flows over SoCal’s coastal ranges on its way from the elevated Great Basin down to sea level, all SAWs warm adiabatically. Many but not all SAWs produce coastal heat events. The strongest regionally averaged SAWs tend to be cold. In fact, some of the hottest and coldest observed temperatures in coastal SoCal are linked to SAWs. We show that hot and cold SAWs are produced by distinct synoptic dynamics. High-amplitude anticyclonic flow around a blocking high pressure aloft anchored at the California coast produces hot SAWs. Cold SAWs result from anticyclonic Rossby wave breaking over the northwestern U.S. Hot SAWs are preceded by warming in the Great Basin and dry conditions across the Southwestern U.S. Precipitation over the Southwest, including SoCal, and snow accumulation in the Great Basin usually precede cold SAWs. Both SAW flavors, but especially the hot SAWs, yield low relative humidity at the coast. Although cold SAWs tend to be associated with the strongest winds, hot SAWs tend to last longer and preferentially favor wildfire growth. Historically, out of large (> 100 acres) SAW-spread wildfires, 90% were associated with hot SAWs, accounting for 95% of burned area. As health impacts of SAW-driven coastal fall, winter and spring heat waves and impacts of smoke from wildfires have been recently identified, our results have implications for designing early warning systems. The long-term warming trend in coastal temperatures associated with SAWs is focused on January–March, when hot and cold SAW frequency and temperature intensity have been increasing and decreasing, respectively, over our 71-year record.

Host adaptation to novel pathogen introduction: Predicting conditions that promote evolutionary rescue - Benjamin D. Golas; Brandon Goodell; Colleen T. Webb (Ecology Letters, 2021)
Novel pathogen introduction can have drastic consequences for naive host populations, and outcomes can be difficult to predict. Evolutionary rescue (ER) provides a foundation for understanding whether hosts are driven to extinction or survive via adaptation. Currently, patterns of host population dynamics alongside evidence of adaptation are used to infer ER. However, the gap between established ER theory and complexity inherent in natural systems makes interpreting empirical patterns difficult because they can be confounded with ecological drivers of survival under current theory. To bridge this gap, we expand ER theory to include biological selective agents, such as pathogens. We find birth processes to be more important than previously theorised in determining ER potential. We employ a novel framework evaluating ER potential within natural systems and gain ability to identify system characteristics that make ER possible. Identifying these characteristics allows a shift from retrospective observation to a predictive mindset, and our findings suggest that ER occurrence may be more limited than previously thought. We use the plague system of Yersinia pestis infecting Cynomys ludovicianus (black‐tailed prairie dogs) and Spermophilus beecheyi (California ground squirrels) as a case study.

Effects of the glucocorticoid receptor antagonist PT150 on stress-induced fentanyl seeking in male and female rats - Lindsey R. Hammerslag; Emily D. Denehy; Benjamin Carper; Tracy L. Nolen; Mark A. Prendergast; Michael T. Bardo (Psychopharmacology, 2021)

Identifying Policy-relevant Indicators for Assessing Landscape Vegetation Patterns to Inform Planning and Management on Multiple-use Public Lands - Sarah K. Carter; L. E. Burris; Christopher T. Domschke; Steven L. Garman; Travis Haby; Benjamin R. Harms; E. Kachergis; S. E. Litschert; Kevin H. Miller (Environmental Management, 2021)
Understanding the structure and composition of landscapes can empower agencies to effectively manage public lands for multiple uses while sustaining land health. Many landscape metrics exist, but they are not often used in public land decision-making. Our objectives were to (1) develop and (2) apply a process for identifying a core set of indicators that public land managers can use to understand landscape-level resource patterns on and around public lands. We first developed a process for identifying indicators that are grounded in policy, feasible to quantify using existing data and resources, and useful for managers. We surveyed landscape monitoring efforts by other agencies, gathered science and agency input on monitoring goals, and quantified the prevalence of potential indicators in agency land health standards to identify five landscape indicators: amount, distribution, patch size, structural connectivity, and diversity of vegetation types. We then conducted pilot applications in four bureau of land management (BLM) field offices in Arizona, California, and Colorado to refine procedures for quantifying the indicators and assess the utility of the indicators for managers. Results highlighted the dominance of upland and the limited extent of riparian/wetland vegetation communities, moderate connectivity of priority vegetation patches, and lower diversity of native vegetation types on BLM compared to non-BLM lands. Agency staff can use the indicators to inform the development of quantitative resource management objectives in land use plans, evaluate progress in meeting those objectives, quantify potential impacts of proposed actions, and as a foundation for an all-lands approach to landscape-level management across public lands.

Occurrence of environmental contaminants (pesticides, herbicides, PAHs) in Australian/Queensland Apis mellifera honey - Natasha L. Hungerford; Mary T. Fletcher; Heng Hang Tsai; Darina Hnatko; Lorinda J. Swann; Cassandra L. Kelly; Shalona R. Anuj; Ujang Tinggi; Dennis C. Webber; Stephen T. Were; Benjamin L. L. Tan (Food Additives & Contaminants Part B-Surveillance, 2021)

Range edges of North American marine species are tracking temperature over decades - Alexa Fredston; Malin Pinsky; Rebecca L. Selden; Cody Szuwalski; James T. Thorson; Steven D. Gaines; Benjamin S. Halpern (Global Change Biology, 2021)
Understanding the dynamics of species range edges in the modern era is key to addressing fundamental biogeographic questions about abiotic and biotic drivers of species distributions. Range edges are where colonization and extirpation processes unfold, and so these dynamics are also important to understand for effective natural resource management and conservation. However, few studies to date have analyzed time series of range edge positions in the context of climate change, in part because range edges are difficult to detect. We first quantified positions for 165 range edges of marine fishes and invertebrates from three U.S. continental shelf regions using up to five decades of survey data and a spatiotemporal model to account for sampling and measurement variability. We then analyzed whether those range edges maintained their edge thermal niche—the temperatures found at the range edge position—over time. A large majority of range edges (88%) maintained either summer or winter temperature extremes at the range edge over the study period, and most maintained both (76%), although not all of those range edges shifted in space. However, we also found numerous range edges—particularly poleward edges and edges in the region that experienced the most warming—that did not shift at all, shifted further than predicted by temperature alone, or shifted opposite the direction expected, underscoring the multiplicity of factors that drive changes in range edge positions. This study suggests that range edges of temperate marine species have largely maintained the same edge thermal niche during periods of rapid change and provides a blueprint for testing whether and to what degree species range edges track temperature in general.

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Nikki Traylor-Knowles; Michael T. Connelly; Benjamin D. Young; Katherine Eaton; Erinn M. Muller; Valerie J. Paul; Blake Ushijima; Allyson DeMerlis; Melissa K. Drown; Ashley Goncalves; Nicholas Kron; Grace A. Snyder; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.

A panel of 96 SNPs to identify individuals and differentiate subspecies of elk (Cervus canadensis) for microfluidic and other genotyping platforms - Benjamin N. Sacks; Gunmeet K. Bali; Zachary T. Lounsberry; Stevi L. Vanderzwan (Conservation Genetics Resources, 2021)

Was historical cisco Coregonus artedi yield consistent with contemporary recruitment and abundance in Lake Superior? - Benjamin J. Rook; Michael J. Hansen; Cory A. Goldsworthy; Bradley A. Ray; Owen T. Gorman; Daniel L. Yule; Charles R. Bronte (Fisheries Management and Ecology, 2021)
Historically, cisco Coregonus artedi Lesueur was the predominant prey fish and target of commercial fisheries throughout Lake Superior, but most spawning stocks collapsed by the mid‐1900s. Stocks partially recovered by the early 1990s, but contemporary abundance is considered to be below historical levels and driven by intermittent recruitment. Stochastic, age‐structured simulation models were used to determine whether historical (pre‐1955) cisco yield in Lake Superior was consistent with contemporary (1992–2015) abundance, life‐history characteristics and recruitment dynamics. When compared to contemporary stocks, the findings suggest historical stocks had: (1) similar recruits per spawner at low spawning stock sizes; (2) lower rates of compensatory density dependence; (3) similar or lower recruitment variation depending on the area and (4) higher median adult and age‐1 density. These findings are consistent with the hypothesis that eutrophication during the historical period supported greater recruitment and adult abundance and that re‐oligotrophication during the contemporary period may be limiting full recovery.

A Dynamic Stress-Scape Framework to Evaluate Potential Effects of Multiple Environmental Stressors on Gulf of Alaska Juvenile Pacific Cod - Josiah Blaisdell; Hillary L. Thalmann; Willem Klajbor; Yue Zhang; Jessica A. Miller; Benjamin J. Laurel; Maria T. Kavanaugh (Frontiers in Marine Science, 2021)
Quantifying the spatial and temporal footprint of multiple environmental stressors on marine fisheries is imperative to understanding the effects of changing ocean conditions on living marine resources. Pacific Cod (Gadus macrocephalus) , an important marine species in the Gulf of Alaska ecosystem, has declined dramatically in recent years, likely in response to extreme environmental variability in the Gulf of Alaska related to anomalous marine heatwave conditions in 2014–2016 and 2019. Here, we evaluate the effects of two potential environmental stressors, temperature variability and ocean acidification, on the growth of juvenile Pacific Cod in the Gulf of Alaska using a novel machine-learning framework called “stress-scapes,” which applies the fundamentals of dynamic seascape classification to both environmental and biological data. Stress-scapes apply a probabilistic self-organizing map (prSOM) machine learning algorithm and Hierarchical Agglomerative Clustering (HAC) analysis to produce distinct, dynamic patches of the ocean that share similar environmental variability and Pacific Cod growth characteristics, preserve the topology of the underlying data, and are robust to non-linear biological patterns. We then compare stress-scape output classes to Pacific Cod growth rates in the field using otolith increment analysis. Our work successfully resolved five dynamic stress-scapes in the coastal Gulf of Alaska ecosystem from 2010 to 2016. We utilized stress-scapes to compare conditions during the 2014–2016 marine heatwave to cooler years immediately prior and found that the stress-scapes captured distinct heatwave and non-heatwave classes, which highlighted high juvenile Pacific Cod growth and anomalous environmental conditions during heatwave conditions. Dominant stress-scapes underestimated juvenile Pacific Cod growth across all study years when compared to otolith-derived field growth rates, highlighting the potential for selective mortality or biological parameters currently missing in the stress-scape model as well as differences in potential growth predicted by the stress-scape and realized growth observed in the field. A sensitivity analysis of the stress-scape classification result shows that including growth rate data in stress-scape classification adjusts the training of the prSOM, enabling it to distinguish between regions where elevated sea surface temperature is negatively impacting growth rates. Classifications that rely solely on environmental data fail to distinguish these regions. With their incorporation of environmental and non-linear physiological variables across a wide spatio-temporal scale, stress-scapes show promise as an emerging methodology for evaluating the response of marine fisheries to changing ocean conditions in any dynamic marine system where sufficient data are available.

Processing of Naturally Sourced Macroalgal- and Coral-Dissolved Organic Matter (DOM) by High and Low Microbial Abundance Encrusting Sponges - Sara Campana; Meggie Hudspith; David Lankes; Anna de Kluijver; Celine Demey; Jorien Schoorl; Samira Absalah; Marcel T. J. van der Meer; Benjamin Mueller; Jasper M. de Goeij (Frontiers in Marine Science, 2021)
Sponges play a key role in (re)cycling of dissolved organic matter (DOM) and inorganic nutrients in coral reef ecosystems. Macroalgae and corals release different quantities of DOM and at different bioavailabilities to sponges and their microbiome. Given the current coral- to algal-dominance shift on coral reefs, we assessed the differential processing of macroalgal- and coral-DOM by three high and three low microbial abundance (HMA and LMA) encrusting sponge species. We followed the assimilation of naturally sourced 13 C- and 15 N-enriched macroalgal- and coral-DOM into bulk tissue and into host- versus bacteria-specific phospholipid fatty acids (PLFAs). Additionally, we compared sponge-processing of the two natural DOM sources with 13 C- and 15 N-enriched laboratory-made diatom-DOM. All investigated sponges utilized all DOM sources, with higher assimilation rates in LMA compared to HMA sponges. No difference was found in carbon assimilation of coral- versus macroalgal-DOM into bulk tissue and host- versus bacteria-specific PLFAs, but macroalgal nitrogen was assimilated into bulk tissue up to eight times faster compared to the other sources, indicating its higher bioavailability to the sponges. Additionally, LMA sponges released significantly more inorganic nitrogen after feeding on macroalgal-DOM. Therefore, we hypothesize that, depending on the abundance and composition of the sponge community, sponges could catalyze reef eutrophication through increased turnover of nitrogen under coral-to-algal regime shifts.

A global reconnaissance of particulates and metals/metalloids in untreated drinking water sources - Jonathan W. Peterson; Benjamin M. Fry; Daniel R. Wade; Ford J. Fishman; Jacob T. Stid; Jonas M. Peterson; Cleveland E. Tarp; Randall D. Wade; Sarah A. Brokus; Michael J. Pikaart; Brent P. Krueger; Aaron A. Best (Environmental Monitoring and Assessment, 2021)
Metal and metalloid contamination in drinking water sources is a global concern, particularly in developing countries. This study used hollow membrane water filters and metal-capturing polyurethane foams to sample 71 drinking water sources in 22 different countries. Field sampling was performed with sampling kits prepared in the lab at Hope College in Holland, MI, USA. Filters and foams were sent back to the lab after sampling, and subsequent analysis of flushates and rinsates allowed the estimation of suspended solids and metal and other analayte concentrations in source waters. Estimated particulate concentrations were 0–92 mg/L, and consisted of quartz, feldspar, and clay, with some samples containing metal oxides or sulfide phases. As and Cu were the only analytes which occurred above the World Health Organization (WHO) guidelines of 10 μg/L and 2000 μg/L, respectively, with As exceeding the guideline in 45% of the sources and Cu in 3%. Except for one value of ~ 285 μg/L, As concentrations were 45–200 μg/L (river), 65–179 μg/L (well), and 112–178 μg/L (tap). Other metals (Ce, Fe, Mg, Mn, Zn) with no WHO guideline were also detected, with Mn the most common. This study demonstrated that filters and foams can be used for reconnaissance characterization of untreated drinking water. However, estimated metal and other analyte concentrations could only be reported as minimum values due to potential incomplete retrieval of foam-bound analytes. A qualitative reporting methodology was used to report analytes as “present” if the concentration was below the WHO guideline, and “present-recommend retesting” if the concentration was quantifiable and above the WHO guideline.

Correction to: Patterns and consequences of life history diversity in salinity exposure of an estuarine dependent fish - T. Reid Nelson; Crystal L. Hightower; Jeff Coogan; Benjamin D. Walther; Sean P. Powers (Environmental Biology of Fishes, 2021)
A Correction to this paper has been published: 10.1007/s10641-021-01096-6

Compromised root development constrains the establishment potential of native plants in unamended alkaline post-mining substrates - Adam T. Cross; Jason C. Stevens; Rohan Sadler; Benjamin Moreira-Grez; Dmitry Ivanov; Hongtao Zhong; Kingsley W. Dixon; Hans Lambers (Plant and Soil, 2021)

Resting fMRI-guided TMS results in subcortical and brain network modulation indexed by interleaved TMS/fMRI - Desmond J. Oathes; Jared P. Zimmerman; Romain Duprat; Seda S. Japp; Morgan Scully; Benjamin M. Rosenberg; Matthew W. Flounders; Hannah Long; Joseph A. Deluisi; Mark Elliott; Gavriella Shandler; Russell T. Shinohara; et al. (Experimental Brain Research, 2021)

Patterns and consequences of life history diversity in salinity exposure of an estuarine dependent fish - T. Reid Nelson; Crystal L. Hightower; Jeff Coogan; Benjamin D. Walther; Sean P. Powers (Environmental Biology of Fishes, 2021)
While it is common knowledge that Red Drum ( Sciaenops ocellatus ) inhabit oligohaline waters (salinity <5), lifetime reconstructions of salinity histories have been lacking, and this study provides unique insight into interannual and ontogenetic patterns of oligohaline occupancy by this economically valuable sportfish . Growth consequences of oligohaline exposure and the relationship of oligohaline residency with river discharge were also investigated. Oligohaline exposure varied most during years 2 and 3 of life. During this time, 22% ( n = 26/120 individuals) of Red Drum were oligohaline residents (≥ 90% of these years spent in oligohaline salinities), 34% ( n = 41) were meso-polyhaline residents (< 10% of years 2 and 3 spent in oligohaline waters), and 44% ( n = 53) spent time in both oligohaline and meso-polyhaline salinities. Trends in oligohaline residency match putative Red Drum life history. Oligohaline residents were present during years 1–6 of life; however, oligohaline residency peaked during the second year of life ( n = 37, 31%) and by year 7 no oligohaline residents remained. Growth of oligohaline resident Red Drum during years 2–3 of life was lower than non-resident fish. However, long-term growth consequences of oligohaline residency were not apparent. The proportion of oligohaline residents during years 2 or 3 of life was positively related to river discharge. This divergence in salinity residency by juvenile Red Drum demonstrates that life history diversity was present in this population and that oligohaline waters provided important nursery habitat for fish that successfully recruited to the adult population.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Tundra wildfire triggers sustained lateral nutrient loss in Alaskan Arctic - Benjamin W. Abbott; Adrian V. Rocha; Arial Shogren; Jay P. Zarnetske; Frances Iannucci; William B. Bowden; Samuel P. Bratsman; Leika Patch; Rachel Watts; Randy Fulweber; Rebecca J. Frei; Amanda M. Huebner; et al. (Global Change Biology, 2021)
Climate change is creating widespread ecosystem disturbance across the permafrost zone, including a rapid increase in the extent and severity of tundra wildfire. The expansion of this previously rare disturbance has unknown consequences for lateral nutrient flux from terrestrial to aquatic environments. Lateral loss of nutrients could reduce carbon uptake and slow recovery of already nutrient‐limited tundra ecosystems. To investigate the effects of tundra wildfire on lateral nutrient export, we analyzed water chemistry in and around the 10‐year‐old Anaktuvuk River fire scar in northern Alaska. We collected water samples from 21 burned and 21 unburned watersheds during snowmelt, at peak growing season, and after plant senescence in 2017 and 2018. After a decade of ecosystem recovery, aboveground biomass had recovered in burned watersheds, but overall carbon and nitrogen remained ~20% lower, and the active layer remained ~10% deeper. Despite lower organic matter stocks, dissolved organic nutrients were substantially elevated in burned watersheds, with higher flow‐weighted concentrations of organic carbon (25% higher), organic nitrogen (59% higher), organic phosphorus (65% higher), and organic sulfur (47% higher). Geochemical proxies indicated greater interaction with mineral soils in watersheds with surface subsidence, but optical analysis and isotopes suggested that recent plant growth, not mineral soil, was the main source of organic nutrients in burned watersheds. Burned and unburned watersheds had similar δ 15 N‐NO 3 − , indicating that exported nitrogen was of preburn origin (i.e., not recently fixed). Lateral nitrogen flux from burned watersheds was 2‐ to 10‐fold higher than rates of background nitrogen fixation and atmospheric deposition estimated in this area. These findings indicate that wildfire in Arctic tundra can destabilize nitrogen, phosphorus, and sulfur previously stored in permafrost via plant uptake and leaching. This plant‐mediated nutrient loss could exacerbate terrestrial nutrient limitation after disturbance or serve as an important nutrient release mechanism during succession.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Quantifying thermal exposure for migratory riverine species: Phenology of Chinook salmon populations predicts thermal stress - Alyssa M. FitzGerald; Sara N. John; Travis M. Apgar; Nathan J. Mantua; Benjamin T. Martin (Global Change Biology, 2021)
Migratory species are particularly vulnerable to climate change because habitat throughout their entire migration cycle must be suitable for the species to persist. For migratory species in rivers, predicting climate change impacts is especially difficult because there is a lack of spatially continuous and seasonally varying stream temperature data, habitat conditions can vary for an individual throughout its life cycle, and vulnerability can vary by life stage and season. To predict thermal impacts on migratory riverine populations, we first expanded a spatial stream network model to predict mean monthly temperature for 465,775 river km in the western U.S., and then applied simple yet plausible future stream temperature change scenarios. We then joined stream temperature predictions to 44,396 spatial observations and life‐stage‐specific phenology (timing) for 26 ecotypes (i.e., geographically distinct population groups expressing one of the four distinct seasonal migration patterns) of Chinook salmon ( Oncorhynchus tshawytscha ), a phenotypically diverse anadromous salmonid that is ecologically and economically important but declining throughout its range. Thermal stress, assessed for each life stage and ecotype based on federal criteria, was influenced by migration timing rather than latitude, elevation, or migration distance such that sympatric ecotypes often showed differential thermal exposure. Early‐migration phenotypes were especially vulnerable due to prolonged residency in inland streams during the summer. We evaluated the thermal suitability of 31,699 stream km which are currently blocked by dams to explore reintroduction above dams as an option to mitigate the negative effects of our warmer stream temperature scenarios. Our results showed that negative impacts of stream temperature warming can be offset for almost all ecotypes if formerly occupied habitat above dams is made available. Our approach of combining spatial distribution and phenology data with spatially explicit and temporally explicit temperature predictions enables researchers to examine thermal exposure of migrating populations that use seasonally varying habitats.

Global climatology of synoptically‐forced downslope winds - John T. Abatzoglou; Benjamin J. Hatchett; Paul Fox‐Hughes; Alexander Gershunov; Nicholas J. Nauslar (International Journal of Climatology, 2021)
Downslope winds are mesoscale mountain meteorological phenomena that contribute to localized temperature extremes and contribute to numerous societal and environmental impacts. Whereas previous studies have examined local downslope winds, no known efforts have attempted to identify and characterize meso‐ to synoptic‐scale downslope winds globally using a common approach. We use a conceptual model for downslope winds that employs cross‐barrier wind speed, near‐mountain top static stability, and downward vertical velocity using thresholds guided by a chronology of local downslope winds and meta‐analysis of downslope wind case studies. This approach was applied to ERA‐5 reanalysis during 1979–2018 to develop a global atlas of downslope winds. Downslope winds adhered to distinct geographic and seasonal patterns, with peak occurrence in north–south oriented midlatitude mountains in the winter hemisphere associated with strong cross‐mountain winds and stability. However, we identify numerous locations from the tropics to the high‐latitudes where downslope winds occur at least 60 days a year as a byproduct of the general circulation and local‐scale circulation interacting with topography. The four‐decade‐long data set is also used to examine statistical relationships between the occurrence of downslope winds and El Niño‐Southern Oscillation as well as long‐term trends in downslope wind occurrence.

High-Resolution Sampling of a Broad Marine Life Size Spectrum Reveals Differing Size- and Composition-Based Associations With Physical Oceanographic Structure - Adam T. Greer; John C. Lehrter; Benjamin M. Binder; Aditya R. Nayak; Ranjoy Barua; Ana E. Rice; Jonathan H. Cohen; Malcolm N. McFarland; Alexis Hagemeyer; Nicole D. Stockley; Kevin M. Boswell; Igor Shulman; et al. (Frontiers in Marine Science, 2020)
Observing multiple size classes of organisms, along with oceanographic properties and water mass origins, can improve our understanding of the drivers of aggregations, yet acquiring these measurements remains a fundamental challenge in biological oceanography. By deploying multiple biological sampling systems, from conventional bottle and net sampling to in situ imaging and acoustics, we describe the spatial patterns of different size classes of marine organisms (several microns to ∼10 cm) in relation to local and regional (m to km) physical oceanographic conditions on the Delaware continental shelf. The imaging and acoustic systems deployed included (in ascending order of target organism size) an imaging flow cytometer (CytoSense), a digital holographic imaging system (HOLOCAM), an In Situ Ichthyoplankton Imaging System (ISIIS, 2 cameras with different pixel resolutions), and multi-frequency acoustics (SIMRAD, 18 and 38 kHz). Spatial patterns generated by the different systems showed size-dependent aggregations and differing connections to horizontal and vertical salinity and temperature gradients that would not have been detected with traditional station-based sampling (∼9-km resolution). A direct comparison of the two ISIIS cameras showed composition and spatial patchiness changes that depended on the organism size, morphology, and camera pixel resolution. Large zooplankton near the surface, primarily composed of appendicularians and gelatinous organisms, tended to be more abundant offshore near the shelf break. This region was also associated with high phytoplankton biomass and higher overall organism abundances in the ISIIS, acoustics, and targeted net sampling. In contrast, the inshore region was dominated by hard-bodied zooplankton and had relatively low acoustic backscatter. The nets showed a community dominated by copepods, but they also showed high relative abundances of soft-bodied organisms in the offshore region where these organisms were quantified by the ISIIS. The HOLOCAM detected dense patches of ciliates that were too small to be captured in the nets or ISIIS imagery. This near-simultaneous deployment of different systems enables the description of the spatial patterns of different organism size classes, their spatial relation to potential prey and predators, and their association with specific oceanographic conditions. These datasets can also be used to evaluate the efficacy of sampling techniques, ultimately aiding in the design of efficient, hypothesis-driven sampling programs that incorporate these complementary technologies.

Detection and molecular characterization of rotavirus of pigs in Kerala, India - G. Logeshwaran; Chintu Ravishankar; D. Nandhakumar; Stephy Rose Sebastian; R. Rajasekhar; K. Sumod; Binu K. Mani; E. D. Benjamin; T. R. Jayakrishnan; Koshy John; M. Mini (VirusDisease, 2020)

Carotenoid availability and tradeoffs in female convict cichlids, a reverse sexually-dichromatic fish - Ryan L. Earley; Caleb T. Anderson; Michele K. Moscicki; Benjamin B. Norton; Alexandria C. Brown; Ethan D. Clotfelter (Environmental Biology of Fishes, 2020)

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

Modeling Impact of Intertidal Foreshore Evolution on Gravel Barrier Erosion and Wave Runup with XBeach-X - Benjamin T. Phillips; Jennifer M. Brown; Andrew J. Plater (Journal of Marine Science and Engineering, 2020)
This paper provides a sensitivity analysis around how characterizing sandy, intertidal foreshore evolution in XBeach-X impacts on wave runup and morphological change of a vulnerable, composite gravel beach. The study is motivated by a need for confidence in storm-impact modeling outputs to inform coastal management policy for composite beaches worldwide. First, the model is run with the sandy settings applied to capture changes in the intertidal foreshore, with the gravel barrier assigned as a non-erodible surface. Model runs were then repeated with the gravel settings applied to obtain wave runup and erosion of the barrier crest, updating the intertidal foreshore from the previous model outputs every 5, 10 and 15 min, and comparing this with a temporally static foreshore. Results show that the scenario with no foreshore evolution led to the highest wave runup and barrier erosion. The applied foreshore evolution setting update is shown to be a large control on the distribution of freeboard values indicative of overwash hazard and barrier erosion by causing an increase (with 5 min foreshore updates applied) or a decrease (with no applied foreshore updating) in the Iribarren number. Therefore, the sandy, intertidal component should not be neglected in gravel barrier modeling applications given the risk of over- or under-predicting the wave runup and barrier erosion.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Environmental influences on invertebrate diversity and community composition in the hyporheic zone ecotone in Texas, USA: contrasts between co-occurring epigean taxa and stygobionts - Benjamin T. Hutchins; Aaron P. Swink; Peter H. Diaz; Benjamin F. Schwartz (Hydrobiologia, 2020)

A new maximum size for the family Nomeidae and the third record of a longfin cigarfish, Cubiceps paradoxus (Stromateoidei: Nomeidae) from California, USA - Benjamin W. Frable; Merit H. Mccrea; Milton S. Love; Matthew T. Craig (Journal of Fish Biology, 2020)
We report the largest specimen from the stromateoid family Nomeidae. The specimen, measuring 1283 mm total length unpreserved, was caught on hook and line from shore in Port Hueneme, California, USA in June 2019. Despite scavenging damage, the specimen was identified as a longfin cigarfish, Cubiceps paradoxus, using morphological characters and molecular techniques. This is the third record of C. paradoxus from California. We also provide an account of a previously unreported C. paradoxus collected off the US‐Mexico Border in 1999 that was examined but not preserved.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Secretive Marsh Bird Densities and Habitat Associations in the Prairie Pothole Region - Joseph T. Orr; Cameron A. Duquette; Torre J. Hovick; Benjamin A. Geaumont; Tyler M. Harms (Wetlands, 2020)

Establishment of long-term ostracod epidermal culture - Siân R. Morgan; Laura Paletto; Benjamin Rumney; Farhana T. Malik; Nick White; Philip N. Lewis; Andrew R. Parker; Simon Holden; Keith M. Meek; Julie Albon (In Vitro Cellular & Developmental Biology - Animal, 2020)
Primary crustacean cell culture was introduced in the 1960s, but to date limited cell lines have been established. Skogsbergia lerneri is a myodocopid ostracod, which has a body enclosed within a thin, durable, transparent bivalved carapace, through which the eye can see. The epidermal layer lines the inner surface of the carapace and is responsible for carapace synthesis. The purpose of the present study was to develop an in vitro epidermal tissue and cell culture method for S. lerneri . First, an optimal environment for the viability of this epidermal tissue was ascertained, while maintaining its cell proliferative capacity. Next, a microdissection technique to remove the epidermal layer for explant culture was established and finally, a cell dissociation method for epidermal cell culture was determined. Maintenance of sterility, cell viability and proliferation were key throughout these processes. This novel approach for viable S. lerneri epidermal tissue and cell culture augments our understanding of crustacean cell biology and the complex biosynthesis of the ostracod carapace. In addition, these techniques have great potential in the fields of biomaterial manufacture, the military and fisheries, for example, in vitro toxicity testing.

Patterns of multi-domain cognitive aging in participants of the Long Life Family Study - Paola Sebastiani; Stacy L. Andersen; Benjamin Sweigart; Mengtian Du; Stephanie Cosentino; Bharat Thyagarajan; Kaare Christensen; Nicole Schupf; Thomas T Perls (GeroScience, 2020)

Simulation of stratified flows over a ridge using a lattice Boltzmann model - Yansen Wang; Benjamin T. MacCall; Christopher M. Hocut; Xiping Zeng; Harindra J. S. Fernando (Environmental Fluid Mechanics, 2020)
A three-dimensional thermal lattice Boltzmann model (TLBM) using multi-relaxation time method was used to simulate stratified atmospheric flows over a ridge. The main objective was to study the efficacy of this method for turbulent flows in the atmospheric boundary layer, complex terrain flows in particular. The simulation results were compared with results obtained using a traditional finite difference method based on the Navier–Stokes equations and with previous laboratory results on stably stratified flows over an isolated ridge. The initial density profile is neutral stratification in the boundary layer, topped with a stable cap and stable stratification aloft. The TLBM simulations produced waves, rotors, and hydraulic jumps in the lee side of the ridge for stably stratified flows, depending on the governing stability parameters. The Smagorinsky turbulence parameterization produced typical turbulence spectra for the velocity components at the lee side of the ridge, and the turbulent flow characteristics of varied stratifications were also analyzed. The comparison of TLBM simulations with other numerical simulations and laboratory studies indicated that TLBM is a viable method for numerical modeling of stratified atmospheric flows. To our knowledge, this is the first TLBM simulation of stratified atmospheric flow over a ridge. The details of the TLBM, its implementation of complex boundaries and the subgrid turbulence parameterizations used in this study are also described in this article.

Oceanic sediment accumulation rates predicted via machine learning algorithm: towards sediment characterization on a global scale - Giancarlo A. Restreppo; Warren T. Wood; Benjamin J. Phrampus (Geo-Marine Letters, 2020)
Observed vertical sediment accumulation rates ( n = 1031) were gathered from ~ 55 years of peer reviewed literature. Original methods of rate calculation include long-term isotope geochronology ( 14 C, 210 Pb, and 137 Cs), pollen analysis, horizon markers, and box coring. These observations are used to create a database of global, contemporary vertical sediment accumulation rates. Rates were converted to cm year −1 , paired with the observation’s longitude and latitude, and placed into a machine learning–based Global Predictive Seabed Model (GPSM). GPSM finds correlations between the data and established global “predictors” (quantities known or estimable everywhere, e.g., distance from coastline and river mouths). The result, using a k-nearest neighbor (k-NN) algorithm, is a 5-arc-minute global map of predicted benthic vertical sediment accumulation rates. The map generated provides a global reference for vertical sedimentation from coastal to abyssal depths. Areas of highest sedimentation, ~ 3–8 cm year −1 , are generally river mouth proximal coastal zones draining relatively large areas with high maximum elevations and with wide, shallow continental shelves (e.g., the Gulf of Mexico and the Amazon Delta), with rates falling exponentially towards the deepest parts of the oceans. The exception is Oceania, which displays significant vertical sedimentation over a large area without draining the large drainage basins seen in other regions. Coastal zones with relatively small drainage basins and steep shelves display vertical sedimentation of ~ 1 cm year −1 , which is limited to the near shore when compared with shallow, wide margins (e.g., the western coasts of North and South America). Abyssal depth rates are functionally zero at the time scale examined (~ 10 −4 cm year −1 ) and increase one order of magnitude near the Mid-Atlantic Ridge and at the Galapagos Triple Junction.

Effects of an experimental increase in flow intermittency on an alpine stream - Andre R. Siebers; Amael Paillex; Benjamin Misteli; Christopher T. Robinson (Hydrobiologia, 2020)

Association of γ-aminobutyric acid and glutamate/glutamine in the lateral prefrontal cortex with patterns of intrinsic functional connectivity in adults - Kai Wang; Harry R. Smolker; Mark S. Brown; Hannah R. Snyder; Benjamin L. Hankin; Marie T. Banich (Brain Structure and Function, 2020)

Towards Spatially Explicit Quantification of Pre- and Postfire Fuels and Fuel Consumption from Traditional and Point Cloud Measurements - Andrew T Hudak; Akira Kato; Benjamin C Bright; E Louise Loudermilk; Christie Hawley; Joseph C Restaino; Roger D Ottmar; Gabriel A Prata; Carlos Cabo; Susan J Prichard; Eric M Rowell; David R Weise (Forest Science, 2020)
Methods to accurately estimate spatially explicit fuel consumption are needed because consumption relates directly to fire behavior, effects, and smoke emissions. Our objective was to quantify sparkleberry (Vaccinium arboretum Marshall) shrub fuels before and after six experimental prescribed fires at Fort Jackson in South Carolina. We used a novel approach to characterize shrubs non-destructively from three-dimensional (3D) point cloud data collected with a terrestrial laser scanner. The point cloud data were reduced to 0.001 m–3 voxels that were either occupied to indicate fuel presence or empty to indicate fuel absence. The density of occupied voxels was related significantly by a logarithmic function to 3D fuel bulk density samples that were destructively harvested (adjusted R2 = .32, P < .0001). Based on our findings, a survey-grade Global Navigation Satellite System may be necessary to accurately associate 3D point cloud data to 3D fuel bulk density measurements destructively collected in small (submeter) shrub plots. A recommendation for future research is to accurately geolocate and quantify the occupied volume of entire shrubs as 3D objects that can be used to train models to map shrub fuel bulk density from point cloud data binned to occupied 3D voxels.

The influence of species abundance, diet and phylogenetic affinity on the co-occurrence of butterflyfishes - Lucas T. Nunes; Alexandre C. Siqueira; Isadora Cord; Benjamin M. Ford; Ana M. R. Liedke; Carlos E. L. Ferreira; Sergio R. Floeter (Marine Biology, 2020)

The Sibalaya flowslide initiated by the 28 September 2018 MW 7.5 Palu-Donggala, Indonesia earthquake - Aaron P. Gallant; Jack Montgomery; H. Benjamin Mason; Daniel Hutabarat; A. Nicole Reed; Joseph Wartman; Masyhur Irsyam; Pintor T. Simatupang; Idrus M. Alatas; Widjojo A. Prakoso; Didiek Djarwadi; Rahma Hanifa; et al. (Landslides, 2020)

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

High water use in desert plants exposed to extreme heat - Luiza M. T. Aparecido; Sabrina Woo; Crystal Suazo; Kevin R. Hultine; Benjamin Blonder (Ecology Letters, 2020)
Many plant water use models predict leaves maximize carbon assimilation while minimizing water loss via transpiration. Alternate scenarios may occur at high temperature, including heat avoidance, where leaves increase water loss to evaporatively cool regardless of carbon uptake; or heat failure, where leaves non‐adaptively lose water also regardless of carbon uptake. We hypothesized that these alternative scenarios are common in species exposed to hot environments, with heat avoidance more common in species with high construction cost leaves. Diurnal measurements of leaf temperature and gas exchange for 11 Sonoran Desert species revealed that 37% of these species increased transpiration in the absence of increased carbon uptake. High leaf mass per area partially predicted this behaviour ( r 2 = 0.39). These data are consistent with heat avoidance and heat failure, but failure is less likely given the ecological dominance of the focal species. These behaviours are not yet captured in any extant plant water use model.

Physiological responses during simulated 16 km recumbent handcycling time trial and determinants of performance in trained handcyclists - Benjamin Stone; Barry S. Mason; Ben T. Stephenson; Vicky L. Goosey-Tolfrey (European Journal of Applied Physiology, 2020)
Purpose To characterise the physiological profiles of trained handcyclists, during recumbent handcycling, to describe the physiological responses during a 16 km time trial (TT) and to identify the determinants of this TT performance. Methods Eleven male handcyclists performed a sub-maximal and maximal incremental exercise test in their recumbent handbike, attached to a Cyclus II ergometer. A physiological profile, including peak aerobic power output (PO Peak ), peak rate of oxygen uptake ( $$\dot{V}$$ V ˙ O 2Peak ), aerobic lactate threshold (AeLT) and PO at 4 mmol L −1 (PO 4 ), were determined. Participants also completed a 16 km simulated TT using the same experimental set-up. Determinants of TT performance were identified using stepwise multiple linear regression analysis. Results Mean values of PO Peak = 252 ± 9 W, $$\dot{V}$$ V ˙ O 2Peak = 3.30 ± 0.36 L min −1 (47.0 ± 6.8 mL kg −1 min −1 ), AeLT = 87 ± 13 W and PO 4 = 154 ± 14 W were recorded. The TT was completed in 29:21 ± 0:59 min:s at an intensity equivalent to 69 ± 4% PO Peak and 87 ± 5% $$\dot{V}$$ V ˙ O 2Peak . PO Peak ( r = − 0.77, P = 0.006), PO 4 ( r = − 0.77, P = 0.006) and AeLT ( r = − 0.68, P = 0.022) were significantly correlated with TT performance. PO 4 and PO Peak were identified as the best predictors of TT performance ( r = 0.89, P < 0.001). Conclusion PO Peak , PO 4 and AeLT are important physiological TT performance determinants in trained handcyclists, differentiating between superior and inferior performance, whereas $$\dot{V}$$ V ˙ O 2peak was not. The TT took place at an intensity corresponding to 69% PO Peak and 87% $$\dot{V}$$ V ˙ O 2peak .

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Projected changes in extreme precipitation intensity and dry spell length in Côte d’Ivoire under future climates - Assi Louis Martial Yapo; Adama Diawara; Benjamin K. Kouassi; Fidèle Yoroba; Mouhamadou Bamba Sylla; Kouakou Kouadio; Dro T. Tiémoko; Dianikoura Ibrahim Koné; Elisée Y. Akobé; Kouassi P. A. T. Yao (Theoretical and Applied Climatology, 2020)

Breast brain metastases are associated with increased risk of leptomeningeal disease after stereotactic radiosurgery: a systematic review and meta-analysis - Desmond A. Brown; Victor M. Lu; Benjamin T. Himes; Terry C. Burns; Alfredo Quiñones-Hinojosa; Kaisorn L. Chaichana; Ian F. Parney (Clinical & Experimental Metastasis, 2020)

Streambank topography: an accuracy assessment of UAV-based and traditional 3D reconstructions - Benjamin U. Meinen; Derek T. Robinson (International Journal of Remote Sensing, 2020)

Rapid culture-based identification of Shiga toxin-producing Escherichia coli and Shigella spp./Enteroinvasive E. coli using the eazyplex® EHEC complete assay - Anika Penzel; Katrin Schützler; Jana Dröge; Alexander Mellmann; Ralf Ehricht; Ines Engelmann; Sascha D. Braun; Benjamin T. Schleenvoigt; Bettina Löffler; Jürgen Rödel (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Caveat consumptor notitia museo : Let the museum data user beware - Jeffrey C. Nekola; Benjamin T. Hutchins; Alison Schofield; Briante Najev; Kathryn E. Perez (Global Ecology and Biogeography, 2019)
Issue Lot accession information from natural history collections represents a potentially vital source of large datasets to test biodiversity, biogeography and macroecology hypotheses. But does such information provide an accurate portrayal of the natural world? We review the many types of bias and error intrinsic to museum collection data and consider how these factors may affect their ability to accurately test ecological hypotheses. Evidence We considered all Texas land snail collections from the two major repositories in the state and compared them with an ecological sample drawn across the same landscape. We found that museum collection localities were biased in favour of regions with higher human population densities and iconic destinations. They also tended to be made during attractive temporal windows. Small, uncharismatic taxa tended to be under‐collected while larger, charismatic species were over‐collected. As a result, for most species it was impossible to use museum lot frequency to accurately predict frequency and abundance in an ecological sample. Species misidentification rate was approximately 20%, while 4% of lots represented more than one species. Errors were spread across the entire shell size spectrum and were present in 75% of taxonomic families. Contingency table analysis documented significant dependence of both misidentification and mixed lot rates upon shell size and family richness. Conclusion Researchers should limit their use of museum record data to situations where their inherent biases and errors are irrelevant, rectifiable or explicitly considered. At the same time museums should begin incorporating expert specimen verification into their digitization programs.

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Functional neuroanatomy of the human eye movement network: a review and atlas - Benjamin Coiner; Hong Pan; Monica L. Bennett; Yelena G. Bodien; Swathi Iyer; Therese M. O’Neil-Pirozzi; Lorene Leung; Joseph T. Giacino; Emily Stern (Brain Structure and Function, 2019)

Microbial responses to warming enhance soil carbon loss following translocation across a tropical forest elevation gradient - Andrew T. Nottingham; Jeanette Whitaker; Nick J. Ostle; Richard D. Bardgett; Niall P. McNamara; Noah Fierer; Norma Salinas; Adan J. Q. Ccahuana; Benjamin L. Turner; Patrick Meir (Ecology Letters, 2019)
Tropical soils contain huge carbon stocks, which climate warming is projected to reduce by stimulating organic matter decomposition, creating a positive feedback that will promote further warming. Models predict that the loss of carbon from warming soils will be mediated by microbial physiology, but no empirical data are available on the response of soil carbon and microbial physiology to warming in tropical forests, which dominate the terrestrial carbon cycle. Here we show that warming caused a considerable loss of soil carbon that was enhanced by associated changes in microbial physiology. By translocating soils across a 3000 m elevation gradient in tropical forest, equivalent to a temperature change of ± 15 °C, we found that soil carbon declined over 5 years by 4% in response to each 1 °C increase in temperature. The total loss of carbon was related to its original quantity and lability, and was enhanced by changes in microbial physiology including increased microbial carbon‐use‐efficiency, shifts in community composition towards microbial taxa associated with warmer temperatures, and increased activity of hydrolytic enzymes. These findings suggest that microbial feedbacks will cause considerable loss of carbon from tropical forest soils in response to predicted climatic warming this century.

The threat of energy diversification to a bioregion: a landscape-level analysis of current and future impacts on the US Chihuahuan Desert - Maureen R. McClung; Nathan T. Taylor; Benjamin K. Zamzow; E. Taylor Stone; Helena Abad; Matthew D. Moran (Regional Environmental Change, 2019)

Development and application of a low-cost rapid assessment system for coastal benthic habitats - Caryl S. Benjamin; Patrick Lawrence P. Cadeliña; Aletta T. Yñiguez; Cesar L. Villanoy (Environmental Monitoring and Assessment, 2019)

Health-Related Quality of Life Following Concussion in Collegiate Student-Athletes With and Without Concussion History - M. L. Weber; R. C. Lynall; N. L. Hoffman; E. H. Miller; T. W. Kaminski; T. A. Buckley; H. J. Benjamin; C. M. Miles; C. T. Whitlow; L. Lintner; S. P. Broglio; M. McCrea; et al. (Annals of Biomedical Engineering, 2019)

Climate and plant trait strategies determine tree carbon allocation to leaves and mediate future forest productivity - Anna T. Trugman; Leander D. L. Anderegg; Brett T. Wolfe; Benjamin Birami; Nadine K. Ruehr; Matteo Detto; Megan K. Bartlett; William R. L. Anderegg (Global Change Biology, 2019)
Forest leaf area has enormous leverage on the carbon cycle because it mediates both forest productivity and resilience to climate extremes. Despite widespread evidence that trees are capable of adjusting to changes in environment across both space and time through modifying carbon allocation to leaves, many vegetation models use fixed carbon allocation schemes independent of environment, which introduces large uncertainties into predictions of future forest responses to atmospheric CO 2 fertilization and anthropogenic climate change. Here, we develop an optimization‐based model, whereby tree carbon allocation to leaves is an emergent property of environment and plant hydraulic traits. Using a combination of meta‐analysis, observational datasets, and model predictions, we find strong evidence that optimal hydraulic–carbon coupling explains observed patterns in leaf allocation across large environmental and CO 2 concentration gradients. Furthermore, testing the sensitivity of leaf allocation strategy to a diversity in hydraulic and economic spectrum physiological traits, we show that plant hydraulic traits in particular have an enormous impact on the global change response of forest leaf area. Our results provide a rigorous theoretical underpinning for improving carbon cycle predictions through advancing model predictions of leaf area, and underscore that tree‐level carbon allocation to leaves should be derived from first principles using mechanistic plant hydraulic processes in the next generation of vegetation models.

High-resolution mapping of rachis nodes per rachis, a critical determinant of grain yield components in wheat - Kai P. Voss-Fels; Gabriel Keeble-Gagnère; Lee T. Hickey; Josquin Tibbits; Sergej Nagornyy; Matthew J. Hayden; Raj K. Pasam; Surya Kant; Wolfgang Friedt; Rod J. Snowdon; Rudi Appels; Benjamin Wittkop (Theoretical and Applied Genetics, 2019)

Cost-effectiveness of patient navigation for breast cancer screening in the National Breast and Cervical Cancer Early Detection Program - Benjamin T. Allaire; Donatus Ekweme; Thomas J. Hoerger; Amy DeGroff; Sun Hee Rim; Sujha Subramanian; Jacqueline W. Miller (Cancer Causes & Control, 2019)

Recent colonization and expansion through the Lesser Sundas by seven amphibian and reptile species - Sean B. Reilly; Alexander L. Stubbs; Benjamin R. Karin; Evy Arida; Djoko T. Iskandar; Jimmy A. McGuire (Zoologica Scripta, 2019)
The Lesser Sundas Archipelago is comprised of two parallel chains of islands that extend between the Asian continental shelf (Sundaland) and Australo‐Papuan continental shelf (Sahul). These islands have served as stepping stones for taxa dispersing between the Asian and Australo‐Papuan biogeographical realms. While the oceanic barriers have prevented many species from colonizing the archipelago, a number of terrestrial vertebrate species have colonized the islands either by rafting/swimming or by human introduction. Here, we examine phylogeographic structure within the Lesser Sundas for three snake, two lizard and two frog species that each has a Sunda Shelf origin. These species are suspected to have recently colonized the archipelago, though all have inhabited the Lesser Sundas for over 100 years. We sequenced mtDNA from 231 samples to test whether there is sufficiently deep genetic structure within any of these taxa to reject human‐mediated introduction. Additionally, we tested for genetic signatures of population expansion consistent with recent introduction and estimated the ages of Lesser Sundas clades, if any exist. Our results show little to no genetic structure between populations on different islands in five species and moderate structure in two species. Nucleotide diversity is low for all species, and the ages of the most recent common ancestor for species with monophyletic Lesser Sundas lineages date to the Holocene or late Pleistocene. These results support the hypothesis that these species entered the archipelago relatively recently and either naturally colonized or were introduced by humans to most of the larger islands in the archipelago within a short time span.

A meta‐analysis of fish behavioural reaction to underwater human presence - Diogo S. M. Samia; Eduardo Bessa; Daniel T. Blumstein; José A. C. C. Nunes; Ernesto Azzurro; Lorenzo Morroni; Valerio Sbragaglia; Fraser A. Januchowski‐Hartley; Benjamin Geffroy (Fish and Fisheries, 2019)
In an increasingly anthropic world, humans have profound impacts on the distribution and behaviour of marine fishes. The increased human presence has modified fishes’ antipredator behavioural responses, and consequently flight decisions, as a function of their changed perceptions of risk. Understanding how fish react to human presence can help identify the most vulnerable functional groups/species and estimate impacts caused by human disturbance. Shoal and body size are known to influence fish flight initiation distance (FID; the distance between the predator and prey when the prey begins to escape); however, few studies attempt to test the moderators of these relationships. Here, we present a comprehensive meta‐analysis evaluating FID of fish in response to human presence. Specifically, we investigated six candidate moderators that could influence the relationship between FID with shoal and body size. Our results showed that individual fish size was strongly and positively correlated with FID and the most important moderator that explained the variance in individual body size‐FID relationship was shoaling behaviour. However, and somehow surprisingly, we detected no significant relationship between shoal size and FID. We discuss how these results can inform the development of fish conservation strategies and ultimately assist in the management of marine protected areas.

A Framework for the Development, Design and Implementation of a Sustained Arctic Ocean Observing System - Craig M. Lee; Sandy Starkweather; Hajo Eicken; Mary-Louise Timmermans; Jeremy Wilkinson; Stein Sandven; Dmitry Dukhovskoy; Sebastian Gerland; Jacqueline Grebmeier; Janet M. Intrieri; Sung-Ho Kang; Molly McCammon; et al. (Frontiers in Marine Science, 2019)

Cost-effectiveness of breast cancer screening in the National Breast and Cervical Cancer Early Detection Program - Sun Hee Rim; Benjamin T. Allaire; Donatus U. Ekwueme; Jacqueline W. Miller; Sujha Subramanian; Ingrid J. Hall; Thomas J. Hoerger (Cancer Causes & Control, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Thirty years of change and the future of Alaskan fisheries: Shifts in fishing participation and diversification in response to environmental, regulatory and economic pressures - Anne H. Beaudreau; Eric J. Ward; Richard E. Brenner; Andrew O. Shelton; Jordan T. Watson; Jennifer C. Womack; Sean C. Anderson; Alan C. Haynie; Kristin N. Marshall; Benjamin C. Williams (Fish and Fisheries, 2019)
Heterogeneity in human responses and decision‐making can contribute to the resilience of social–ecological systems in the face of environmental, political and economic pressures. In fishery systems worldwide, the ability of harvesters to maintain a diverse portfolio of fishing strategies is important for building adaptive capacity. We used a case‐study approach to examine the complexity of factors that inhibit or promote diversification in fisheries of Alaska, one of the major fishing regions of the world. Through a combination of harvest records and literature review, we explored shifts in participation and portfolio diversity in Alaskan fisheries over three decades. The four case‐studies examined the responses of fishers, fleets and communities to multiple, intersecting pressures, including biological declines, market and price dynamics, fishery privatization and the 1989 Exxon Valdez oil spill. These cases illustrate how stressors acting at multiple scales can encourage or constrain opportunities for diversification, and that these opportunities may be spread inequitably across participants. Overall, we found evidence for reduced participation and increasing specialization in Alaskan commercial fisheries. While numerous factors explain these trends, policies like individual quota systems and the increasing cost of entry into fisheries are forcing consolidation at local to regional scales. A portfolio approach to managing fisheries that reduces barriers to diversification and includes broad representation of resource users and communities in management may help to maintain opportunity and choice for fishers.

Cerebellar Theta Frequency Transcranial Pulsed Stimulation Increases Frontal Theta Oscillations in Patients with Schizophrenia - Arun Singh; Nicholas T. Trapp; Benjamin De Corte; Scarlett Cao; Johnathon Kingyon; Aaron D. Boes; Krystal L. Parker (The Cerebellum, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Modeling Temperature Regime and Physical Habitat Impacts from Restored Streamflow - Russell T. Bair; Benjamin W. Tobin; Brian D. Healy; Claire E. Spangenberg; Hampton K. Childres; Edward R. Schenk (Environmental Management, 2019)

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

The mutual interplay between calcification and coccolithovirus infection - Christopher T. Johns; Austin R. Grubb; Jozef I. Nissimov; Frank Natale; Viki Knapp; Alwin Mui; Helen F. Fredricks; Benjamin A. S. Van Mooy; Kay D. Bidle (Environmental Microbiology, 2019)
Summary Two prominent characteristics of marine coccolithophores are their secretion of coccoliths and their susceptibility to infection by coccolithoviruses (EhVs), both of which display variation among cells in culture and in natural populations. We examined the impact of calcification on infection by challenging a variety of Emiliania huxleyi strains at different calcification states with EhVs of different virulence. Reduced cellular calcification was associated with increased infection and EhV production, even though calcified cells and associated coccoliths had significantly higher adsorption coefficients than non‐calcified (naked) cells. Sialic acid glycosphingolipids, molecules thought to mediate EhV infection, were generally more abundant in calcified cells and enriched in purified, sorted coccoliths, suggesting a biochemical link between calcification and adsorption rates. In turn, viable EhVs impacted cellular calcification absent of lysis by inducing dramatic shifts in optical side scatter signals and a massive release of detached coccoliths in a subpopulation of cells, which could be triggered by resuspension of healthy, calcified host cells in an EhV‐free, ‘induced media’. Our findings show that calcification is a key component of the E. huxleyi ‐EhV arms race and an aspect that is critical both to the modelling of these host–virus interactions in the ocean and interpreting their impact on the global carbon cycle.

Cultures of Gossypium barbadense cotton ovules offer insights into the microtubule-mediated control of fiber cell expansion - Ethan T. Pierce; Benjamin P. Graham; Michael R. Stiff; Jason A. Osborne; Candace H. Haigler (Planta, 2019)

Effect of range of heading differences on human visual–inertial heading estimation - Raul Rodriguez; Benjamin T. Crane (Experimental Brain Research, 2019)

Genetic and Environmental Contributions to Variation in the Posterior Communicating Collaterals of the Circle of Willis - James E. Faber; Hua Zhang; Wojciech Rzechorzek; Kathy Z. Dai; Benjamin T. Summers; Cooper Blazek; Samuel J. Hedges (Translational Stroke Research, 2019)

Multi-gene panel testing confirms phenotypic variability in MUTYH-Associated Polyposis - Erin G. Sutcliffe; Amanda Bartenbaker Thompson; Amy R. Stettner; Megan L. Marshall; Maegan E. Roberts; Lisa R. Susswein; Ying Wang; Rachel T. Klein; Kathleen S. Hruska; Benjamin D. Solomon (Familial Cancer, 2019)

Leap‐frog dispersal and mitochondrial introgression: Phylogenomics and biogeography of Limnonectes fanged frogs in the Lesser Sundas Archipelago of Wallacea - Sean B. Reilly; Alexander L. Stubbs; Benjamin R. Karin; Ke Bi; Evy Arida; Djoko T. Iskandar; Jimmy A. McGuire (Journal of Biogeography, 2019)
Aim The Lesser Sunda Islands are situated between the Sunda and Sahul Shelves, with a linear arrangement that has functioned as a two‐way filter for taxa dispersing between the Asian and Australo‐Papuan biogeographical realms. Distributional patterns of many terrestrial vertebrates suggest a stepping‐stone model of island colonization. Here we investigate the timing and sequence of island colonization in Asian‐origin fanged frogs from the volcanic Sunda Arc islands with the goal of testing the stepping‐stone model of island colonization. Location The Indonesian islands of Java, Lombok, Sumbawa, Flores and Lembata. Taxon Limnonectes dammermani and L. kadarsani (Family: Dicroglossidae) Methods Mitochondrial DNA was sequenced from 153 frogs to identify major lineages and to select samples for an exon‐capture experiment. We designed probes to capture sequence data from 974 exonic loci (1,235,981 bp) from 48 frogs including the outgroup species, L. microdiscus . The resulting data were analysed using phylogenetic, population genetic and biogeographical model testing methods. Results The mt DNA phylogeny finds L. kadarsani paraphyletic with respect to L. dammermani , with a pectinate topology consistent with the stepping‐stone model. Phylogenomic analyses of 974 exons recovered the two species as monophyletic sister taxa that diverged ~7.6 Ma with no detectable contemporary gene flow, suggesting introgression of the L. dammermani mitochondrion into L. kadarsani on Lombok resulting from an isolated ancient hybridization event ~4 Ma. Within L. kadarsani, the Lombok lineage diverged first while the Sumbawa and Lembata lineages are nested within a Flores assemblage composed of two parapatrically distributed lineages meeting in central Flores. Biogeographical model comparison found strict stepping‐stone dispersal to be less likely than models involving leap‐frog dispersal events. Main conclusions These results suggest that the currently accepted stepping‐stone model of island colonization might not best explain the current patterns of diversity in the archipelago. The high degree of genetic structure, large divergence times, and absent or low levels of migration between lineages suggests that L. kadarsani represents five distinct species.

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

Biogeochemical recuperation of lowland tropical forest during succession - Benjamin W. Sullivan; Rachel L. DuBose; Megan K. Nasto; Silvia Alvarez‐Clare; Camie M. Dencker; Fiona M. Soper; Kevin T. Shoemaker; F. Yoko Ishida; Joana Zaragoza‐Castells; Eric A. Davidson; Cory C. Cleveland (Ecology, 2019)
High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest establishment. Biogeochemical theory and results from individual studies suggest that N can recuperate during secondary forest recovery, especially relative to P. Here, we synthesized 23 metrics of N and P in soil and plants from 45 secondary forest chronosequences located in the wet tropics to empirically explore (1) whether there is a consistent change in nutrients and nutrient cycling processes during secondary succession in the biome; (2) which metrics of N and P in soil and plants recuperate most consistently; (3) if the recuperation of nutrients during succession approaches similar nutrient concentrations and fluxes as those in mature forest in ~100 yr following the initiation of succession; and (4) whether site characteristics, including disturbance history, climate, and soil order are significantly related to nutrient recuperation. During secondary forest succession, nine metrics of N and/or P cycling changed consistently and substantially. In most sites, N concentrations and fluxes in both plants and soil increased during secondary succession, and total P concentrations increased in surface soil. Changes in nutrient concentrations and nutrient cycling processes during secondary succession were similar whether mature forest was included or excluded from the analysis, indicating that nutrient recuperation in secondary forest leads to biogeochemical conditions that are similar to those of mature forest. Further, of the N and P metrics that recuperated, only soil total P and foliar δ 15 N were strongly influenced by site characteristics like climate, soils, or disturbance history. Predictable nutrient recuperation across a diverse and productive ecosystem may support future forest growth and could provide a means to quantify successful restoration of ecosystem function in secondary tropical forest beyond biomass or species composition.

The poleward shift of South Atlantic Convergence Zone in recent decades - Marcia T. Zilli; Leila M. V. Carvalho; Benjamin R. Lintner (Climate Dynamics, 2019)

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

DNA Binding and Molecular Dynamic Studies of Polycyclic Tetramate Macrolactams (PTM) with Potential Anticancer Activity Isolated from a Sponge-Associated Streptomyces zhaozhouensis subsp. mycale subsp. nov. - M. Dhaneesha; O. Hasin; K. C. Sivakumar; R. Ravinesh; C. Benjamin Naman; S. Carmeli; T. P. Sajeevan (Marine Biotechnology, 2019)

Attenuation of cocaine seeking in rats via enhancement of infralimbic cortical activity using stable step-function opsins - Victória A. Müller Ewald; Benjamin J. De Corte; Subhash C. Gupta; Katherine V. Lillis; Nandakumar S. Narayanan; John A. Wemmie; Ryan T. LaLumiere (Psychopharmacology, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Decline in Ecosystem δ13C and Mid-Successional Nitrogen Loss in a Two-Century Postglacial Chronosequence - Edward T. Malone; Benjamin W. Abbott; Megan J. Klaar; Chris Kidd; Mathieu Sebilo; Alexander M. Milner; Gilles Pinay (Ecosystems, 2018)

Effects of seasonal and environmental changes on aquaculture production in tropical Lake Volta, Ghana - Emmanuel T. D. Mensah; Hederick R. Dankwa; Lauridsen L. Torben; Ruby Asmah; Benjamin B. Campion; Regina Edziyie (Aquaculture International, 2018)

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

Microbes follow Humboldt: temperature drives plant and soil microbial diversity patterns from the Amazon to the Andes - Andrew T. Nottingham; Noah Fierer; Benjamin L. Turner; Jeanette Whitaker; Nick J. Ostle; Niall P. McNamara; Richard D. Bardgett; Jonathan W. Leff; Norma Salinas; Miles R. Silman; Loeske E. B. Kruuk; Patrick Meir (Ecology, 2018)
More than 200 years ago, Alexander von Humboldt reported that tropical plant species richness decreased with increasing elevation and decreasing temperature. Surprisingly, coordinated patterns in plant, bacterial, and fungal diversity on tropical mountains have not yet been observed, despite the central role of soil microorganisms in terrestrial biogeochemistry and ecology. We studied an Andean transect traversing 3.5 km in elevation to test whether the species diversity and composition of tropical forest plants, soil bacteria, and fungi follow similar biogeographical patterns with shared environmental drivers. We found coordinated changes with elevation in all three groups: species richness declined as elevation increased, and the compositional dissimilarity among communities increased with increased separation in elevation, although changes in plant diversity were larger than in bacteria and fungi. Temperature was the dominant driver of these diversity gradients, with weak influences of edaphic properties, including soil pH . The gradients in microbial diversity were strongly correlated with the activities of enzymes involved in organic matter cycling, and were accompanied by a transition in microbial traits towards slower‐growing, oligotrophic taxa at higher elevations. We provide the first evidence of coordinated temperature‐driven patterns in the diversity and distribution of three major biotic groups in tropical ecosystems: soil bacteria, fungi, and plants. These findings suggest that interrelated and fundamental patterns of plant and microbial communities with shared environmental drivers occur across landscape scales. These patterns are revealed where soil pH is relatively constant, and have implications for tropical forest communities under future climate change.

Prolonged standing increases lower limb arterial stiffness - Aaron R. Caldwell; Kaitlin M. Gallagher; Benjamin T. Harris; Megan E. Rosa-Caldwell; Marcus Payne; Bryce Daniels; Matthew S. Ganio (European Journal of Applied Physiology, 2018)

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

Genome-wide association for testis weight in the diversity outbred mouse population - Joshua T. Yuan; Daniel M. Gatti; Vivek M. Philip; Steven Kasparek; Andrew M. Kreuzman; Benjamin Mansky; Kayvon Sharif; Dominik Taterra; Walter M. Taylor; Mary Thomas; Jeremy O. Ward; Andrew Holmes; et al. (Mammalian Genome, 2018)

Validation of a Sulfuric Acid Digestion Method for Inductively Coupled Plasma Mass Spectrometry Quantification of TiO2 Nanoparticles - Preston S. Watkins; Benjamin T. Castellon; Chiyen Tseng; Moncie V. Wright; Cole W. Matson; George P. Cobb (Bulletin of Environmental Contamination and Toxicology, 2018)

Racialized economic segregation and stage at diagnosis of colorectal cancer in the United States - Benjamin J. Scally; Nancy Krieger; Jarvis T. Chen (Cancer Causes & Control, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

Submarine Groundwater Discharge Estimates Using Radium Isotopes and Related Nutrient Inputs into Tauranga Harbour (New Zealand) - Benjamin T. Stewart; Karin R. Bryan; Conrad A. Pilditch; Isaac R. Santos (Estuaries and Coasts, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Somatic embryogenesis, acclimatization and genetic homogeneity assessment of regenerated plantlets of Anoectochilus elatus Lindl., an endangered terrestrial jewel orchid - N. Ahamed Sherif; J. H. Franklin Benjamin; T. Senthil Kumar; M. V. Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Delivery of adjuvant chemotherapy among stage III colon cancer patients at a public versus private hospital in New York City - Daniel Lin; Judith D. Goldberg; Tsivia Hochman; Benjamin A. Levinson; Maria Khan; Elliot Newman; Lawrence P. Leichman; Heather T. Gold (Cancer Causes & Control, 2018)

The conservation status of Texas groundwater invertebrates - Benjamin T. Hutchins (Biodiversity and Conservation, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Vegetation demographics in Earth System Models: A review of progress and priorities - Rosie A. Fisher; Charles D. Koven; William R. L. Anderegg; Bradley O. Christoffersen; Michael C. Dietze; Caroline E. Farrior; Jennifer A. Holm; George C. Hurtt; Ryan G. Knox; Peter J. Lawrence; Jeremy W. Lichstein; Marcos Longo; et al. (Global Change Biology, 2018)
Numerous current efforts seek to improve the representation of ecosystem ecology and vegetation demographic processes within Earth System Models ( ESM s). These developments are widely viewed as an important step in developing greater realism in predictions of future ecosystem states and fluxes. Increased realism, however, leads to increased model complexity, with new features raising a suite of ecological questions that require empirical constraints. Here, we review the developments that permit the representation of plant demographics in ESM s, and identify issues raised by these developments that highlight important gaps in ecological understanding. These issues inevitably translate into uncertainty in model projections but also allow models to be applied to new processes and questions concerning the dynamics of real‐world ecosystems. We argue that stronger and more innovative connections to data, across the range of scales considered, are required to address these gaps in understanding. The development of first‐generation land surface models as a unifying framework for ecophysiological understanding stimulated much research into plant physiological traits and gas exchange. Constraining predictions at ecologically relevant spatial and temporal scales will require a similar investment of effort and intensified inter‐disciplinary communication.

Changes in marijuana use symptoms and emotional functioning over 28-days of monitored abstinence in adolescent marijuana users - Joanna Jacobus; Lindsay M. Squeglia; Silvia Escobar; Benjamin M. McKenna; Margie Mejia Hernandez; Kara S. Bagot; Charles T. Taylor; Marilyn A. Huestis (Psychopharmacology, 2017)

Breeding Differently—the Digital Revolution: High-Throughput Phenotyping and Genotyping - Anthony T. Slater; Noel O. I. Cogan; Brendan C. Rodoni; Hans D. Daetwyler; Benjamin J. Hayes; Brittney Caruana; Pieter E. Badenhorst; German C. Spangenberg; John W. Forster (Potato Research, 2017)

3D seismic analysis of the gas hydrate system and the fluid migration paths in part of the Niger Delta Basin, Nigeria - Olumuyiwa T. Akinsanpe; Adekunle A. Adepelumi; Uzochukwu K. Benjamin; Dele E. Falebita (Journal of Ocean University of China, 2017)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Polyteny: still a giant player in chromosome research - Benjamin M. Stormo; Donald T. Fox (Chromosome Research, 2017)

Investigating Climate Compatible Development Outcomes and their Implications for Distributive Justice: Evidence from Malawi - Benjamin T. Wood; Claire H. Quinn; Lindsay C. Stringer; Andrew J. Dougill (Environmental Management, 2017)

Climate impacts on agricultural land use in the USA: the role of socio-economic scenarios - Jianhong E. Mu; Benjamin M. Sleeter; John T. Abatzoglou; John M. Antle (Climatic Change, 2017)

Biogeochemistry drives diversity in the prokaryotes, fungi, and invertebrates of a Panama forest - Michael Kaspari; Jelena Bujan; Michael D. Weiser; Daliang Ning; Sean T. Michaletz; He Zhili; Brian J. Enquist; Robert B. Waide; Jizhong Zhou; Benjamin L. Turner; S. Joseph Wright (Ecology, 2017)
Humans are both fertilizing the world and depleting its soils, decreasing the diversity of aquatic ecosystems and terrestrial plants in the process. We know less about how nutrients shape the abundance and diversity of the prokaryotes, fungi, and invertebrates of Earth's soils. Here we explore this question in the soils of a Panama forest subject to a 13‐yr fertilization with factorial combinations of nitrogen (N), phosphorus (P), and potassium (K) and a separate micronutrient cocktail. We contrast three hypotheses linking biogeochemistry to abundance and diversity. Consistent with the Stress Hypothesis, adding N suppressed the abundance of invertebrates and the richness of all three groups of organisms by ca. 1 SD or more below controls. Nitrogen addition plots were 0.8 pH units more acidic with 18% more exchangeable aluminum, which is toxic to both prokaryotes and eukaryotes. These stress effects were frequently reversed, however, when N was added with P (for prokaryotes and invertebrates) and with added K (for fungi). Consistent with the Abundance Hypothesis, adding P generally increased prokaryote and invertebrate diversity, and adding K enhanced invertebrate diversity. Also consistent with the Abundance Hypothesis, increases in invertebrate abundance generated increases in richness. We found little evidence for the Competition Hypothesis: that single nutrients suppressed diversity by favoring a subset of high nutrient specialists, and that nutrient combinations suppressed diversity even more. Instead, combinations of nutrients, and especially the cation/micronutrient treatment, yielded the largest increases in richness in the two eukaryote groups. In sum, changes in soil biogeochemistry revealed a diversity of responses among the three dominant soil groups, positive synergies among nutrients, and–in contrast with terrestrial plants–the frequent enhancement of soil biodiversity.

A Proposal to Redefine Clinical Immunogenicity Assessment - Daniel T. Mytych; M. Benjamin Hock; Mark Kroenke; Vibha Jawa; Arunan Kaliyaperumal; Yanchen Zhou (The AAPS Journal, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Investigating genetic introgression from farmed red foxes into the wild population in Newfoundland, Canada - Zachary T. Lounsberry; Cate B. Quinn; Mark J. Statham; Carla L. Angulo; Tatyana J. Kalani; Eugene Tiller; Benjamin N. Sacks (Conservation Genetics, 2017)

Predators modify biogeographic constraints on species distributions in an insect metacommunity - Tess Nahanni Grainger; Rachel M. Germain; Natalie T. Jones; Benjamin Gilbert (Ecology, 2017)
Theory describing the positive effects of patch size and connectivity on diversity in fragmented systems has stimulated a large body of empirical work, yet predicting when and how local species interactions mediate these responses remains challenging. We used insects that specialize on milkweed plants as a model metacommunity to investigate how local predation alters the effects of biogeographic constraints on species distributions. Species‐specific dispersal ability and susceptibility to predation were used to predict when patch size and connectivity should shape species distributions, and when these should be modified by local predator densities. We surveyed specialist herbivores and their predators in milkweed patches in two matrix types, a forest and an old field. Predator‐resistant species showed the predicted direct positive effects of patch size and connectivity on occupancy rates. For predator‐susceptible species, predators consistently altered the impact of biogeographic constraints, rather than acting independently. Finally, differences between matrix types in species’ responses and overall occupancy rates indicate a potential role of the inter‐patch environment in mediating the joint effects of predators and spatial drivers. Together, these results highlight the importance of local top‐down pressure in mediating classic biogeographic relationships, and demonstrate how species‐specific responses to local and regional constraints can be used to predict these effects.

A Multiplatform Experiment to Unravel Meso- and Submesoscale Processes in an Intense Front (AlborEx) - Ananda Pascual; Simon Ruiz; Antonio Olita; Charles Troupin; Mariona Claret; Benjamin Casas; Baptiste Mourre; Pierre-Marie Poulain; Antonio Tovar-Sanchez; Arthur Capet; Evan Mason; John T. Allen; et al. (Frontiers in Marine Science, 2017)

Effects of N-methyl-D-aspartate receptor ligands on sensitivity to reinforcer magnitude and delayed reinforcement in a delay-discounting procedure - Justin R Yates; Benjamin T Gunkel; Katherine K Rogers; Mallory N Hughes; Nicholas A Prior (Psychopharmacology, 2017)

Recent Changes in Land Water Storage and its Contribution to Sea Level Variations - Yoshihide Wada; John T. Reager; Benjamin F. Chao; Jida Wang; Min-Hui Lo; Chunqiao Song; Yuwen Li; Alex S. Gardner (Surveys in Geophysics, 2017)

Assessment of metal contamination in the biota of four rivers experiencing varying degrees of human impact - Gretchen K. Bielmyer-Fraser; Matthew Neal Waters; Christina G. Duckworth; Pratik P. Patel; Benjamin Cole Webster; Amber Blocker; Cliff Hunter Crummey; Aundrea Nicole Duncan; Somuayiro Nadia Nwokike; Codie Richard Picariello; James T. Ragan; Erika L. Schumacher; et al. (Environmental Monitoring and Assessment, 2017)

Moving Towards a New Urban Systems Science - Peter M. Groffman; Mary L. Cadenasso; Jeannine Cavender-Bares; Daniel L. Childers; Nancy B. Grimm; J. Morgan Grove; Sarah E. Hobbie; Lucy R. Hutyra; G. Darrel Jenerette; Timon McPhearson; Diane E. Pataki; Steward T. A. Pickett; et al. (Ecosystems, 2017)

Climate change adaptation and the Least Developed Countries Fund (LDCF): Qualitative insights from policy implementation in the Asia-Pacific - Benjamin K. Sovacool; Björn-Ola Linnér; Richard J. T. Klein (Climatic Change, 2017)

Survival probabilities and movements of harbor seals in central California - Suzanne C. Manugian; Denise Greig; Derek Lee; Benjamin H. Becker; Sarah Allen; Mark S. Lowry; James T. Harvey (Marine Mammal Science, 2017)
Harbor seal numbers and population trajectories differ by location in central California. Within San Francisco Bay ( SFB ) counts have been relatively stable since the 1972 Marine Mammal Protection Act, but in coastal areas like Tomales Bay ( TB ), counts increased before stabilizing in the 1990s. Emigration, poor survival, and environmental effects have been hypothesized as contributors to differences between trajectories; however, basic demographic data were not available to evaluate these hypotheses. We monitored 32 radio‐tagged adult females ( SFB n = 17, TB n = 15) for 20 mo (2011–2013), and estimated survival, resight, and movement probabilities using mark‐resight analyses and multistate mark‐resight models. Annual survival probability for both sites was 0.90 (95% CI = 0.18–0.99). Six seals were observed moving between locations resulting in an estimated probability of 0.042 (95% CI = 0.023–0.076) per month equal movement between sites. Resight probability was less in SFB relative to TB , likely due to differential haul‐out access, area surveyed, visibility, and resight effort. Because of wide confidence intervals and low precision of these first estimates of adult female harbor seal survival in California, this demographic must be further examined to dismiss its contribution to differing population trajectories. Using aerial survey data, we estimated 950 harbor seals in SFB (95% CI = 715–1,184) confirming numbers are still stable.

Realizing the potential of trait‐based aquatic ecology: New tools and collaborative approaches - Colin T. Kremer; Alicia K. Williams; Michael Finiguerra; Allison A. Fong; Anne Kellerman; Sara F. Paver; Bradley B. Tolar; Benjamin J. Toscano (Limnology and Oceanography, 2017)
Trait‐based ecology, which focuses on using the traits of species and individuals to understand ecology (from populations to ecosystems), is becoming an increasingly productive and widely employed paradigm. To date, trait‐based approaches have been used to study taxa from microbes to megafauna in every major area of aquatic ecology yielding exciting results. However, this promising field faces a number of significant obstacles, including: (1) identifying and measuring ecologically relevant traits, (2) integrating inter‐ and intra‐specific trait variation, (3) detecting and quantifying trait correlations and trade‐offs, and (4) accounting for the context dependency of traits. These issues are often particularly acute for specific taxa or systems. This paper highlights these looming challenges, as well as ways to address them. Proposed solutions center around using new technologies to collect trait data, coordinating research efforts, and curating and sharing data. Throughout, we take an interdisciplinary approach, sharing examples spanning a wide range of aquatic taxa and systems. It is our hope that this paper will stimulate frank discussions and help the growing field of trait‐based aquatic ecology maximize its potential.

Phenomenological vs. biophysical models of thermal stress in aquatic eggs - Benjamin T. Martin; Andrew Pike; Sara N. John; Natnael Hamda; Jason Roberts; Steven T. Lindley; Eric M. Danner (Ecology Letters, 2017)
Predicting species responses to climate change is a central challenge in ecology. These predictions are often based on lab‐derived phenomenological relationships between temperature and fitness metrics. We tested one of these relationships using the embryonic stage of a Chinook salmon population. We parameterised the model with laboratory data, applied it to predict survival in the field, and found that it significantly underestimated field‐derived estimates of thermal mortality. We used a biophysical model based on mass transfer theory to show that the discrepancy was due to the differences in water flow velocities between the lab and the field. This mechanistic approach provides testable predictions for how the thermal tolerance of embryos depends on egg size and flow velocity of the surrounding water. We found support for these predictions across more than 180 fish species, suggesting that flow and temperature mediated oxygen limitation is a general mechanism underlying the thermal tolerance of embryos.

Biotic forcing: the push–pull of plant ranges - Natalie T. Jones; Benjamin Gilbert (Plant Ecology, 2016)

The effect of climate change on rural land cover patterns in the Central United States - Christopher Lant; Timothy J. Stoebner; Justin T. Schoof; Benjamin Crabb (Climatic Change, 2016)

The occurrence of pulse, “knock” sounds amidst social/sexual behavior of gray whales ( Eschrichtius robustus ) off Vancouver Island - Benjamin T. Youngson; James D. Darling (Marine Mammal Science, 2016)

Subglacial lava propagation, ice melting and heat transfer during emplacement of an intermediate lava flow in the 2010 Eyjafjallajökull eruption - Björn Oddsson; Magnús T. Gudmundsson; Benjamin R. Edwards; Thorvaldur Thordarson; Eyjólfur Magnússon; Gunnar Sigurðsson (Bulletin of Volcanology, 2016)

Mapping 3D Strains with Ultrasound Speckle Tracking: Method Validation and Initial Results in Porcine Scleral Inflation - Benjamin Cruz Perez; Elias Pavlatos; Hugh J. Morris; Hong Chen; Xueliang Pan; Richard T. Hart; Jun Liu (Annals of Biomedical Engineering, 2016)

Sinking phytoplankton associated with carbon flux in the Atlantic Ocean - Colleen A. Durkin; Benjamin A. S. Van Mooy; Sonya T. Dyhrman; Ken O. Buesseler (Limnology and Oceanography, 2016)
The composition of sinking particles and the mechanisms leading to their transport ultimately control how much carbon is naturally sequestered in the deep ocean by the “biological pump.” While detrital particles often contain much of the sinking carbon, sinking of intact phytoplankton cells can also contribute to carbon export, which represents a direct flux of carbon from the atmosphere to the deep ocean by circumventing the surface ocean food web. Phytoplankton that contributed to carbon flux were identified in sinking material collected by short‐term sediment trap deployments conducted along a transect off the eastern shore of South America. Particulate organic carbon flux at 125 m depth did not change significantly along the transect. Instead, changes occurred in the composition and association of phytoplankton with detrital particles. The fluxes of diatoms, coccolithophores, dinoflagellates, and nano‐sized cells at 125 m were unrelated to the overlying surface population abundances, indicating that functional‐group specific transport mechanisms were variable across locations. The dominant export mechanism of phytoplankton at each station was putatively identified by principal component analysis and fell into one of three categories; (1) transport and sinking of individual, viable diatom cells, (2) transport by aggregates and fecal pellets, or (3) enhanced export of coccolithophores through direct settling and/or aggregation.

Thermal stratification in small arctic lakes of southwest Greenland affected by water transparency and epilimnetic temperatures - Jasmine E. Saros; Robert M. Northington; Christopher L. Osburn; Benjamin T. Burpee; Nicholas John Anderson (Limnology and Oceanography, 2016)
We assessed which factors control summer epilimnion thickness in arctic lakes of southwest Greenland. A suite of 22 lakes that thermally stratify was measured in the summer of 2013; a sub‐set of eight of the lakes was measured again in 2014, which was a warmer summer than 2013. Regression analysis of the 22 lakes indicated that the 1% attenuation depth for photosynthetically active radiation (PAR) was the strongest single predictor ( R 2 = 0.75) of epilimnion thickness across lakes; the addition of epilimnion temperature to the PAR model explained additional variability ( R 2 = 0.79). The importance of including temperature in the model was apparent in the results of model validation as well as when comparing across years: while the 1% PAR was 0.4–2 m deeper in 2014 compared with 2013, water temperatures were 2–3°C higher, resulting in July epilimnion thicknesses that were equal to or shallower than in 2013. In these lakes with low color dissolved organic carbon (DOC), multiple factors control the 1% PAR, including absorbance at 440 nm ( a 440 ), 380 nm ( a 380 ), and 320 ( a 320 ), chlorophyll a (Chl a ) and DOC concentration. In 2014, when 1% PAR was deeper than in 2013, a 380, Chl a and DOC were lower in six of the eight lakes. Our results reveal that the thermal structure of these arctic lakes is under complex control by air temperatures and factors that affect PAR attenuation, particularly Chl a and DOC quality, suggesting that continued warming in the Arctic will have strong effects on lake stratification.

Female Sexual Preferences Toward Conspecific and Hybrid Male Mating Calls in Two Species of Polygynous Deer, Cervus elaphus and C. nippon - Megan T. Wyman; Yann Locatelli; Benjamin D. Charlton; David Reby (Evolutionary Biology, 2016)

Chemolithoautotrophy supports macroinvertebrate food webs and affects diversity and stability in groundwater communities - Benjamin T. Hutchins; Annette Summers Engel; Weston H. Nowlin; Benjamin F. Schwartz (Ecology, 2016)
The prevailing paradigm in subterranean ecology is that below‐ground food webs are simple, limited to one or two trophic levels, and composed of generalist species because of spatio‐temporally patchy food resources and pervasive energy limitation. This paradigm is based on relatively few studies of easily accessible, air‐filled caves. However, in some subterranean ecosystems, chemolithoautotrophy can subsidize or replace surface‐based allochthonous inputs of photosynthetically derived organic matter ( OM ) as a basal food resource and promote niche specialization and evolution of higher trophic levels. Consequently, the current subterranean trophic paradigm fails to account for variation in resources, trophic specialization, and food chain length in some subterranean ecosystems. We reevaluated the subterranean food web paradigm by examining spatial variation in the isotopic composition of basal food resources and consumers, food web structure, stygobiont species diversity, and chromophoric organic matter ( CDOM ), across a geochemical gradient in a large and complex groundwater system, the Edwards Aquifer in Central Texas ( USA ). Mean δ 13 C values of stygobiont communities become increasingly more negative along the gradient of photosynthetic OM sources near the aquifer recharge zone to chemolithoautotrophic OM sources closer to the freshwater‐saline water interface ( FWSWI ) between oxygenated freshwater and anoxic, sulfide‐rich saline water. Stygobiont community species richness declined with increasing distance from the FWSWI . Bayesian mixing models were used to estimate the relative importance of photosynthetic OM and chemolithoautotrophic OM for stygobiont communities at three biogeochemically distinct sites. The contribution of chemolithoautotrophic OM to consumers at these sites ranged between 25% and 69% of total OM utilized and comprised as much as 88% of the diet for one species. In addition, the food web adjacent to the FWSWI had greater trophic diversity when compared to the other two sites. Our results suggest that diverse OM sources and in situ , chemolithoautotrophic OM production can support complex groundwater food webs and increase species richness. Chemolithoautotrophy has been fundamental for the long‐term maintenance of species diversity, trophic complexity, and community stability in this subterranean ecosystem, especially during periods of decreased photosynthetic production and groundwater recharge that have occurred over geologic time scales.

Responses of Marine Organisms to Climate Change across Oceans - Elvira S. Poloczanska; Michael T. Burrows; Christopher J. Brown; Jorge García Molinos; Benjamin S. Halpern; Ove Hoegh-Guldberg; Carrie V. Kappel; Pippa J. Moore; Anthony J. Richardson; David S. Schoeman; William J. Sydeman (Frontiers in Marine Science, 2016)

A Permutation Test for Unbalanced Paired Comparisons of Global Field Power - Benjamin T. Files; Vernon J. Lawhern; Anthony J. Ries; Amar R. Marathe (Brain Topography, 2016)

Ecological and methodological drivers of species’ distribution and phenology responses to climate change - Christopher J. Brown; Mary I. O'Connor; Elvira S. Poloczanska; David S. Schoeman; Lauren B. Buckley; Michael T. Burrows; Carlos M. Duarte; Benjamin S. Halpern; John M. Pandolfi; Camille Parmesan; Anthony J. Richardson (Global Change Biology, 2016)
Climate change is shifting species’ distribution and phenology. Ecological traits, such as mobility or reproductive mode, explain variation in observed rates of shift for some taxa. However, estimates of relationships between traits and climate responses could be influenced by how responses are measured. We compiled a global data set of 651 published marine species’ responses to climate change, from 47 papers on distribution shifts and 32 papers on phenology change. We assessed the relative importance of two classes of predictors of the rate of change, ecological traits of the responding taxa and methodological approaches for quantifying biological responses. Methodological differences explained 22% of the variation in range shifts, more than the 7.8% of the variation explained by ecological traits. For phenology change, methodological approaches accounted for 4% of the variation in measurements, whereas 8% of the variation was explained by ecological traits. Our ability to predict responses from traits was hindered by poor representation of species from the tropics, where temperature isotherms are moving most rapidly. Thus, the mean rate of distribution change may be underestimated by this and other global syntheses. Our analyses indicate that methodological approaches should be explicitly considered when designing, analysing and comparing results among studies. To improve climate impact studies, we recommend that (1) reanalyses of existing time series state how the existing data sets may limit the inferences about possible climate responses; (2) qualitative comparisons of species’ responses across different studies be limited to studies with similar methodological approaches; (3) meta‐analyses of climate responses include methodological attributes as covariates; and (4) that new time series be designed to include the detection of early warnings of change or ecologically relevant change. Greater consideration of methodological attributes will improve the accuracy of analyses that seek to quantify the role of climate change in species’ distribution and phenology changes.

Li zoning in zircon as a potential geospeedometer and peak temperature indicator - Dustin Trail; Daniele J. Cherniak; E. Bruce Watson; T. Mark Harrison; Benjamin P. Weiss; Ian Szumila (Contributions to Mineralogy and Petrology, 2016)

Dating archaeobotanical remains: a cautionary tale from Port au Choix, Newfoundland - Robert J. Anstey; Eric J. Guiry; M. A. P. Renouf; Michael Deal; Benjamin T. Fuller (Vegetation History and Archaeobotany, 2016)

Unacylated ghrelin restores insulin and autophagic signaling in skeletal muscle of diabetic mice - Bjorn T. Tam; Xiao M. Pei; Benjamin Y. Yung; Shea P. Yip; Lawrence W. Chan; Cesar S. Wong; Parco M. Siu (Pflügers Archiv - European Journal of Physiology, 2015)

Organic and inorganic mercurials have distinct effects on cellular thiols, metal homeostasis, and Fe-binding proteins in Escherichia coli - Stephen P. LaVoie; Daphne T. Mapolelo; Darin M. Cowart; Benjamin J. Polacco; Michael K. Johnson; Robert A. Scott; Susan M. Miller; Anne O. Summers (JBIC Journal of Biological Inorganic Chemistry, 2015)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Analyzing the disruption resilience of bioenergy parks using dynamic inoperability input–output modeling - Michael Francis D. Benjamin; Aristotle T. Ubando; Luis F. Razon; Raymond R. Tan (Environment Systems and Decisions, 2015)

Rhizobacterial colonization of roots modulates plant volatile emission and enhances the attraction of a parasitoid wasp to host-infested plants - Nurmi Pangesti; Berhane T. Weldegergis; Benjamin Langendorf; Joop J. A. van Loon; Marcel Dicke; Ana Pineda (Oecologia, 2015)

Overview of the special issue: a multi-model framework to achieve consistent evaluation of climate change impacts in the United States - Stephanie T. Waldhoff; Jeremy Martinich; Marcus Sarofim; Benjamin DeAngelo; Jim McFarland; Lesley Jantarasami; Kate Shouse; Allison Crimmins; Sara Ohrel; Jia Li (Climatic Change, 2015)

Distinct muscle apoptotic pathways are activated in muscles with different fiber types in a rat model of critical illness myopathy - Benjamin T. Barnes; Amy L. Confides; Mark M. Rich; Esther E. Dupont-Versteegden (Journal of Muscle Research and Cell Motility, 2015)

Indigenous innovation incorporates biochar into swidden-fallow agroforestry systems in Amazonian Peru - Benjamin C. Miltner; Oliver T. Coomes (Agroforestry Systems, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Evans blue nanocarriers visually demarcate margins of invasive gliomas - Benjamin T. Roller; Jennifer M. Munson; Barunashish Brahma; Philip J. Santangelo; S. Balakrishna Pai; Ravi V. Bellamkonda (Drug Delivery and Translational Research, 2015)

Controls on the nitrogen isotopic composition of shallow water corals across a tropical reef flat transect - Dirk V. Erler; Xingchen T. Wang; Daniel M. Sigman; Sander R. Scheffers; Benjamin O. Shepherd (Coral Reefs, 2015)

The role of photo-osmotic adaptation in semi-continuous culture and lipid particle release from Dunaliella viridis - Ryan W. Davis; Benjamin J. Carvalho; Howland D. T. Jones; Seema Singh (Journal of Applied Phycology, 2015)

Strengthening confidence in climate change impact science - Mary I. O'Connor; Johnna M. Holding; Carrie V. Kappel; Carlos M. Duarte; Keith Brander; Christopher J. Brown; John F. Bruno; Lauren Buckley; Michael T. Burrows; Benjamin S. Halpern; Wolfgang Kiessling; Pippa Moore; et al. (Global Ecology and Biogeography, 2015)
Aim To assess confidence in conclusions about climate‐driven biological change through time, and identify approaches for strengthening confidence scientific conclusions about ecological impacts of climate change. Location Global. Methods We outlined a framework for strengthening confidence in inferences drawn from biological climate impact studies through the systematic integration of prior expectations, long‐term data and quantitative statistical procedures. We then developed a numerical confidence index ( C index ) and used it to evaluate current practices in 208 studies of marine climate impacts comprising 1735 biological time series. Results Confidence scores for inferred climate impacts varied widely from 1 to 16 (very low to high confidence). Approximately 35% of analyses were not associated with clearly stated prior expectations and 65% of analyses did not test putative non‐climate drivers of biological change. Among the highest‐scoring studies, 91% tested prior expectations, 86% formulated expectations for alternative drivers but only 63% statistically tested them. Higher confidence scores observed in studies that did not detect a change or tracked multiple species suggest publication bias favouring impact studies that are consistent with climate change. The number of time series showing climate impacts was a poor predictor of average confidence scores for a given group, reinforcing that vote‐counting methodology is not appropriate for determining overall confidence in inferences. Main conclusions Climate impacts research is expected to attribute biological change to climate change with measurable confidence. Studies with long‐term, high‐resolution data, appropriate statistics and tests of alternative drivers earn higher C index scores, suggesting these should be given greater weight in impact assessments. Together with our proposed framework, the results of our C index analysis indicate how the science of detecting and attributing biological impacts to climate change can be strengthened through the use of evidence‐based prior expectations and thorough statistical analyses, even when data are limited, maximizing the impact of the diverse and growing climate change ecology literature.

The influence of head and body tilt on human fore-aft translation perception - Benjamin T. Crane (Experimental Brain Research, 2014)

Transplantation of devitalized muscle scaffolds is insufficient for appreciable de novo muscle fiber regeneration after volumetric muscle loss injury - Koyal Garg; Catherine L. Ward; Christopher R. Rathbone; Benjamin T. Corona (Cell and Tissue Research, 2014)

Improving breeding efficiency in potato using molecular and quantitative genetics - Anthony T. Slater; Noel O. I. Cogan; Benjamin J. Hayes; Lee Schultz; M. Finlay B. Dale; Glenn J. Bryan; John W. Forster (Theoretical and Applied Genetics, 2014)

Dextran-Coated Gold Nanoprobes for the Concentration and Detection of Protein Biomarkers - Ricky Y. T. Chiu; Phuong T. Nguyen; Juntian Wang; Erik Jue; Benjamin M. Wu; Daniel T. Kamei (Annals of Biomedical Engineering, 2014)

Response of red deer stags (Cervus elaphus) to playback of harsh versus common roars - Maxime Garcia; Megan T. Wyman; Benjamin D. Charlton; W. Tecumseh Fitch; David Reby (The Science of Nature, 2014)

Neuromuscular Complexity During Gait is not Responsive to Medication in Persons with Parkinson’s Disease - Ryan T. Roemmich; Benjamin J. Fregly; Chris J. Hass (Annals of Biomedical Engineering, 2014)

Global relationship of wood and leaf litter decomposability: the role of functional traits within and across plant organs - Katherina A. Pietsch; Kiona Ogle; Johannes H. C. Cornelissen; William K. Cornwell; Gerhard Bönisch; Joseph M. Craine; Benjamin G. Jackson; Jens Kattge; Duane A. Peltzer; Josep Penuelas; Peter B. Reich; David A. Wardle; et al. (Global Ecology and Biogeography, 2014)
Aim Recent meta‐analyses have revealed that plant traits and their phylogenetic history influence decay rates of dead wood and leaf litter, but it remains unknown if decay rates of wood and litter covary over a wide range of tree species and across ecosystems. We evaluated the relationships between species‐specific wood and leaf litter decomposability, as well as between wood and leaf traits that control their respective decomposability. Location Global. Methods We compiled data on rates of wood and leaf litter decomposition for 324 and 635 tree species, respectively, and data on six functional traits for both organs. We used hierarchical Bayesian meta‐analysis to estimate, for the first time, species‐specific values for wood and leaf litter decomposability standardized to reference conditions ( k * wood and k * leaf ) across the globe. With these data, we evaluated the relationships: (1) between wood and leaf traits, (2) between each k * and the selected traits within and across organs, and (3) between wood and leaf k *. Results Across all species k * wood and k * leaf were positively correlated, phylogenetically clustered and correlated with plant functional traits within and across organs. k * of both organs was usually better described as a function of within‐ and cross‐organ traits, than of within‐organ traits alone. When analysed for angiosperms and gymnosperms separately, wood and leaf k * were no longer significantly correlated, but each k * was still significantly correlated to the functional traits. Main conclusions We demonstrate important relationships among wood and leaf litter decomposability as after‐life effects of traits from the living plants. These functional traits influence the decomposability of senesced tissue which could potentially lead to alterations in the rates of biogeochemical cycling, depending on the phylogenetic structure of the species pool. These results provide crucial information for a better representation of decomposition rates in dynamic global vegetation models.

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

Thresholds in the Response of Free-Floating Plant Abundance to Variation in Hydraulic Connectivity, Nutrients, and Macrophyte Abundance in a Large Floodplain River - Shawn M. Giblin; Jeffrey N. Houser; John F. Sullivan; Heidi A. Langrehr; James T. Rogala; Benjamin D. Campbell (Wetlands, 2014)

Development and Initial Feedback About a Human Papillomavirus (HPV) Vaccine Comic Book for Adolescents - Mira L. Katz; Benjamin R. Oldach; Jennifer Goodwin; Paul L. Reiter; Mack T. Ruffin; Electra D. Paskett (Journal of Cancer Education, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Development and characterization of 15 polymorphic microsatellite markers for North Pacific albatrosses using paired-end Illumina shotgun sequencing - Luis D. Hernandez; Zachary T. Lounsberry; Paul W. Collins; Robert W. Henry; Seth D. Newsome; Benjamin N. Sacks (Conservation Genetics Resources, 2014)

Pituitary control of branchial NCC, NKCC and Na+, K+-ATPase α-subunit gene expression in Nile tilapia, Oreochromis niloticus - Jason P. Breves; Andre P. Seale; Benjamin P. Moorman; Darren T. Lerner; Shunsuke Moriyama; Kevin D. Hopkins; E. Gordon Grau (Journal of Comparative Physiology B, 2014)

Improving the analysis of low heritability complex traits for enhanced genetic gain in potato - Anthony T. Slater; Graeme M. Wilson; Noel O. I. Cogan; John W. Forster; Benjamin J. Hayes (Theoretical and Applied Genetics, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Stereological and ultrastructural quantification of the afferent synaptome of individual neurons - Pablo Henny; Matthew T. C. Brown; Benjamin R. Micklem; Peter J. Magill; J. Paul Bolam (Brain Structure and Function, 2014)

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Modeling structured population dynamics using data from unmarked individuals - Elise F. Zipkin; James T. Thorson; Kevin See; Heather J. Lynch; Evan H. Campbell Grant; Yoichiro Kanno; Richard B. Chandler; Benjamin H. Letcher; J. Andrew Royle (Ecology, 2014)
The study of population dynamics requires unbiased, precise estimates of abundance and vital rates that account for the demographic structure inherent in all wildlife and plant populations. Traditionally, these estimates have only been available through approaches that rely on intensive mark–recapture data. We extended recently developed N ‐mixture models to demonstrate how demographic parameters and abundance can be estimated for structured populations using only stage‐structured count data. Our modeling framework can be used to make reliable inferences on abundance as well as recruitment, immigration, stage‐specific survival, and detection rates during sampling. We present a range of simulations to illustrate the data requirements, including the number of years and locations necessary for accurate and precise parameter estimates. We apply our modeling framework to a population of northern dusky salamanders ( Desmognathus fuscus ) in the mid‐Atlantic region (USA) and find that the population is unexpectedly declining. Our approach represents a valuable advance in the estimation of population dynamics using multistate data from unmarked individuals and should additionally be useful in the development of integrated models that combine data from intensive (e.g., mark–recapture) and extensive (e.g., counts) data sources.

Evolution of dispersal and life history interact to drive accelerating spread of an invasive species - T. Alex Perkins; Benjamin L. Phillips; Marissa L. Baskett; Alan Hastings (Ecology Letters, 2013)
Populations on the edge of an expanding range are subject to unique evolutionary pressures acting on their life‐history and dispersal traits. Empirical evidence and theory suggest that traits there can evolve rapidly enough to interact with ecological dynamics, potentially giving rise to accelerating spread. Nevertheless, which of several evolutionary mechanisms drive this interaction between evolution and spread remains an open question. We propose an integrated theoretical framework for partitioning the contributions of different evolutionary mechanisms to accelerating spread, and we apply this model to invasive cane toads in northern Australia. In doing so, we identify a previously unrecognised evolutionary process that involves an interaction between life‐history and dispersal evolution during range shift. In roughly equal parts, life‐history evolution, dispersal evolution and their interaction led to a doubling of distance spread by cane toads in our model, highlighting the potential importance of multiple evolutionary processes in the dynamics of range expansion.

Clinical Pharmacokinetics of Buffered Propranolol Sublingual Tablet (Promptol™)—Application of a New “Physiologically Based” Model to Assess Absorption and Disposition - Yanfeng Wang; Zhijun Wang; Zhong Zuo; Brian Tomlinson; Benjamin T. K. Lee; Michael B. Bolger; Moses S. S. Chow (The AAPS Journal, 2013)

Heat waves in the United States: definitions, patterns and trends - Tiffany T. Smith; Benjamin F. Zaitchik; Julia M. Gohlke (Climatic Change, 2013)

Comparison of discharge, chloride, temperature, uranine, δD, and suspended sediment responses from a multiple tracer test in karst - Andrew J. Luhmann; Matthew D. Covington; Scott C. Alexander; Su Yi Chai; Benjamin F. Schwartz; Joel T. Groten; E. Calvin Alexander (Carbonates and Evaporites, 2013)

Extrapolating ecotoxicological effects from individuals to populations: a generic approach based on Dynamic Energy Budget theory and individual-based modeling - Benjamin T. Martin; Tjalling Jager; Roger M. Nisbet; Thomas G. Preuss; Monika Hammers-Wirtz; Volker Grimm (Ecotoxicology, 2013)

The Need for a Next Generation of Sonoran Desert Researchers - Benjamin T. Wilder; Carolyn O'Meara; Nemer Narchi; Alfonso Medel Narváez; Octavio Aburto‐Oropeza (Conservation Biology, 2013)

Oxidative stress and DNA damage signalling in skeletal muscle in pressure-induced deep tissue injury - Thomas K. Sin; Xiao M. Pei; Bee T. Teng; Eric W. Tam; Benjamin Y. Yung; Parco M. Siu (Pflügers Archiv - European Journal of Physiology, 2013)

Limited interaction between translation and visual motion aftereffects in humans - Benjamin T. Crane (Experimental Brain Research, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Roll aftereffects: influence of tilt and inter-stimulus interval - Benjamin T. Crane (Experimental Brain Research, 2012)

The Impact of Extreme Low Flows on the Water Quality of the Lower Murray River and Lakes (South Australia) - Luke M. Mosley; Benjamin Zammit; Emily Leyden; Theresa M. Heneker; Matthew R. Hipsey; Dominic Skinner; Kane T. Aldridge (Water Resources Management, 2012)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Transposon proliferation in an asexual parasitoid - KEN KRAAIJEVELD; BRECHTJE ZWANENBURG; BENJAMIN HUBERT; CRISTINA VIEIRA; SYLVIA De PATER; JACQUES J. M. Van ALPHEN; JOHAN T. Den DUNNEN; PETER De KNIJFF (Molecular Ecology, 2012)
The widespread occurrence of sex is one of the most elusive problems in evolutionary biology. Theory predicts that asexual lineages can be driven to extinction by uncontrolled proliferation of vertically transmitted transposable elements (TEs), which accumulate because of the inefficiency of purifying selection in the absence of sex and recombination. To test this prediction, we compared genome‐wide TE load between a sexual lineage of the parasitoid wasp Leptopilina clavipes and a lineage of the same species that is rendered asexual by Wolbachia ‐induced parthenogenesis. We obtained draft genome sequences at 15–20× coverage of both the sexual and the asexual lineages using next‐generation sequencing. We identified transposons of most major classes in both lineages. Quantification of TE abundance using coverage depth showed that copy numbers in the asexual lineage exceeded those in the sexual lineage for DNA transposons, but not LTR and LINE‐like elements. However, one or a small number of gypsy ‐like LTR elements exhibited a fourfold higher coverage in the asexual lineage. Quantitative PCR showed that high loads of this gypsy ‐like TE were characteristic for 11 genetically distinct asexual wasp lineages when compared to sexual lineages. We found no evidence for an overall increase in copy number for all TE types in asexuals as predicted by theory. Instead, we suggest that the expansions of specific TEs are best explained as side effects of (epi)genetic manipulations of the host genome by Wolbachia. Asexuality is achieved in a myriad of ways in nature, many of which could similarly result in TE proliferation.

Metal Accumulation From Dietary Exposure in the Sea Urchin, Strongylocentrotus droebachiensis - Gretchen K. Bielmyer; Tayler A. Jarvis; Benjamin T. Harper; Brittany Butler; Lawrence Rice; Siobhan Ryan; Peter McLoughlin (Archives of Environmental Contamination and Toxicology, 2012)

Butterfly response to floral resources during early establishment at a heterogeneous prairie biomass production site in Iowa, USA - Mark C. Myers; Benjamin J. Hoksch; James T. Mason (Journal of Insect Conservation, 2012)

Suprathreshold asymmetries in human motion perception - Rachel E. Roditi; Benjamin T. Crane (Experimental Brain Research, 2012)

Fore–aft translation aftereffects - Benjamin T. Crane (Experimental Brain Research, 2012)

Priority Actions for Sustainable Forest Management in the International Year of Forests - DOMINICK A. DELLASALA; JOHN M. FITZGERALD; BENGT‐GUNNAR JONSSON; JEFFREY A. MCNEELY; BENJAMIN DELALI DOVIE; MARTIN DIETERICH; PATRICIA MAJLUF; SIMON C. NEMTZOV; OWEN T. NEVIN; E. CHRISTIEN M. PARSONS; JAMES E.M. WATSON (Conservation Biology, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Groundwater recharge to a sedimentary aquifer in the topographically closed Uley South Basin, South Australia - Carlos M. Ordens; Adrian D. Werner; Vincent E. A. Post; John L. Hutson; Craig T. Simmons; Benjamin M. Irvine (Hydrogeology Journal, 2012)

Projecting the future distribution of European potential natural vegetation zones with a generalized, tree species‐based dynamic vegetation model - Thomas Hickler; Katrin Vohland; Jane Feehan; Paul A. Miller; Benjamin Smith; Luis Costa; Thomas Giesecke; Stefan Fronzek; Timothy R. Carter; Wolfgang Cramer; Ingolf Kühn; Martin T. Sykes (Global Ecology and Biogeography, 2012)
Aim To assess the extent to which climate change might cause changes in potential natural vegetation (PNV) across Europe. Location Europe. Method We parameterized a generalized dynamic vegetation model (LPJ‐GUESS) for the most common European tree species, and, for the first time, modelled large‐scale vegetation dynamics using a process‐based model explicitly representing tree species, age cohorts, gap dynamics and biogeochemical cycles in a single framework. For projections, the model was driven with climate scenario data from two atmosphere–ocean general circulation models (AOGCMs), downscaled to 10 × 10′ spatial resolution ( c . 18.5 × 12 km at 50° N). Results At a general level, modelled present‐day PNV corresponded better with an expert reconstruction of the PNV than most earlier plant functional type (PFT)‐based simulations, but at a finer scale the model and the expert map showed substantial discrepancies in some areas. Simulations until 2085 showed considerable successional shifts in vegetation types in most areas: 31–42% of the total area of Europe was projected to be covered by a different vegetation type by the year 2085. In the long term, equilibrium changes are substantially larger: simulations with one climate scenario suggest that 76–80% of the European land surface could exist within another PNV if climate was stabilized by the end of the century and vegetation had unlimited time to achieve equilibrium with the new climate. ‘Hotspots’ of change include arctic and alpine ecosystems, where trees replace tundra in the model, and the transition zone between temperate broad‐leaved and boreal conifer forest. In southern Europe, the model projected widespread shifts from forest to shrublands as a result of drought. Main conclusions The model presents a considerable advance in modelling dynamic changes in natural vegetation across Europe. Climate change might cause substantial changes in PNV across Europe, which should be considered in the management of reserves and forestry.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.

Genome of alkaliphilic Bacillus pseudofirmus OF4 reveals adaptations that support the ability to grow in an external pH range from 7.5 to 11.4 - Benjamin Janto; Azad Ahmed; Masahiro Ito; Jun Liu; David B. Hicks; Sarah Pagni; Oliver J. Fackelmayer; Terry‐Ann Smith; Joshua Earl; Liam D.H. Elbourne; Karl Hassan; Ian T. Paulsen; et al. (Environmental Microbiology, 2011)
Summary Bacillus pseudofirmus OF4 is an extreme but facultative alkaliphile that grows non‐fermentatively in a pH range from 7.5 to above 11.4 and can withstand large sudden increases in external pH. It is a model organism for studies of bioenergetics at high pH, at which energy demands are higher than at neutral pH because both cytoplasmic pH homeostasis and ATP synthesis require more energy. The alkaliphile also tolerates a cytoplasmic pH > 9.0 at external pH values at which the pH homeostasis capacity is exceeded, and manages other stresses that are exacerbated at alkaline pH, e.g. sodium, oxidative and cell wall stresses. The genome of B. pseudofirmus OF4 includes two plasmids that are lost from some mutants without viability loss. The plasmids may provide a reservoir of mobile elements that promote adaptive chromosomal rearrangements under particular environmental conditions. The genome also reveals a more acidic pI profile for proteins exposed on the outer surface than found in neutralophiles. A large array of transporters and regulatory genes are predicted to protect the alkaliphile from its overlapping stresses. In addition, unanticipated metabolic versatility was observed, which could ensure requisite energy for alkaliphily under diverse conditions.

A longitudinal study of motor performance and striatal [18F]fluorodopa uptake in Parkinson’s disease - Catherine L. Gallagher; Sterling C. Johnson; Barbara B. Bendlin; Moo K. Chung; James E. Holden; Terrence R. Oakes; Benjamin R. Brooks; Richard A. Konopacki; Selami Dogan; James H. Abbs; Guofan Xu; Robert J. Nickles; et al. (Brain Imaging and Behavior, 2011)

Effect of resistance training during hemodialysis on circulating cytokines: a randomized controlled trial - Birinder Singh Bobby Cheema; Haifa Abas; Benjamin C. F. Smith; Anthony J. O’Sullivan; Maria Chan; Aditi Patwardhan; John Kelly; Adrian Gillin; Glen Pang; Brad Lloyd; Klaus Berger; Bernhard T. Baune; et al. (European Journal of Applied Physiology, 2011)

Chemical reactivity of Synechococcus sp. PCC 7002 and Synechocystis sp. PCC 6803 hemoglobins: covalent heme attachment and bishistidine coordination - Henry J. Nothnagel; Matthew R. Preimesberger; Matthew P. Pond; Benjamin Y. Winer; Emily M. Adney; Juliette T. J. Lecomte (JBIC Journal of Biological Inorganic Chemistry, 2011)

Economics of Grassland Conversion to Cropland in the Prairie Pothole Region - BENJAMIN S. RASHFORD; JOHANN A. WALKER; CHRISTOPHER T. BASTIAN (Conservation Biology, 2011)
Much of the remaining grassland, particularly in North America, is privately owned, and its conversion to cultivated cropland is largely driven by economics. An understanding of why landowners convert grassland to cropland could facilitate more effective design of grassland‐conservation programs. We built an empirical model of land‐use change in the Prairie Pothole Region (north‐central United States) to estimate the probability of grassland conversion to alternative agricultural land uses, including cultivated crops. Conversion was largely driven by landscape characteristics and the economic returns of alternative uses. Our estimate of the probability of grassland conversion to cultivated crops (1.33% on average from 1979 to 1997) was higher than past estimates (0.4%). Our model also predicted that grassland‐conversion probabilities will increase if agricultural commodity prices continue to follow the trends observed from 2001 to 2006 (0.93% probability of grassland conversion to cultivated crops in 2006 to 1.5% in 2011). Thus, nearly 121 million ha (30 million acres) of grassland could be converted by 2011. Conversion probabilities, however, are spatially heterogeneous (range 0.2% to 3%), depending on characteristics of a parcel (e.g., soil quality and economic returns). Grassland parcels with relatively high‐quality land for agricultural production are more likely to be converted to cultivated crops than lower‐quality parcels and are more responsive to changes in the economic returns on alternative agricultural land uses (i.e., conversion probability increases by a larger magnitude for high‐quality parcels when economics returns to alternative uses increase). Our results suggest that grassland conservation programs could be proactively targeted toward high‐risk parcels by anticipating changes in economic returns, such as could occur if a new biofuel processing plant were to be built in an area.

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Effects of Central Airway Shunting on the Mechanical Impedance of the Mouse Lung - Benjamin L. Schwartz; Ron C. Anafi; Minara Aliyeva; John A. Thompson-Figueroa; Gilman B. Allen; Lennart K. A. Lundblad; Jason H. T. Bates (Annals of Biomedical Engineering, 2011)

Prevalence of Cancer Visits by Physician Specialty, 1997–2006 - Benjamin M. Craig; Bethany A. Bell; Gwendolyn P. Quinn; Susan T. Vadaparampil (Journal of Cancer Education, 2010)

KISS1 over-expression suppresses metastasis of pancreatic adenocarcinoma in a xenograft mouse model - Lacey R. McNally; Danny R. Welch; Benjamin H. Beck; Lewis J. Stafford; Joshua W. Long; Jeffery C. Sellers; Zhi Q. Huang; William E. Grizzle; Cecil R. Stockard; Kevin T. Nash; Donald J. Buchsbaum (Clinical & Experimental Metastasis, 2010)

Characterizing relationships between population density and nighttime imagery for Denver, Colorado: issues of scale and representation - Sharolyn J. Anderson; Benjamin T. Tuttle; Rebecca L. Powell; Paul C. Sutton (International Journal of Remote Sensing, 2010)

Interactive effects of ontogeny, food ration and temperature on elemental incorporation in otoliths of a coral reef fish - Benjamin D. Walther; Michael J. Kingsford; Mark D. O’Callaghan; Malcolm T. McCulloch (Environmental Biology of Fishes, 2010)

Efficacy of surface-generated nitric oxide against Candida albicans adhesion and biofilm formation - Benjamin J. Privett; Steven T. Nutz; Mark H. Schoenfisch (Biofouling, 2010)

Founding population size of an aquatic invasive species - Steven T. Kalinowski; Clint C. Muhlfeld; Christopher S. Guy; Benjamin Cox (Conservation Genetics, 2010)

Evidence for inheritance in patients with VACTERL association - Benjamin D. Solomon; Daniel E. Pineda-Alvarez; Manu S. Raam; Derek A. T. Cummings (Human Genetics, 2010)

GEOCHEM-EZ: a chemical speciation program with greater power and flexibility - Jon E. Shaff; Benjamin A. Schultz; Eric J. Craft; Randy T. Clark; Leon V. Kochian (Plant and Soil, 2010)

Is it possible to identify habitat for a rare species? Shortjaw Cisco (Coregonus zenithicus) in Lake Huron as a case study - Benjamin T. Naumann; Stephen S. Crawford (Environmental Biology of Fishes, 2009)

Does hunting regulate cougar populations? A test of the compensatory mortality hypothesis - Hilary S. Cooley; Robert B. Wielgus; Gary M. Koehler; Hugh S. Robinson; Benjamin T. Maletzke (Ecology, 2009)
Many wildlife species are managed based on the compensatory mortality hypothesis, which predicts that harvest mortality (especially adult male mortality) will trigger density‐dependent responses in reproduction, survival, and population growth caused via reduced competition for resources. We tested the compensatory mortality hypothesis on two cougar ( Puma concolor ) populations in Washington, USA (one heavily hunted and one lightly hunted). We estimated population growth, density, survival, and reproduction to determine the effects of hunting on cougar population demography based on data collected from 2002 to 2007. In the heavily hunted population, the total hunting mortality rate (mean ± SD) was 0.24 ± 0.05 (0.35 ± 0.08 for males, 0.16 ± 0.05 for females). In the lightly hunted population, the total hunting mortality rate was 0.11 ± 0.04 (0.16 ± 0.06 for males, 0.07 ± 0.05 for females). The compensatory mortality hypothesis predicts that higher mortality will result in higher maternity, kitten survival, reproductive success, and lower natural mortality. We found no differences in rates of maternity or natural mortality between study areas, and kitten survival was lower in the heavily hunted population. We rejected the compensatory mortality hypothesis because vital rates did not compensate for hunting mortality. Heavy harvest corresponded with increased immigration, reduced kitten survival, reduced female population growth, and a younger overall age structure. Light harvest corresponded with increased emigration, higher kitten survival, increased female population growth, and an older overall age structure. Managers should not assume the existence of compensatory mortality when developing harvest prescriptions for cougars.

Abnormal Fronto-striatal Connectivity in Children with Histories of Early Deprivation: A Diffusion Tensor Imaging Study - Michael E. Behen; Otto Muzik; Anita S. D. Saporta; Benjamin J. Wilson; Darshan Pai; Jing Hua; Harry T. Chugani (Brain Imaging and Behavior, 2009)

Adaptive differences in gene expression associated with heavy metal tolerance in the soil arthropod Orchesella cincta - DICK ROELOFS; THIERRY K. S. JANSSENS; MARTIJN J. T. N. TIMMERMANS; BENJAMIN NOTA; JANINE MARIËN; ZOLTÁN BOCHDANOVITS; BAUKE YLSTRA; NICO M. VAN STRAALEN (Molecular Ecology, 2009)
Field‐selected tolerance to heavy metals has been reported for Orchesella cincta (Arthropoda: Collembola) populations occurring at metal‐contaminated mining sites. This tolerance correlated with heritable increase in metal excretion efficiency, less pronounced cadmium (Cd)‐induced growth reduction and overexpression of the metallothionein gene. We applied transcriptomics to determine differential gene expression caused by this abiotic stress in reference and Cd‐tolerant populations. Many cDNAs responded to Cd exposure in the reference population. Significantly fewer clones were Cd responsive in tolerant animals. Analysis of variance revealed transcripts that interact between Cd exposure and population. Hierarchical cluster analysis of these clones identified two major groups. The first one contained cDNAs that were up‐regulated by Cd in the reference culture but non‐responsive or down‐regulated in tolerant animals. This cluster was also characterized by elevated constitutive expression in the tolerant population. Gene ontology analysis revealed that these cDNAs were involved in structural integrity of the cuticle, anti‐microbial defence, calcium channel‐blocking, sulphur assimilation and chromatin remodelling. The second group consisted of cDNAs down‐regulated in reference animals but not responding or slightly up‐regulated in tolerant animals. Their functions involved carbohydrate metabolic processes, Ca 2+ ‐dependent stress signalling, redox state, proteolysis and digestion. The reference population showed a strong signature of stress‐induced genome‐wide perturbation of gene expression, whereas the tolerant animals maintained normal gene expression upon Cd exposure. We confirmed the micro‐evolutionary processes occurring in soil arthropod populations and suggest a major contribution of gene regulation to the evolution of a stress‐adapted phenotype.

Identification of human sperm transcripts as candidate markers of male fertility - Claudia Lalancette; Adrian E. Platts; Graham D. Johnson; Benjamin R. Emery; Douglas T. Carrell; Stephen A. Krawetz (Journal of Molecular Medicine, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Modeling the effects of El Niño, density‐dependence, and disturbance on harbor seal ( Phoca vitulina ) counts in Drakes Estero, California: 1997–2007 - Benjamin H. Becker; David T. Press; Sarah G. Allen (Marine Mammal Science, 2009)
Harbor seal ( Phoca vitulina ) haul‐out site use may be affected by natural or anthropogenic factors. Here, we use an 11‐yr (1997–2007) study of a seal colony located near a mariculture operation in Drakes Estero, California, to test for natural (El Niño‐Southern Oscillation (ENSO), density‐dependence, long‐term trends) and anthropogenic (disturbance or displacement related to oyster production activities) factors that may influence the use of haul‐out subsites. Annual mariculture related seal disturbance rates increased significantly with increases in oyster harvest ( r s = 0.55). Using generalized linear models (GLMs) ranked by best fit and Akaike's Information Criteria, ENSO and oyster production (as a proxy for disturbance/displacement) best explained the patterns of seal use at all three subsites near the mariculture operations, with effects being stronger at the two subsites closest to operations. Conversely, density‐dependence and linear trend effects poorly explained the counts at these subsites. We conclude that a combination of ENSO and mariculture activities best explain the patterns of seal haul‐out use during the breeding/pupping season at the seal haul‐out sites closest to oyster activities.

The scale-dependent importance of habitat factors and dispersal limitation in structuring Great Lakes shoreline plant communities - E. Binney Girdler; Benjamin T. Connor Barrie (Plant Ecology, 2008)

Perchlorate Distribution, Excretion, and Depuration in Prairie Voles and Deer Mice - Qiuqiong Cheng; Fujun Liu; Philip N. Smith; W. Andrew Jackson; Scott T. McMurry; Michael J. Hooper; Ernest E. Smith; Benjamin C. Blount; Liza Valentin-Blasini; Todd A. Anderson (Water, Air, & Soil Pollution, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

CO 2 fertilization in temperate FACE experiments not representative of boreal and tropical forests - THOMAS HICKLER; BENJAMIN SMITH; I. COLIN PRENTICE; KRISTINA MJÖFORS; PAUL MILLER; ALMUT ARNETH; MARTIN T. SYKES (Global Change Biology, 2008)
Results from free‐air CO 2 enrichment (FACE) experiments in temperate climates indicate that the response of forest net primary productivity (NPP) to elevated CO 2 might be highly conserved across a broad range of productivities. In this study, we show that the LPJ‐GUESS dynamic vegetation model reproduces the magnitude of the NPP enhancement at temperate forest FACE experiments. A global application of the model suggests that the response found in the experiments might also be representative of the average response of forests globally. However, the predicted NPP enhancement in tropical forests is more than twice as high as in boreal forests, suggesting that currently available FACE results are not applicable to these ecosystems. The modeled geographic pattern is to a large extent driven by the temperature dependence of the relative affinities of the primary assimilation enzyme (Rubisco) for CO 2 and O 2 .

A cross‐system synthesis of consumer and nutrient resource control on producer biomass - Daniel S. Gruner; Jennifer E. Smith; Eric W. Seabloom; Stuart A. Sandin; Jacqueline T. Ngai; Helmut Hillebrand; W. Stanley Harpole; James J. Elser; Elsa E. Cleland; Matthew E. S. Bracken; Elizabeth T. Borer; Benjamin M. Bolker (Ecology Letters, 2008)
Nutrient availability and herbivory control the biomass of primary producer communities to varying degrees across ecosystems. Ecological theory, individual experiments in many different systems, and system‐specific quantitative reviews have suggested that (i) bottom–up control is pervasive but top–down control is more influential in aquatic habitats relative to terrestrial systems and (ii) bottom–up and top–down forces are interdependent, with statistical interactions that synergize or dampen relative influences on producer biomass. We used simple dynamic models to review ecological mechanisms that generate independent vs. interactive responses of community‐level biomass. We calibrated these mechanistic predictions with the metrics of factorial meta‐analysis and tested their prevalence across freshwater, marine and terrestrial ecosystems with a comprehensive meta‐analysis of 191 factorial manipulations of herbivores and nutrients. Our analysis showed that producer community biomass increased with fertilization across all systems, although increases were greatest in freshwater habitats. Herbivore removal generally increased producer biomass in both freshwater and marine systems, but effects were inconsistent on land. With the exception of marine temperate rocky reef systems that showed positive synergism of nutrient enrichment and herbivore removal, experimental studies showed limited support for statistical interactions between nutrient and herbivory treatments on producer biomass. Top–down control of herbivores, compensatory behaviour of multiple herbivore guilds, spatial and temporal heterogeneity of interactions, and herbivore‐mediated nutrient recycling may lower the probability of consistent interactive effects on producer biomass. Continuing studies should expand the temporal and spatial scales of experiments, particularly in understudied terrestrial systems; broaden factorial designs to manipulate independently multiple producer resources (e.g. nitrogen, phosphorus, light), multiple herbivore taxa or guilds (e.g. vertebrates and invertebrates) and multiple trophic levels; and – in addition to measuring producer biomass – assess the responses of species diversity, community composition and nutrient status.

Recent divergence with gene flow in Tennessee cave salamanders (Plethodontidae: Gyrinophilus ) inferred from gene genealogies - MATTHEW L. NIEMILLER; BENJAMIN M. FITZPATRICK; BRIAN T. MILLER (Molecular Ecology, 2008)
Cave organisms occupy a special place in evolutionary biology because convergent morphologies of many species demonstrate repeatability in evolution even as they obscure phylogenetic relationships. The origin of specialized cave‐dwelling species also raises the issue of the relative importance of isolation vs. natural selection in speciation. Two alternative hypotheses describe the origin of subterranean species. The ‘climate‐relict’ model proposes allopatric speciation after populations of cold‐adapted species become stranded in caves due to climate change. The ‘adaptive‐shift’ model proposes parapatric speciation driven by divergent selection between subterranean and surface habitats. Our study of the Tennessee cave salamander complex shows that the three nominal forms ( Gyrinophilus palleucus palleucus , G. p. necturoides , and G. gulolineatus ) arose recently and are genealogically nested within the epigean (surface‐dwelling) species, G. porphyriticus . Short branch lengths and discordant gene trees were consistent with a complex history involving gene flow between diverging forms. Results of coalescent‐based analysis of the distribution of haplotypes among groups reject the allopatric speciation model and support continuous or recurrent genetic exchange during divergence. These results strongly favour the hypothesis that Tennessee cave salamanders originated from spring salamanders via divergence with gene flow.

Three dimensional kinematics of rapid compensatory eye movements in humans with unilateral vestibular deafferentation - Jun-Ru Tian; Benjamin T. Crane; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2007)

Expression of the cytoskeleton linker protein ezrin in human cancers - Benjamin Bruce; Gaurav Khanna; Ling Ren; Goran Landberg; Karin Jirström; Charles Powell; Alain Borczuk; Evan T. Keller; Kirk J. Wojno; Paul Meltzer; Kristin Baird; Andrea McClatchey; et al. (Clinical & Experimental Metastasis, 2007)

Ascertainment Bias and the Pattern of Nucleotide Diversity at the Human ALDH2 Locus in a Japanese Population - Benjamin T. Brown; August Woerner; Jason A. Wilder (Journal of Molecular Evolution, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Redirection of carotenoid metabolism for the efficient production of taxadiene [taxa-4(5),11(12)-diene] in transgenic tomato fruit - Katalin Kovacs; Lina Zhang; Robert S. T. Linforth; Benjamin Whittaker; Christopher J. Hayes; Rupert G. Fray (Transgenic Research, 2007)

Probabilistic analysis of recessive mutagenesis screen strategies - Jeremy D. Silver; Douglas J. Hilton; Melanie Bahlo; Benjamin T. Kile (Mammalian Genome, 2007)

Changes in European ecosystem productivity and carbon balance driven by regional climate model output - PABLO MORALES; THOMAS HICKLER; DAVID P. ROWELL; BENJAMIN SMITH; MARTIN T. SYKES (Global Change Biology, 2007)
Climate change resulting from the enhanced greenhouse effect together with the direct effect of increased atmospheric CO 2 concentrations on vegetation growth are expected to produce changes in the cycling of carbon in terrestrial ecosystems. Impacts will vary across Europe, and regional‐scale studies are needed to resolve this variability. In this study, we used the LPJ‐GUESS ecosystem model driven by a suite of regional climate model (RCM) scenarios from the European Union (EU) project PRUDENCE to estimate climate impacts on carbon cycling across Europe. We identified similarities and discrepancies in simulated climate impacts across scenarios, particularly analyzing the uncertainties arising from the range of climate models and emissions scenarios considered. Our results suggest that net primary production (NPP) and heterotrophic respiration (Rh) will generally increase throughout Europe, but with considerable variation between European subregions. The smallest NPP increases, and in some cases decreases, occurred in the Mediterranean, where many ecosystems switched from sinks to sources of carbon by 2100, mainly as a result of deteriorating water balance. Over the period 1991–2100, modeled climate change impacts on the European carbon balance ranged from a sink of 11.6 Gt C to a source of 3.3 Gt C, the average annual sink corresponding with 1.85% of the current EU anthropogenic emissions. Projected changes in carbon balance were more dependent on the choice of the general circulation model (GCM) providing boundary conditions to the RCM than the choice of RCM or the level of anthropogenic greenhouse gases emissions.

Spring photosynthesis in a cool temperate bog - TIM R. MOORE; PETER M. LAFLEUR; DIANE M. I. POON; BENJAMIN W. HEUMANN; J. W. SEAQUIST; NIGEL T. ROULET (Global Change Biology, 2006)
In northern ecosystems, the onset and growth of spring photosynthesis may have an important influence on the annual carbon (C) budget, yet the controls have not been clearly identified, especially for peatlands. We used a 5‐year set of daily carbon dioxide (CO 2 ) exchange measurements derived from an eddy covariance tower located at Mer Bleue, an ombrotrophic bog near Ottawa, Canada, from March to May [day‐of‐year (DOY) 60–150], 1999–2003. We used half‐hourly measured net ecosystem exchange minus modelled ecosystem respiration to estimate daily photosynthesis, as gross ecosystem production (GEP). The onset of GEP in each year was closely related to the thinning and disappearance of the snow cover, occurring between DOY 86 and 101. GEP increased during the spring, reaching 10‐day average values of between 5 and 9 g CO 2 m −2 day −1 by the end of May. This increase was initially associated with moss activity ( Sphagnum and Polytrichum ), followed by the evergreen shrubs. Peat temperatures in the rooting zone (10–20 cm depth) and increases in shrub leaf nitrogen and chlorophyll a concentrations contributed to this rapid increase in GEP. Examination of moderate‐resolution imaging spectroradiometer (MODIS) images over several years revealed that the temporal resolution (16‐day composites) was inadequate to capture the onset of GEP but estimates of gross primary productivity and photosynthesis from MODIS 8‐day composites for the most part followed the pattern and magnitude of CO 2 exchange observed at the tower.

Biocolloid retention in partially saturated soils - Tammo S. Steenhuis; Annette Dathe; Yuniati Zevi; Jennifer L. Smith; Bin Gao; Stephen B. Shaw; Dilkushi DeAlwis; Samary Amaro-Garcia; Rosemarie Fehrman; M. Ekrem Cakmak; Ian C. Toevs; Benjamin M. Liu; et al. (Biologia, 2006)

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sönke Zaehle (Global Ecology and Biogeography, 2006)
Aim To implement plant hydraulic architecture within the Lund–Potsdam–Jena Dynamic Global Vegetation Model (LPJ–DGVM), and to test the model against a set of observational data. If the model can reproduce major patterns in vegetation and ecosystem processes, we consider this to be an important linkage between plant physiology and larger‐scale ecosystem dynamics. Location The location is global, geographically distributed. Methods A literature review was carried out to derive model formulations and parameter values for representing the hydraulic characteristics of major global plant functional types (PFTs) in a DGVM. After implementing the corresponding formulations within the LPJ–DGVM, present‐day model output was compared to observational data. Results The model reproduced observed broad‐scale patterns in potential natural vegetation, but it failed to distinguish accurately between different types of grassland and savanna vegetation, possibly related to inadequate model representations of water fluxes in the soil and wildfire effects. Compared to a version of the model using an empirical formulation for calculating plant water supply without considering plant hydraulic architecture, the new formulation improved simulated patterns of vegetation in particular for dry shrublands. Global‐scale simulation results for runoff and actual evapotranspiration (AET) corresponded well to available data. The model also successfully reproduced the magnitude and seasonal cycle of AET for most EUROFLUX forests, while modelled variation in NPP across a large number of sites spanning several biomes showed a strong correlation with estimates from field measurements. Main conclusions The model was generally confirmed by comparison to observational data. The novel model representation of water flow within plants makes it possible to resolve mechanistically the effects of hydraulic differences between plant functional groups on vegetation structure, water cycling, and competition. This may be an advantage when predicting ecosystem responses to nonextant climates, in particular in areas dominated by dry shrubland vegetation.

Modelling Regional Climate Change Effects On Potential Natural Ecosystems in Sweden - Deniz Koca; Benjamin Smith; Martin T. Sykes (Climatic Change, 2006)

Timecourse microarray analyses reveal global changes in gene expression of susceptible Glycine max (soybean) roots during infection by Heterodera glycines (soybean cyst nematode) - Nadim W. Alkharouf; Vincent P. Klink; Imed B. Chouikha; Hunter S. Beard; Margaret H. MacDonald; Susan Meyer; Halina T. Knap; Rana Khan; Benjamin F. Matthews (Planta, 2006)

Implementing plant hydraulic architecture within the LPJ Dynamic Global Vegetation Model - Thomas Hickler; I. Colin Prentice; Benjamin Smith; Martin T. Sykes; Sonke Zaehle (Global Ecology and Biogeography, 2006)

Tidal circulation in Tasman and Golden Bays: Implications for river plume behaviour - Benjamin J. Tuckey; Mark T. Gibbs; Benjamin R. Knight; Paul A. Gillespie (New Zealand Journal of Marine and Freshwater Research, 2006)
An investigation into the tidal residual circulation in the Tasman/Golden Bays system was performed. This investigation involved collecting hydrographic and current meter data, and configuring a numerical circulation model. The model was able to reproduce the gross features of the major tidal flows within the system revealed by the data. The simulated tidal residual circulation conformed to that previously suggested, except along the western side of Tasman Bay where this investigation suggests that residual flows move northwards. The validated model was then used to produce simulations of the fate of the plumes from the major rivers. Salinity field simulations describing different river flow and wind direction/velocity scenarios suggest that the Motueka River plume can cover considerable proportions of western side Tasman Bay, extending into Golden Bay during flood conditions. The embedded sediment transport model was also used to investigate the fate of fine sediments entering the bays. Simulated distribution patterns of fine sediments entering the bays from the four major tributaries were found to be consistent with existing bathymetric and seabed substrate characteristics.

Sensitivity of African biomes to changes in the precipitation regime - Christelle Hely; Laurent Bremond; Samuel Alleaume; Benjamin Smith; Martin T. Sykes; Joel Guiot (Global Ecology and Biogeography, 2006)

Sensitivity of African biomes to changes in the precipitation regime - Christelle Hély; Laurent Bremond; Samuel Alleaume; Benjamin Smith; Martin T. Sykes; Joël Guiot (Global Ecology and Biogeography, 2006)
Aim Africa is identified by the Inter‐governmental Panel on Climate Change (IPCC) as the least studied continent in terms of ecosystem dynamics and climate variability. The aim of this study was (1) to adapt the Lund‐Postdam‐Jena‐GUESS (LPJ‐GUESS) ecological modelling framework to Africa by providing new parameter values for tropical plant functional types (PFT), and (2) to assess the sensitivity of some African biomes to changes in precipitation regime. Location The study area was a representative transect (0–22° N and 7–18° E) through the transition from equatorial evergreen forests to savannas, steppes and desert northwards. The transect showed large latitudinal variation in precipitation (mean rainfall ranged from 50 to 2300 mm year −1 ). Methods New PFT parameters used to calibrate LPJ‐GUESS were based on modern pollen PFTs and remote sensed leaf area index (LAI). The model was validated using independent modern pollen assemblages, LAI and through comparison with White's modern potential vegetation map. Several scenarios were developed by combining changes in total rainfall amount with variation in the length of the dry season in order to test the sensitivity of African biomes. Results Simulated vegetation compared well to observed data at local and regional scales, in terms of ecosystem functioning (LAI), and composition (pollen and White's vegetation map). The assessment of the sensitivity of biomes to changes in precipitation showed that none of the ecosystems would shift towards a new type under the range of precipitation increases suggested by the IPCC (increases from 5 to 20%). However, deciduous and semi‐deciduous forests may be very sensitive to small reductions in both the amount and seasonality of precipitation. Main conclusions This version of LPJ‐GUESS parameterized for Africa simulated correctly the vegetation present over a wide precipitation gradient. The biome sensitivity assessment showed that, compared with savannas and grasslands, closed canopy forests may be more sensitive to change in precipitation regime due to the synergetic effects of changed rainfall amounts and seasonality on vegetation functioning.

Comparing and evaluating process‐based ecosystem model predictions of carbon and water fluxes in major European forest biomes - Pablo Morales; Martin T. Sykes; I. Colin Prentice; Pete Smith; Benjamin Smith; Harald Bugmann; Bärbel Zierl; Pierre Friedlingstein; Nicolas Viovy; Santi Sabaté; Anabel Sánchez; Eduard Pla; et al. (Global Change Biology, 2005)
Process‐based models can be classified into: (a) terrestrial biogeochemical models (TBMs), which simulate fluxes of carbon, water and nitrogen coupled within terrestrial ecosystems, and (b) dynamic global vegetation models (DGVMs), which further couple these processes interactively with changes in slow ecosystem processes depending on resource competition, establishment, growth and mortality of different vegetation types. In this study, four models – RHESSys, GOTILWA+, LPJ‐GUESS and ORCHIDEE – representing both modelling approaches were compared and evaluated against benchmarks provided by eddy‐covariance measurements of carbon and water fluxes at 15 forest sites within the EUROFLUX project. Overall, model‐measurement agreement varied greatly among sites. Both modelling approaches have somewhat different strengths, but there was no model among those tested that universally performed well on the two variables evaluated. Small biases and errors suggest that ORCHIDEE and GOTILWA+ performed better in simulating carbon fluxes while LPJ‐GUESS and RHESSys did a better job in simulating water fluxes. In general, the models can be considered as useful tools for studies of climate change impacts on carbon and water cycling in forests. However, the various sources of variation among models simulations and between models simulations and observed data described in this study place some constraints on the results and to some extent reduce their reliability. For example, at most sites in the Mediterranean region all models generally performed poorly most likely because of problems in the representation of water stress effects on both carbon uptake by photosynthesis and carbon release by heterotrophic respiration ( R h ). The use of flux data as a means of assessing key processes in models of this type is an important approach to improving model performance. Our results show that the models have value but that further model development is necessary with regard to the representation of the some of the key ecosystem processes.

Melittin-induced membrane permeability: A nonosmotic mechanism of cell death - Juan Pablo Pratt; Dino J. Ravnic; Harold T. Huss; Xiaoqun Jiang; Benjamin S. Orozco; Steven J. Mentzer (In Vitro Cellular & Developmental Biology - Animal, 2005)

Mapping and Modeling the Biogeochemical Cycling of Turf Grasses in the United States - Cristina Milesi; Steven W. Running; Christopher D. Elvidge; John B. Dietz; Benjamin T. Tuttle; Ramakrishna R. Nemani (Environmental Management, 2005)

Comparison of effect of BMP-2, -4, and -6 on in vitro cartilage formation of human adult stem cells from bone marrow stroma - Ichiro Sekiya; Benjamin L. Larson; Jussi T. Vuoristo; Roxanne L. Reger; Darwin J. Prockop (Cell and Tissue Research, 2005)

Initiation and cancellation of the human heave linear vestibulo-ocular reflex after unilateral vestibular deafferentation - Benjamin T. Crane; Jun-Ru Tian; Akira Ishiyama; Joseph L. Demer (Experimental Brain Research, 2005)

Public Influences on Plantation Forestry - Glenn T. Howe; Bruce Shindler; Benjamin Cashore; Eric Hansen; Denise Lach; Ward Armstrong (Journal of Forestry, 2005)
For plantation forestry to be successful, it must be biologically possible, economically feasible, and culturally adoptable (i.e., socially acceptable). We discuss social acceptability and plantation forestry in the Pacific Northwest, stressing that social acceptability is a judgmental process that is both provisional and dependent on many complex factors, and that most decisions are based on intuition, rather than a rational evaluation of all relevant choices. We suggest that conflicts over plantation forestry can be minimized by carefully considering social acceptability and by forging formal agreements (accords) that promote the goals of both environmentalists and forest industries.

Predator effects on herbivore and plant stability - Benjamin S. Halpern; Elizabeth T. Borer; Eric W. Seabloom; Jonathan B. Shurin (Ecology Letters, 2005)
Humans are rapidly altering the diversity and composition of ecological communities by accelerating rates of species extinctions and introductions. These changes in diversity are not random and disproportionately involve the addition or extinction of predators. Theoretical and microcosm studies suggest predator removal may either increase or decrease ecosystem stability. Here we test whether the addition or removal of predators affects aggregate biomass stability in 40 experiments carried out in six different ecosystems. Predators did not alter the temporal variability of autotroph biomass, but significantly destabilized herbivore biomass. The effects of predators on herbivore biomass stability varied significantly among ecosystems, with benthic and pelagic lake systems showing the greatest shifts. Consequently, the addition of predators to communities, as occurs in many conservation efforts, biological control programmes and species introductions, may lead to more variable system dynamics.

MELITTIN-INDUCED MEMBRANE PERMEABILITY: A NONOSMOTIC MECHANISM OF CELL DEATH - JUAN PABLO PRATT; DINO J. RAVNIC; HAROLD T. HUSS; XIAOQUN JIANG; BENJAMIN S. OROZCO; STEVEN J. MENTZER (In Vitro Cellular & Developmental Biology - Animal, 2005)

LANDSCAPE DEVELOPMENT INTENSITY INDEX - MARK T. BROWN; M. BENJAMIN VIVAS (Environmental Monitoring and Assessment, 2005)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Analysis and glycosyl composition of the exopolysaccharide isolated from the floc‐forming wastewater bacterium Thauera sp. MZ1T - Michael S. Allen; Karen T. Welch; Benjamin S. Prebyl; David C. Baker; Arthur J. Meyers; Gary S. Sayler (Environmental Microbiology, 2004)
Summary Conditions were developed for the reproducible production, isolation and characterization of a novel microbial extracellular polysaccharide believed to be involved in transient viscous bulking at an industrial wastewater treatment plant. The exopolysaccharide was extracted from cell‐free culture supernatants of Thauera sp. strain MZ1T grown on a minimal medium with succinate. The purified polymer was found to be approximately 260 kDa in size by gel‐permeation chromatography. The GC–MS analysis of the alditol acetate and per‐ O ‐trimethylsilyl methyl glycoside derivatives revealed that the exopolysaccharide was composed of four monosaccharides including: rhamnose, galacturonic acid, N ‐acetylglucosamine and N ‐acetylfucosamine. Glucose, which also appeared at low levels, is most likely from a co‐eluting glucan. The FTIR and NMR spectroscopic analyses further revealed the presence of esterified component groups on the polymer. These results represent the first published description of a polysaccharide from a member of the genus Thauera , and lay the foundation for a deeper understanding of the factors potentially involved in zoogloeal cluster formation and viscous bulking.

Species-Specific Allozyme Markers for Appalachian Wood-Feeding Cockroaches (Dictyoptera: Cryptocercidae) - Benjamin T. Aldrich; Elliot Krafsur; Srinivas Kambhampati (Biochemical Genetics, 2004)

The effect of introgressions of wheat D-genome chromosomes into 'Presto' triticale - Hikmet Budak; P. Stephen Baenziger; Brian S. Beecher; Robert A. Graybosch; Benjamin T. Campbell; Marry J. Shipman; Mustafa Erayman; Kent M. Eskridge (Euphytica, 2004)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Nitrogen Dynamics in Ice Storm-Damaged Forest Ecosystems: Implications for Nitrogen Limitation Theory - Benjamin Z. Houlton; Charles T. Driscoll; Timothy J. Fahey; Gene E. Likens; Peter M. Groffman; Emily S. Bernhardt; Donald C. Buso (Ecosystems, 2003)

Sex and strain-related differences in the peripheral blood cell values of inbred mouse strains - Benjamin T. Kile; Cammy L. Mason-Garrison; Monica J. Justice (Mammalian Genome, 2003)

Initiation of the human heave linear vestibulo-ocular reflex - Benjamin T. Crane; Junru Tian; Gerald Wiest; Joseph L. Demer (Experimental Brain Research, 2003)

A cross‐ecosystem comparison of the strength of trophic cascades - Jonathan B. Shurin; Elizabeth T. Borer; Eric W. Seabloom; Kurt Anderson; Carol A. Blanchette; Bernardo Broitman; Scott D. Cooper; Benjamin S. Halpern (Ecology Letters, 2002)
Although trophic cascades (indirect effects of predators on plants via herbivores) occur in a wide variety of food webs, the magnitudes of their effects are often quite variable. We compared the responses of herbivore and plant communities to predator manipulations in 102 field experiments in six different ecosystems: lentic (lake and pond), marine, and stream benthos, lentic and marine plankton, and terrestrial (grasslands and agricultural fields). Predator effects varied considerably among systems and were strongest in lentic and marine benthos and weakest in marine plankton and terrestrial food webs. Predator effects on herbivores were generally larger and more variable than on plants, suggesting that cascades often become attenuated at the plant–herbivore interface. Top‐down control of plant biomass was stronger in water than on land; however, the differences among the five aquatic food webs were as great as those between wet and dry systems.

Effect of aging on the human initial interaural linear vestibulo-ocular reflex - Jun-Ru Tian; Benjamin T. Crane; Gerald Wiest; Joseph L. Demer (Experimental Brain Research, 2002)

Egg-marking pheromones in honey-bees Apis mellifera - Benjamin P. Oldroyd; Francis L. W. Ratnieks; T. C. Wossler (Behavioral Ecology and Sociobiology, 2002)

Regeneration in Gap Models: Priority Issues for Studying Forest Responses to Climate Change - David T. Price; Niklaus E. Zimmermann; Peter J. van der Meer; Manfred J. Lexer; Paul Leadley; Irma T. M. Jorritsma; Jörg Schaber; Donald F. Clark; Petra Lasch; Steve McNulty; Jianguo Wu; Benjamin Smith (Climatic Change, 2001)

Representation of vegetation dynamics in the modelling of terrestrial ecosystems: comparing two contrasting approaches within European climate space - Benjamin Smith; I. Colin Prentice; Martin T. Sykes (Global Ecology and Biogeography, 2001)
Advances in dynamic ecosystem modelling have made a number of different approaches to vegetation dynamics possible. Here we compare two models representing contrasting degrees of abstraction of the processes governing dynamics in real vegetation. Model (a) (GUESS) simulates explicitly growth and competition among individual plants. Differences in crown structure (height, depth, area and LAI) influence relative light uptake by neighbours. Assimilated carbon is allocated individually by each plant to its leaf, fine root and sapwood tissues. Carbon allocation and turnover of sapwood to heartwood in turn govern height and diameter growth. Model (b) (LPJ) incorporates a ‘dynamic global vegetation model’ (DGVM) architecture, simulating growth of populations of plant functional types (PFTs) over a grid cell, integrating individual‐level processes over the proportional area (foliar projective cover, FPC) occupied by each PFT. Individual plants are not simulated, but are replaced by explicit parameterizations of their growth and interactions. The models are identical in their representation of core physiological and biogeochemical processes. Both also use the same set of PFTs, corresponding to the major woody plant groups in Europe, plus a grass type. When applied at a range of locations, broadly spanning climatic variation within Europe, both models successfully predicted PFT composition and succession within modern natural vegetation. However, the individual‐based model performed better in areas where deciduous and evergreen types coincide, and in areas subject to pronounced seasonal water deficits, which would tend to favour grasses over drought‐intolerant trees. Differences in model performance could be traced to their treatment of individual‐level processes, in particular light competition and stress‐induced mortality. Our results suggest that an explicit individual‐based approach to vegetation dynamics may be an advantage in modelling of ecosystem structure and function at the resolution required for regional‐ to continental‐scale studies.

An introduction to the European Terrestrial Ecosystem Modelling Activity - Martin T. Sykes; I. Colin Prentice; Benjamin Smith; Wolfgang Cramer; Sergey Venevsky (Global Ecology and Biogeography, 2001)
The objective of the European Terrestrial Ecosystem Modelling Activity (ETEMA) was to address some of the major challenges in developing generalized models to examine responses of natural and seminatural ecosystems to environmental change at the regional to European scale. The approach described herein was to break down the totality of ecosystem functioning into its key components, each with its characteristic spatial and temporal scales. A conceptual framework was developed describing the configuration of these components as modules within a generalized simulation model. The framework describes the key inputs, outputs and state variables, their spatial and temporal contexts, and information flows between modules. The ‘backbone’ of the model is a system of nested timing loops corresponding to the disparate time scales at which different ecosystem processes occur. The framework is a theoretical construct into which ecosystem models at levels of complexity ranging from the very general to the highly detailed can be mapped, and thus provides a guide for development of models for novel, particularly regional‐scale, applications. A number of subsystem studies of the major components of ecosystem functioning, i.e. modules of the conceptual framework, are briefly introduced herein. The general aim of the subsystem studies was to identify the key alternative formulations (as opposed to minor variants) and test these against observational data. The various subsystem studies concern planetary boundary layer–ecosystem interactions, ecosystem CO 2 and H 2 O fluxes, vegetation physiology and phenology, biogeography and vegetation dynamics, detritus and SOM dynamics, soil moisture and human and natural disturbances and, as individual papers, they complete this special ETEMA issue.

Carbon, water and nutrient flux in Maya homegardens in the Yucatán peninsula of México - T. J. Benjamin; P. I. Montañez; J. J. M. Jaménez; A. R. Gillespie (Agroforestry Systems, 2001)

Vestibular catch-up saccades in labyrinthine deficiency - Jun-ru Tian; Benjamin T. Crane; Joseph L. Demer (Experimental Brain Research, 2000)

Initial vestibulo-ocular reflex during transient angular and linear acceleration in human cerebellar dysfunction - Benjamin T. Crane; Jun-Ru Tian; Joseph L. Demer (Experimental Brain Research, 2000)

Defining competition vectors in a temperate alley cropping system in the midwestern USA: 4. The economic return of ecological knowledge - T. J. Benjamin; W.L. Hoover; J.R. Seifert; A.R. Gillespie (Agroforestry Systems, 2000)

Defining competition vectors in a temperate alley cropping system in the midwestern USA: 1. Production physiology - A. R. Gillespie; S. Jose; D. B. Mengel; W. L. Hoover; P. E. Pope; J. R. Seifert; D. J. Biehle; T. Stall; T. J. Benjamin (Agroforestry Systems, 2000)

A linear canal-otolith interaction model to describe the human vestibulo-ocular reflex - Benjamin T. Crane; Joseph L. Demer (Biological Cybernetics, 1999)

Cloning, expression, and promoter structure of a mammalian Inner Centromere Protein (INCENP) - Richard Saffery; Danielle V. Irvine; Benjamin T. Kile; Damien F. Hudson; Suzanne M. Cutts; K.H. Andy Choo (Mammalian Genome, 1999)

Lorazepam for chronic catatonia: a randomized, double-blind, placebo-controlled cross-over study - G. S. Ungvari; Helen F. K. Chiu; Lok Yee Chow; Benjamin S. T. Lau; Wai Kwong Tang (Psychopharmacology, 1999)

Horizontal vestibulo-ocular reflex and head stability in response to torso perturbations during visual search - Benjamin T. Crane; J. L. Demer (Experimental Brain Research, 1999)

Gaze stabilization during dynamic posturography in normal and vestibulopathic humans - Benjamin T. Crane; J. L. Demer (Experimental Brain Research, 1998)

Molecular characterization and sequencing of antifreeze proteins from larvae of the beetle Dendroides canadensis - J. G. Duman; N. Li; D. Verleye; F. W. Goetz; D. W. Wu; C. A. Andorfer; T. Benjamin; D. C. Parmelee (Journal of Comparative Physiology B, 1998)

The human horizontal vestibulo-ocular reflex during combined linear and angular acceleration - Benjamin T. Crane; Erik S. Viirre; J. L. Demer (Experimental Brain Research, 1997)

Using Decision Analysis to Include Climate Change in Water Resources Decision Making - Benjamin F. Hobbs; Philip T. Chao; Boddu N. Venkatesh (Climatic Change, 1997)

Effect of ?-cyclodextrin on mucochloric acid and 3-chloro-4-(dichloromethyl)-5-hydroxy-2(5H)-furanone - Ieva R. Politzer; Kathleen T. Crago; Wendy Benjamin; Jocelyn Joseph; Keith Amos; W. Emile Coleman (Archives of Environmental Contamination and Toxicology, 1991)